Proteomic and metabolomic analysis of Litopenaeus vannamei infected with infectious hypodermal and hematopoietic necrosis virus (IHHNV) - Fan Yang; Shou-Xin Luo; Zhi-Peng Yin; Ling-Jun Si; Ting Li; Lin-Rui Chang; Dong-Chun Yan (Aquaculture, 2027)

PCB2 improves porcine oocyte maturation by enhancing TZP-mediated cumulus-oocyte communication - Yuwen Luo; Qingrui Zhuan; Dan Zhou; Hongyu Liu; Jun Li; Xiangwei Fu (Theriogenology, 2026)

Drip irrigation with fulvic acid influences ammonia volatilization and greenhouse gas emissions by improving surface and subsurface soil environments - Hao Liu; Jun Wang; Jiusheng Li; Long Wang; Taofeng Luo; Chaofan Zhang (Soil and Tillage Research, 2026)

High-resolution carbon isotope chemostratigraphy of the upper Cambrian from the East Tarim Basin and implications for global correlation and paleoenvironment reconstruction - Xiao-Jun Zuo; Bo Chen; Hong-Xing Wei; Zhi-Xin Sun; Xin-Sheng Luo; Guo-Xiang Li; Zhi-Bin Huang; Miao Lu; Yong-Quan Chen; Ai-Hua Yang; Fang-Chen Zhao; Mao-Yan Zhu (Palaeoworld, 2026)

Single-cell transcriptomics reveals cellular heterogeneity and cell–cell communication networks in free gossypol-induced enteritis in juvenile largemouth bass (Micropterus salmoides) - Xinpeng Wang; Wanying Jiang; Linlin Li; Jun Wen; Limeng Wang; Shimei Lin; Yongjun Chen; Li Luo; Xinghua Zhou; Yuanfa He (Fish & Shellfish Immunology, 2026)

Safety and efficacy of recombinant botulinum toxin type A (Eveotox®) in patients with post-stroke upper limb spasticity: Results from a Phase Ib/II clinical trial - Rongrong Lu; Lingjing Jin; Jianzhong Xiong; Lixin Zhang; Yaling Liu; Leilei Xu; Rui Wu; Jianhua Tang; Liandong Zhao; Lihua Dong; Weifeng Luo; Yu Pan; et al. (Toxicon, 2026)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

Monsoon intensification as a driver of enhanced biogenic silica burial during the Bajocian cooling event in the western Yarlung Zangbo Suture Zone, southern Tibet - Xiaohui Cui; Xin Li; Jonathan C. Aitchison; Mei-Fu Zhou; Yichun Zhang; Jun Chen; Xuejin Wu; Xiru Li; Jiaqi Song; Hui Luo (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Sex peptide receptor modulates sex pheromone perception plasticity in female Galleria mellonella across mating status - Zhen-Ping Guo; Xu-Dong Pang; Li-Lin Luo; Ming-Qing Yu; Jun-Hong Linghu; Hua-Yan Xie; Guy Smagghe; Tong-Xian Liu; Shun-Hua Gui (Insect Biochemistry and Molecular Biology, 2026)

Exogenous melatonin partially alleviates the effects of reduced nitrogen by enhancing photosynthetic carbon assimilation, nitrogen assimilation, and grain yield in field-grown rice - Yangming Ma; Xiana Tie; Yuanqing Shi; Ning Liu; Ruhongji Liu; Leilei Li; Guanzhou Luo; Ruijie Li; Cheng Wang; Xinghai Huang; Zhonglin Wang; Zongkui Chen; et al. (Field Crops Research, 2026)

Comparative performance analysis of ejector-enhanced graded coupled solar-air dual-source heat pumps for cold and low-irradiance applications - Shengyu Li; Mingxi Guan; Xiaoxiao Wang; Lulin Luo; Jun Lu (Energy and Buildings, 2026)

Exploring the mechanism of Panax notoginseng injection in the treatment of skin wound based on network pharmacology and experimental verification - Yibin Li; Qinglin Li; Jun Liu; Juncen Li; Huaman Geng; Genke Li; Huilin Huang; Chen Jin; Jie Luo; Zhihong Zhang (Journal of Molecular Histology, 2026)

Promoting chemical nitrogen uptake via nitrogen cycle of organisms in the rice-crayfish co-culture system - Jialu Qian; Zifang Chen; Xiaolei Gong; Jintao Li; Yishui Luo; Yali Li; Jun Hou (Aquaculture, 2026)

Reshaping geochemical fate of gold-mining-derived arsenic in Jiehe River sediments from molecular to field scales via an innovative iron-based mineralization strategy - Weichen Luo; Ting Li; Yujun Zhou; Baoting Ding; Xin Du; Xuan Liu; Yongpeng Zhang; Zhaodi Wu; Jianru Liang; Shuqing Li; Jun Chen; Lixiang Zhou (Water Research, 2026)

Freeze-thaw-induced destabilization of organic matter in Mollisols after decadal mineral fertilization - Dan-Dan Wang; Zhiming Zhang; Peng He; Shan-Shan Dai; Minghui Liu; Yu Luo; Tida Ge; Ekaterina Filimonenko; Yakov Kuzyakov; William R. Horwath; Lu-Jun Li (Soil Biology and Biochemistry, 2026)

The effects of combined irradiation with blue and white light-emitting diodes on alleviated browning and decay and mitochondrial function of Pleurotus eryngii is mediated by jasmonic acid - Shufen Luo; He Yang; Xuesong Liu; Huali Hu; Jun Ling; Pengxia Li (Postharvest Biology and Technology, 2026)

Toward engineering closed loops for carbon-based metal ion capture and selective recovery: Speciation, binding sites, and evidence standards - Shilong Chen; Junlong Zheng; Zhuocheng Li; Yinghong Wu; Longchao Zhuo; Wenxian Liu; Jun Luo; Xijun Liu (Journal of Environmental Chemical Engineering, 2026)

Al-modified ReS2/TiO2 with enhanced adsorption and stepwise interfacial charge migration for photocatalytic PFOA removal - Ran Chen; Feng Liu; Zhenkai Liu; Jun Wan; Qidi Liu; Yixin Ma; Yan Li; Shunli Wan; Yongming Luo; Haijiao Xie (Journal of Environmental Chemical Engineering, 2026)

Development of a NIR fluorescent probe HDI based on Zinc-mediated competitive coordination for multidimensional detection of glyphosate in complex systems - Ya-Tong Liu; Xi-Yue Luo; Bu-Xiao Wu; Yi-Wen Cui; Jun-Wen Wang; Ying-Kai Yuan; Yue-Li Zou; Li-Xia Zhao (Journal of Environmental Chemical Engineering, 2026)

Is the 5 mm inflow-based subdivision method necessary in the Xinanjiang model? - Jianfei Zhao; Wentao Li; Panpan Luo; Zhen Ding; Jun Wang; Binquan Li; Yiming Hu; Zhongmin Liang (Environmental Modelling & Software, 2026)

Multi-level biomarker responses in Eisenia fetida co-exposed to PE-MPs and DiBP: An ecological risk assessment based on physiological, biochemical, and molecular indicators - Yanan Zhang; Yumu Luo; Zhensi Meng; Jun Luo; Ke Li; Yuhang Lin; Minle Li; Rongren Bin; Mingming Fu; Ming Hung Wong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Oxophilic Nb incorporation induces reaction pathway transition in hollow RuO2 toward durable acidic oxygen evolution - Jie Zhang; Man Luo; Jun Liang; Wenyuan Gao; Jingbin Huang; Yibing Li; Xinhui Yang; Jie Zhu (Chemical Engineering Journal, 2026)

Toward integrated CO2 capture and photocatalytic conversion: From catalyst design to reactor engineering - Ziyi Li; Chenxi Ran; Jiao Feng; Jun Zhong; Jiaxin Xie; Yue-Fei Zhang; Xiao Luo; Yu Mao; Zhiwu Liang (Chemical Engineering Journal, 2026)

A data-driven multimodal diagnostic framework for quality evaluation of artificial calculus bovis based on HEMT biosensors and systematic quality data engineering - Kaiyi Wang; Fangyu Zhang; Yufeng Guo; Huimin Feng; Xinhai Chen; Jing Wang; Yifei Wang; Lu Yao; Zhaohua Zhang; Jun Jia; Yi Luo; Mingshuang Li; et al. (Chemical Engineering Journal, 2026)

Deciphering sulfidation chemistry of nanoscale zerovalent iron for enhanced reductive defluorination of trace PFOA: Precursor-driven core-shell engineering and electron transfer - Mi Li; Jing Wang; Qisheng Lu; Cui Hu; Yuping Qiu; Xinyi Zeng; Genhe He; Wei Hui; Kai He; Jun Zhong; Xiaoyu Xiao; Xubiao Luo (Chemical Engineering Journal, 2026)

Color-tunable and multi-stimuli-responsive room temperature phosphorescence based on an efficient supramolecular approach - Huan Yao; Yu-Ling Hu; Jun-Fu Chen; Han-Yu Luo; Wen-Jie Chen; Liu-Pan Yang; Li-Li Wang (Chemical Engineering Journal, 2026)

A mineralizable and electroactive periosteum for promoting infected bone defect repair by remodeling the osteogenic microenvironment - Yangyang Qu; Linghanqing Wang; Xinyue Yang; Shixing Luo; Chongnan Yan; Nizhou Jiang; Yanchao Zhang; Jingyi Qu; Sida Chen; Yuanming Xiao; Yifeng Shang; Jun Li; et al. (Chemical Engineering Journal, 2026)

An improved RF-XGBoost integrated approach for GNSS-IR snow depth estimation - Xinqiang Lei; Jun Zhang; Xinpeng Wang; Yixu Li; Haifang Jian; Fei Luo (Cold Regions Science and Technology, 2026)

Molecular mechanism of anammox granular sludge disintegration caused by polyethylene terephthalate micro/nanoplastics: a new perspective based on quorum sensing - Chaofan Xie; Dongyue Li; Jun Li; Jiarui Li; Muchen Yin; Yanshuo Wu; Chi Zhang; Rong Luo; Yuxi Zhu; Zehao Zhang; Zhaoming Zheng; Yongzhen Peng (Bioresource Technology, 2026)

Chemical constituents from the root of Bistorta suffulta (Maxim.) H. Gross and their chemotaxonomic significance - Xin-Yi Liu; Chun-Yi Li; Meng-Yin Luo; Xu Yang; Lu-Jun Li; Li-Juan Sun; Chun-Yang Shi (Biochemical Systematics and Ecology, 2026)

Contrasting representations of marine heatwaves due to baseline selection: implications for phytoplankton responses in the South China Sea - Wenbo He; Yongxiu Liang; Fuan Xiao; Yuchen Liang; Xiaomei Luo; Xinyan Li; Huajian Zheng; Jun Zhao (Journal of Oceanology and Limnology, 2026)

Testing the REVEALS model in monsoon–steppe landscapes: pollen-based quantitative land-cover reconstruction from lakes in northern China - Xiuxiu Ren; Laurent Marquer; Furong Li; Yuanhao Sun; Min Zheng; Lixiong Xiang; Jun Zhang; Haipeng Wang; Derui Luo; Chong Huang; Wenjia Wang; Guoqiang Ding; et al. (Quaternary Science Reviews, 2026)

Deciphering the carrier potential of microplastics aged in freeze-thaw soils: Multiscale insights into mechanisms for antibiotic adsorption amplification - Wen-hao Yang; Jian-yong Wu; Kong-yan Luo; Ling-li Ma; Bin Yan; Jin-song Guo; Jie Zeng; Yi-zhi Pei; Jun-min Gao (Journal of Hazardous Materials, 2026)

Integrated evaluation of cement mortar incorporating municipal solid waste incineration bottom ash-derived manufactured sand: Mechanical performance, microstructure, and life cycle assessment - Yulong Luo; Zhonghao Li; Yuheng Xue; Yundan Gui; Zhengdong Wang; Guangming Xie; Weizhuo Zhang; Lei Cheng; Jun Liu (Journal of Environmental Chemical Engineering, 2026)

Oat protein-EGCG-sugar beet pectin ternary complexes: Role of pectin in driving non-covalent interactions and improving functional properties - Zihao Chen; Muyao Luo; Taotao Dai; Min Fu; Zhaoying Li; Qin Geng; Jun Chen; Ti Li; Risi Wang (Food Hydrocolloids, 2026)

Impact of different animal and plant proteins on the structure, rheology and texture of nanocellulose composite oleogels - Yubo Zhu; Bing Zhao; Ai Li; Jia Luo; Jienan Li; Jun Sheng; Yang Tian; Xiufen Li (Food Hydrocolloids, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Novel Streptomyces sp. SCUT-3 promoter’ and 5’UTR chimeras enhanced its alginate lyase expression for kelp degradation - Jun Dai; Hai-Ning Wang; Can Qin; Peng-Bo Dan; Jun-Jin Deng; Lei Wu; Zhi-Wei Li; Fu-Gen Zhang; Chu-Yan Liang; Ming-Shu Zhang; Xiao-Chun Luo (Chemical Engineering Journal, 2026)

Suffocating bacterial pathogens: Material-based interventions targeting the respiratory chain - Ziyi Han; Luyi He; Jingji Hou; Wei Huang; Jun Luo; Jiaojiao Yang; Jianshu Li (Chemical Engineering Journal, 2026)

Corrigendum to “In-situ forming carboxymethyl chitosan hydrogel containing Paeonia suffruticosa Andr. leaf extract for mixed infectious vaginitis treatment by reshaping the micro-biota” [Carbohydrate Polymers 339 (2024) 122255] - Shiami Jia; Shengting Huang; Rezhemu Jimo; Yongbu AXi; Yuanhui Lu; Ziling Kong; Jun Ma; Heran Li; Xiao Luo; Yan Qu; Kaijun Gou; Rui Zeng; et al. (Carbohydrate Polymers, 2026)

Seasonal source shifts and toxicity implications of PM2.5-bound polycyclic aromatic hydrocarbons in central China: The critical role of underrated local emissions - Runqi Zhang; Sheng Li; Qiongwei Zhang; Jun Wang; Datong Luo; Zhan Liu; Xinming Wang (Atmospheric Pollution Research, 2026)

Diversified cropping combined with nutrient optimization regulates microbial resource limitations, thereby influencing ecoenzymatic carbon and nitrogen use efficiencies - Wei Zhang; Wanting Li; Zhuolin Li; Xinlei Li; Ruqi Duan; Dexiang Luo; Guohui Xiong; Mingmin Li; Jun Tao; Shichen Li; Yingfen Yang; Zhengxiong Zhao (Agriculture, Ecosystems & Environment, 2026)

Species Diversity, Parasitism Rates, Longevity, and Population Dynamics of the Parasitoid Complex Attacking Ophelimus bipolaris in China - Jin Hu; Yuan-Hao Li; Jing-Hui Su; Jin-Bo Sun; Guo-Bao Qin; Yan Qin; Lai-Feng Luo; Lin-Xia Feng; Kai-Jian Han; Zoya Yefremova; Jun Li; Xia-Lin Zheng (Neotropical Entomology, 2026)

The evaluation of biological effects of artesunate on ovarian cancer using three-dimensional cell culture methods - Yijun Yuan; Xiaojing Luo; Longyu Tang; Tianwen He; Xinru Zou; Lu Feng; Bin Su; Jia Wu; Jun Li; Dongqin Xiao (Cell and Tissue Banking, 2026)
Ovarian cancer (OC) is one of the most aggressive malignancies, with high mortality rates largely attributed to late-stage diagnosis, tumor heterogeneity, recurrence, and resistance to chemotherapy. Artesunate (ART), a water-soluble derivative traditionally used to treat malaria, has recently gained attention as a promising anticancer agent. Recently, studies have shown that ART can inhibit the migration and invasion of cancer cells. However, theses studies are always based on conventional two-dimensional (2D) culture models, which neglect the complex interactions between cells and the extracellular matrix (ECM) or in vivo microenvironment. To address these challenges, in this study, honeycomb-like gelatin methacryloyl (GelMA) hydrogel microspheres as a three-dimensional (3D) culture platform were introduced to mimic the native ECM microenvironment and assess the effects of ART on ovarian cancer cells. The results showed that these GelMA microspheres exhibited a uniform and highly porous structure, which supported cell adhesion, proliferation, and migration. Notably, 3D culture promoted DNA synthesis and induced G1-to-S phase transition, indicating enhanced proliferative capacity. Furthermore, ovarian cancer cells cultured in 3D exhibited stronger invasive and chemoresistant phenotypes. RNA sequencing revealed that after ART treatment, tumor-related proliferation and invasion genes of ovarian cancer cells were significantly up-regulated under 3D culture compared with 2D culture. This might be related to the up-regulation of TNF signaling pathway, NF-kappa B signaling pathway, and Pl3K-Akt signaling pathway. Correspondly, epithelial-mesenchymal transition (EMT) of ovarian cancer cells was markedly enhanced when cultured on GelMA hydrogel microspheres after ART treatment. These effects might be attributed to the altered microenvironment provided by the GelMA hydrogel microspheres, which could be responsible for the enhanced resistance of ovarian cancer cells to ART. These findings suggest that, compared to traditional 2D. These findings suggest that, compared to traditional 2D culture, the 3D extracellular matrix-based system better mimics the in vivo tumor architecture, thereby improving the sensitivity of anticancer drug screening and offering a more reliable platform for evaluating drug resistance and tumor cell heterogeneity.

A self-supervised learning based method for fish disease diagnosis utilizing extremely limited samples - Zehui Liu; Shanshan Ye; Xuanzhi Li; Xianwu Luo; Jiaji Pan; Miaolei He; Wei Qin; Jun Xiao; Yaoyi Cai; Tiantian Shen; Yu Li; Hao Feng (Computers and Electronics in Agriculture, 2026)

Photoactive and self-sustaining: How soil organic matter drives the natural remediation of Cr(VI) via photochemical pathways at the soil-water interface - Yaoning Chen; Mengwei Luo; Yuanping Li; Jun Wang; Hongjuan Jiang; Mengyang Zhao; Yaoqin Nie; Bin Zou; Qianruyu Wang; Nianping Chi (Water Research, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Zn2 +-doped and -NH2-modified TiO2-SiO2 composite for highly efficient and selective removal of Sr2+ from nuclear wastewater - Jun Liao; Ke Su; Heyu Luo; Pan Li; Nishan Zhong; Zijia Zhang; Ling Ding (Process Safety and Environmental Protection, 2026)

Waste cotton textiles-derived cellulose superhydrophobic aerogel for efficient oil-water separation - Ya-hui Li; Hui-Jiang; Xiao-quan Zhu; Ru-ru Ma; Er-min Zhou; Jun-li Luo; De-qiang Li; Hong-tao Jia; Jun Li; Lu-xiang Wang (Journal of Water Process Engineering, 2026)

Rare earth nanoparticles: Illuminating the future of precision photodynamic therapy in oncology - Han Wang; Zhiwei Li; Jun Liao; Qi Nie; Qianli Lin; Tingting Qi; Xiao Luo (Journal of Photochemistry and Photobiology B: Biology, 2026)

Indium enrichment in VMS deposits: insights from sphalerite geochemistry and thermodynamic modeling of the Tiemurt Pb-Zn-Cu deposit, NW China - Min Luo; Peng-Peng Yu; Yi Zheng; Jie-Jun Lei; Xi Chen; Yi-Han Wu; Hong-Xiang Shan; Quan-Jie Li; Zhuo-Xiong Shi (Journal of Geochemical Exploration, 2026)

Contamination severity shifts the multi-mode protective functions of edaphic phosphorus against cadmium in rice - Haiyi Chen; Xiaotong Li; Paul N. Williams; Xing Liu; Yujie Xie; Haitao Sun; Siliang Zhang; Danxing Yang; Jun Luo (Journal of Environmental Management, 2026)

Walnut oil oleogel constructed by cellulose nanofiber and walnut protein isolate: Structure, rheology characterization and complementary stabilization effect - Yubo Zhu; Bing Zhao; Jia Luo; Jienan Li; Jun Sheng; Yang Tian; Xiufen Li (Food Chemistry, 2026)

Physics-informed GRU encoder-decoder model for predicting cross-scale mechanical behavior of rock - Zhuang Wang; Cunbao Li; Bowen Liu; Jun Li; Yi Luo; Heping Xie (Computers and Geotechnics, 2026)

One-step fabrication of porous carbon via molten salt-assisted pyrolysis and evaluation of its CO2 adsorption performance - Li Zhao; Run Zhang; Ting Huang; Ding-wang Qiao; Qi Niu; Ze-jun Luo; Kai Li; Qiang Lu (Biomass and Bioenergy, 2026)

The characteristics and possible mechanisms of the anomalously high sea levels observed along the South China Coast in 2017 - Menglu Wang; Wenya Ji; Juan Li; Jun Luo; Min Zhang; Qiyan Ji (Ocean Dynamics, 2026)

Optimizing nitrogen varieties improved sustainability of rice–crayfish co-culture system - Xiaolei Gong; Yishui Luo; Yali Li; Jialu Qian; Jintao Li; Jun Hou; Xuexia Wang (Nutrient Cycling in Agroecosystems, 2026)

In situ mapping of rhizosphere processes: biochar-mediated cadmium immobilization and rhizosphere microenvironment regulation - Baoying Wang; Zhao Wei; Haitao Sun; Xing Liu; Li Zhang; Jianyu Lin; Jun Luo (Journal of Soils and Sediments, 2026)

Compatibility of three adjuvants with Cordyceps fumosorosea and their synergistic effects on controlling the diamondback moth, Plutella xylostella - Mei-Qiong Xie; Long-Jiang Wang; Yong-Qiang Han; Jin-Cui Chen; Li-Ying Cao; Shi-Chuan Luo; Fan-Fan Jiao; Shu-Jun Wei (Crop Protection, 2026)

Transcriptomic-proteomic integration reveals RNGTT as a critical host factor mediating the replication of virulent but not attenuated SADS-CoV - Zexin Chen; Yihui Huang; Mingchong Li; Ouyang Peng; Jun Luo; Yue Pan; Zhanpeng Kuang; Zhichao Xu; Yongchang Cao; Xiaona Wei; Chunyi Xue (Veterinary Microbiology, 2026)

Machine learning-driven multi-objective optimization of sustainable engineered cementitious composites: Balancing performance and CO2 reduction via municipal solid waste incineration bottom ash (MSWIBA) - Lei Cheng; Lantian Zhou; Zhonghao Li; Yulong Luo; Yundan Gui; Jun Liu (Environmental Research, 2026)

Mechanical side-deep fertilization achieves 10% nitrogen reduction with higher rice yield, nitrogen use efficiency and profitability in China - Linsheng Yang; Debao Tu; Zhong Li; Xingcheng Huang; Jun Xie; Xueyuan Sun; Ting Luo; Prakash Lakshmanan; Min Xi (European Journal of Agronomy, 2026)

Construction of 3D printed self-supporting electrode for efficient electrochemical lithium recovery from brine - Muyao He; Guiling Luo; Li Zhang; Jun Gu; Tongyu Wu; Xiaoxiao Yu; Minmeng Tang; Xiao Zhang; Yanhong Chao; Wenshuai Zhu (Chemical Engineering Journal, 2026)

A low-power and visualized varicose vein ablation surgery based on interventional optical fiber therapeutic probe - Fangzhou Jin; Yinsheng Lin; Yading Luo; Jian Han; Xu Yue; Wenwei Chen; Yongkang Zhang; Shanshan Guo; Xiaobing Niu; Jun Guo; Bai-Ou Guan; Chengzhi Li; et al. (Chemical Engineering Journal, 2026)

A high-entropy multicationic substituted Li10GeP2S12 solid electrolyte enabling stable all-solid-state batteries - Shiqiang Zhou; Mengrui Li; Wen Ren; Peike Wang; Lukuan Cheng; Wenzheng Li; Jingjing Luo; Chuanzhou Long; Suzhu Yu; Jun Wei (Chemical Engineering Journal, 2026)

Fast and Accurate Flood Inundation Dynamics Modeling and Prediction Based on Spatial Reconstruction and ConvLSTM - Shuang Zhu; Qiaolong Chen; Jun Guo; Xiangang Luo; Yi Liu; Yida Li; Hui Qin (Water Resources Management, 2026)

Immunogenic evaluation of a recombinant rabies virus expressing canine distemper virus H gene and canine parvovirus VP2 gene - Zhibin Yan; Bingjie Li; Jin Peng; Xin Li; Yiwan Wu; Xinhui Liu; Ying Chu; Shile Huang; Jun Luo; Xiaofeng Guo (The Veterinary Journal, 2026)

Abnormal lipoylation of aceF in proteobacteria induced by AgNPs during the storage of ozone-treated wastewater - Muxinjian Luo; Yuhe Wang; Qiang Sun; Heng Zhang; Jun Yuan; Weiyi Zhou; Xiyun Dong; Shihao Peng; Wenbo Cao; Hong Li; Huaili Zheng (Journal of Environmental Chemical Engineering, 2026)

Enhanced selective leaching of Ni and Co via pre-oxidizing and high-pressure acid leaching of Ni-Co-Fe powder - Jing Chen; Yuqi Zhong; Jun Luo; Xin Zhang; Mingjun Rao; Zhiwei Peng; Guanghui Li; Tao Jiang (Hydrometallurgy, 2026)

Understanding the differences in ignition and combustion characteristics between raw coal and pyrolyzed char: A combined PLIF measurement and DFT calculation - Yawei Song; Sheng Su; Qifu Lin; Longwei Chen; Chengzhou Liu; Weiye Chen; Zhenyang Li; Yiman Jiang; Dianwu Wu; Hansheng Feng; Guangnan Luo; Jun Xiang (Fuel, 2026)

Green and economical lattice-engineered CoMn2O4 spinel from spent lithium-ion batteries enables efficient mercury capture from oxy-fuel combustion flue gas - Zixuan Wang; Yang Xu; Yuyang Wang; Suhan Luo; Xianqing Zhu; Jiaxin Zhu; Deyu Hua; Ziyao Yang; Jun Li; Qingzhu Zhang (Chemical Engineering Journal, 2026)

Emerging roles of dehydrogenase/reductase (DHRS) in cancer - Jun Huang; Chenpeng Tang; Xue Chen; Pai Zeng; Hongde Li; Xiangjian Luo (Chemistry and Physics of Lipids, 2026)

Engineering Ru–Co sites for promoted hydrogen spillover in ammonia synthesis - Shengxuan Luo; Guorun Dai; Annan Hu; Jun Cheng; Yuxiang Mao; Hao Li; Zhefeng Li; Weixin Liu; Rongxin Xia (Waste Disposal & Sustainable Energy, 2026)

Correction: Establishment and Methodology Validation of Latex-Enhanced Turbidimetric Immunoassay for Dextran Determination in Sugar - Guowei Chang; Jun Liu; Bin Feng; Jun Chen; Qing Huang; Guiyun Liu; Xiuyu Luo; Zhide Li; Zengwei Huang; Dafeng Liang (Sugar Tech, 2026)

Exploring gut microbiota responses to low-dose thallium exposure via food chain transfer: insights from soil–plant–human systems - Lu-Xiu Lin; Wei-Jun Chen; Shun-Xing Li; Feng-Ying Zheng; Xu-Guang Huang; Feng-Jiao Liu; Jia-Yi Luo; Zhao-Jing Huang; Wen-Jie Zhang; You-Bin Zhuo; Xin Long (Environmental Geochemistry and Health, 2026)

Impacts of surface heterogeneity on energy partitioning in paddy ecosystems: A dual eddy covariance study - Yulong Dai; Bo Liu; Jun Wei; Yuanzhi Shi; Qilin Li; Fangping Liu; Yufeng Luo; Yuanlai Cui (Agricultural and Forest Meteorology, 2026)

Research on scientific and technological applications of spaceborne GNSS for China’s Space Station - Yifan Duan; Xinyuan Mao; Xuzhi Li; Leizheng Shu; Xiaoyu Chen; Yong Zhang; Bingxian Luo; Tingling Ren; Jun Sun; Shushi Liu; Wenbin Wang; Yang Gao (Advances in Space Research, 2026)

High-resolution electrical resistivity imaging of crust beneath Helishan mountains in Hexi Corridor, implications for basin-range coupling and hydrocarbon generation mechanism - Xian-zhong Luo; Sheng Xia; Jun-lu Wang; Yao-tian Yin; Hui Chen; Zhan Liang; Long-long Li (Applied Geophysics, 2026)

Intermittent Theta-Burst Stimulation (iTBS) Improves Motor Coordination and Modulates Neuroinflammation and Autophagy in SCA3/MJD Mice - Le-Wen Chen; Yan-Hua Lian; Xiao-Lei Dong; Kai-Liang Luo; Li-Qiong Zhan; Li-Li Xie; Qi-Kui Sun; Wei Lin; Shi-Rui Gan; Xiao-Ping Cheng; Jun Ni; Xin-Yuan Chen (The Cerebellum, 2026)

Sex-specific responses of intestinal health, microbiota composition, and transcriptome profiles in golden pompano (Trachinotus blochii) subjected to hypoxia and reoxygenation - Xiao Kun Wang; Shan Ying Han; Ze Xin Zhong; Zeng Tan Hu; Tian Xiu Li; Yue Gu; Chun Xiu Jin; Tian Jiang; Fei Biao Song; Jian Luo; Jun Long Sun (Frontiers in Marine Science, 2026)
Introduction Driven by global climate change and coastal eutrophication, severe hypoxic events have become a primary environmental stressor in marine ecosystems, posing a critical threat to commercially vital teleosts like the golden pompano ( Trachinotus blochii ). Understanding the dimorphic physiological and microbial responses between sexes under such stress is crucial for developing targeted mitigation strategies. Methods Golden pompano were subjected to hypoxia stress (3.0 ± 0.2 mg/L) for 14 days, followed by restoration of dissolved oxygen to normoxic state (7.0 ± 0.2 mg/L) and cultivation for another 14 days. Subsequently, the histology ( n = 3), digestive enzyme activity ( n = 9), microbial composition ( n = 3), and transcriptome ( n = 3) of intestinal tissue were evaluated. Results Hypoxia induces marked physiological stress and a shift toward intestinal dysbiosis across both genders, manifested by damaged intestinal integrity, oxidative stress, and an increased abundance of opportunistic pathogens (e.g., Spirochaetes ). Although reoxygenation further deteriorates the histological condition of female intestinal tissue, it also triggers more significant molecular and enzyme activity rebound effects compared to males. Moreover, females exhibit significant upregulation of lipid metabolism, antioxidant defense mechanisms, and key signaling pathways, suggesting that they may have adopted a high-energy “compensatory recovery” strategy. Correlation analyses reveal that these microbial shifts are closely linked to host metabolic regulation: beneficial bacteria ( Pseudoalteromonas and Lactococcus ) support sterol transport and signaling homeostasis, while opportunistic taxa ( Brevinema ) negatively impact lipid synthesis. Discussion Our findings reveal a distinct gender dimorphism in the hypoxia and reoxygenation response, providing a theoretical foundation for sex-specific management and nutritional interventions in golden pompano aquaculture.

Asymmetric deformation and damage mechanisms of double-block ballastless track induced by subgrade frost heave considering the shady–sunny slope effect - Binqiang Li; Jun Luo; Yanbo Bai; Jianfeng Yun; Xu Zhang; Peng Yue; Kaiyun Wang (Transportation Geotechnics, 2026)

Mechanism of GCN2/eIF2α signaling pathway in MC-LR-induced hepatocyte oxidative damage and alpha-lipoic acid intervention - Ailin Tan; Yu Huang; Hanyun Shen; Chaoyun Chen; Qingbi Zhang; Jun Bai; Liangping Luo; Xuelian Jiang; Shuai Li; Zhixia Han (Toxicon, 2026)

Inhibitory effect of pulsed electric field pretreatment on acrylamide formation in air-fried French fries and its mechanism - Jian Li; Yue-Wei Huang; Yi-Tong Li; Shi-Yin Luo; Wei-Yan Xiong; Jin-Hua Wang; Jun-Hu Cheng; Ting-Shi He; Xin-An Zeng (Food Research International, 2026)

Methionine-driven covalent chelation of Zn2+ by linusorb: a paradigm in hydrophobic cyclic peptide metal binding - Yi-kang Zhang; Du-jian Deng; Zhong-yi Luo; Wan-nan Wang; Jun-le Li; Shao-rong Zhang; Jia-li Li; Jia-zi Chen; Yong Wang; Zi-zhe Cai (Food Chemistry, 2026)

Gaδ+-H active sites-driven reverse water gas shift reaction with high CO selectivity - Zhenzhong Tao; Huaixiang Li; Dedong He; Zijun Huang; Jun Liang; Jiaming Dong; Xiaohua Cao; Yongming Luo (Chemical Engineering Journal, 2026)

Population Genomics of a Cosmopolitan Weed Provides Insights Into Its Local Adaptation and Recent Demographic History - Marilia Souza Lucas; Christoph Rosche; Isabell Hensen; Stefan G. Michalski; Dávid U. Nagy; Diana Gamba; Renske E. Onstein; Karime Abidkulova; Mohammad Al‐Gharaibeh; Ali A. Al‐Namazi; Sirwan Babaei; Fernando Bastida; et al. (Molecular Ecology, 2026)
Invasive plant species present a growing ecological and economic challenge, and often adapt rapidly to their novel environments through complex demographic and evolutionary processes. Invasion genomics offers powerful tools to disentangle these processes, but most studies rely on geographically narrow sampling across native and non‐native ranges. Erigeron canadensis is a cosmopolitan weed native to North America that has successfully invaded diverse climates worldwide. We used double‐digest restriction site‐associated DNA sequencing (ddRADseq) to investigate the genetic diversity and structure of 280 E. canadensis populations across the Northern Hemisphere. We found that native and non‐native populations maintained comparable genetic diversity. Population structure analyses revealed four genetic clusters that were mainly differentiated along latitudinal and aridity gradients. However, one cluster was strongly overrepresented in the non‐native compared to the native range. In the native range, genetic differentiation was shaped by spatial and environmental gradients, while in non‐native regions human‐mediated dispersal and repeated introductions disrupted environmentally driven genetic structure. Migration network analyses revealed limited intercontinental connectivity and a possible role of long‐distance dispersal in within‐range expansions. Genomic offset analyses showed that genotype‐environment mismatches in non‐native populations associated with reduced growth and reproduction. Together, our results indicate that the invasion dynamics of E. canadensis were driven by multiple introductions, population admixture, and lineage sorting, while some genotypes contributed disproportionately to the spread of this invader. The presence of apparent maladaptation suggests that even long‐established invaders may still be evolving in response to their novel environment, raising concerns about potential future expansions.

Drivers of Moss Functional Richness on Subtropical Coastal Islands: Area‐Driven Environmental Changes and Trait Structure Shape Distinct Pathways - Jun Yang; Guangyu Luo; Maozhen Yu; Dengxiong Yu; Wen Cai; Shuiliang Guo; Dandan Li; Jing Yu (Journal of Biogeography, 2026)
Aim Although island attributes are known to influence functional richness (FRic), the mechanisms underlying these patterns remain unclear. Specifically, whether they are driven by area thresholds (the small‐island effect, SIE) or mediated by community assembly processes remains unclear. This study aims to disentangle the relative importance of island attributes versus climatic factors in shaping moss FRic and to evaluate how environmental scaling and trait structure contribute to its regulation in subtropical coastal islands. Location Coastal islands in Zhejiang Province, East China Sea, China. Taxon Mosses (404 species). Methods We analysed moss community data and environmental variables from 180 islands, classified into 110 small islands and 70 large islands (based on a detected SIE area threshold: 10 2.038 ha). FRic was calculated from 13 moss morphological traits, and the standardised effect size of FRic (SES.FRic) was derived via null models to represent community assembly outcomes. We used variation partitioning analysis (VPA) to quantify the relative importance of island attributes versus climatic factors. In addition, piecewise structural equation models (piecewise SEMs) were grouped by both the area and SES.FRic thresholds were used to evaluate the pathways linking island attributes to FRic. Results Variation partitioning and hierarchical partitioning consistently showed that island attributes explained more variation than climatic factors. On small islands, island characteristics were the main independent contributors ( R 2 = 0.051, p = 0.018), whereas on large islands, island area became dominant ( R 2 = 0.092, p = 0.002), with climatic variables showing comparatively weaker effects. Hierarchical partitioning revealed a similar shift, with island characteristics contributing most on small islands (57.2%) and island area increasing on large islands (46.2%). SEM analyses showed that area‐based grouping primarily altered the relationships between island attributes and mediating variables, whereas SES.FRic‐based grouping mainly affected the pathways linking mediating variables to FRic. Main Conclusions The regulation of moss functional richness reflects a pathway‐level differentiation in the mechanisms underlying FRic. Environmental scaling associated with island area structures the relationships between island attributes and mediating variables, whereas trait structure determines how these mediators are translated into functional diversity outcomes. Rather than representing alternative explanations, environmental scaling and trait structure operate at different stages of the ecological pathway underlying FRic. These findings extend and refine the view that community assembly uniformly mediates environment–diversity relationships and instead highlight a stage‐specific interaction between environmental constraints and trait structure in shaping FRic.

Biosynthesis of active small molecule prenylsalidroside a and its anti-inflammatory activity - Jia-Hao Xue; Hua-Jin Yu; Long-Jun Li; Gui-Hu Lu; Pei-Shan Li; Xia Cheng; Qi Luo; Wei Wu; Zhong-Sheng Bi (Natural Product Research, 2026)

Repurposing Pentacyclic Triterpenoids as Ferroptosis Inducing Agents for Cancer Therapies - Siqi Li; Jun-Xian He; Ziyuan Zhou; Yi-Hui Luo; Jiale Zhuang; Tanziela Tanziela; Lei Gao; Wensi Tao; Nai-Kei Wong (Current Pharmacology Reports, 2026)

Integrated UHPLC-mS/mS analysis, spectrum-effect relationship, and molecular docking to study the antidiabetic components of Cyclocarya paliurus - Dan-Dan Zhang; Ming-Hua Hu; Zhen Luo; Yu-Ying Yang; Hui-Jun Li; Xin-Yao Luo; Qiong Wei; Xiao-Chuan Ye (Natural Product Research, 2026)

Antimicrobial polyketides from an endophytic fungus Arcopilus aureus HJ-7 from Ardisia mamillata Hance - Li-Qi Liang; Xian-Hua He; Chun-Yan Wei; Jing-Xian Zhao; Qian Wu; Min Liang; Jun Li; Yan Luo; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2026)

Coordinating metabolic reprogramming and exosome secretion: A dual role for SIRT1/HIF-1α under hypoxia in golden pompano - Yue Chen; Shan Ying Han; Ze Xin Zhong; Chun Xiu Jin; Geng Hui Fang; Li Xiao Zhou; Fei Biao Song; Jian Luo; Jun Long Sun (Aquaculture, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Unlocking silicate via DFT-revealed mechanisms: Synergistic Fe2+–SPC leaching for vanadium recovery in room temperature - Haoyu Li; Yuxing Zhou; Tengfei Luo; Jiayao Zuo; Can Jing; Jun Wang; Xuejun Zhu; Aiyuan Ma; Shihong Tian (Journal of Environmental Chemical Engineering, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Climate-sensitive environmental drivers shaping epipelagic and mesopelagic fauna biodiversity patterns in the Amundsen–Bellingshausen Seas, Southern Ocean - Jiayu Fan; Yang Liu; Yanping Luo; Yuru Li; Mi Duan; Chunlin Liu; Zhenjiang Ye; Jianchao Li; Peng Sun; Chi Zhang; Jun Zhao; Jianfeng He; et al. (Environmental Research, 2026)

Occurrence and distribution of phthalate esters in stormwater runoff and coastal water receiving bodies, Macao, South China - Yutang Luo; Tianyi Zhang; Yaru Cao; Qiying Jian; Aolei Du; Jun Yan; Yanjun Li; Youxiang Xu; Guoyuan Zhu; Xiong Xiong; Chenxi Wu; Kai Zhang (Environmental Pollution, 2026)

Local load-bearing stability of UHPC hollow-core bridge deck structure: Experimental and theoretical research - Jun Luo; Hongrui Guan; Min Liu; Jie Li; Mengxiao Hu; Aowei Ren; Yi Wang (Engineering Structures, 2026)

Strain-mediated solvation structure modulation governing ion selectivity in Zn(OTf)2 /PAM hydrogel electrolytes - Shuang Luo; Yanbo Wang; Xinyao Ma; Bochun Liang; Jien Li; Chunyi Zhi; Jun Fan (Chemical Engineering Journal, 2026)

Co-solvent-modulated polyamide nanofiltration membranes for high-temperature separation - Wan-Long Li; Xiao-Wei Luo; Wan-Ting Lin; Si-Yuan Zhang; Zi-Lu Zhang; Zi-Jun Zhang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2026)

Field observations reveal biomass burning and cooking as the significant sources of PM2.5-bound organic acids in Central China - Ziyue Xiang; Runqi Zhang; Sheng Li; Bin Xu; Qiongwei Zhang; Jun Wang; Datong Luo; Zhan Liu; Xinming Wang (Atmospheric Environment, 2026)

Molecular Mechanism of Phytohormones Regulating Dormancy and Germination of Barley Seeds - Jun Wu; Bing Zhou; Bo Li; Peng Wang; Ying Zhang; Liya Luo; Le Xu; Yanhao Xu (Journal of Plant Growth Regulation, 2026)

Priming Effects on Soil Organic Matter Mineralization by Carbon Substrates: A Global Meta‐Analysis - Hongxin Dong; Yingyi Fu; Shanshan Dai; Peng He; Yu Luo; Margaret A. Oliver; William R. Horwath; Lu‐Jun Li (Global Change Biology, 2026)
Priming effects (PE) on soil organic matter (SOM) mineralization depend strongly on the type of carbon substrates added. It is crucial to understand the PE induced by various carbon substrates for predicting SOM dynamics and soil‐atmosphere carbon feedback. We conducted a meta‐analysis of 8015 observations from 283 articles to evaluate how carbon substrates (plant residues, root exudates, biochar, and degradable microplastics) regulate the mineralization of SOM through PE. Results demonstrated that all these types of carbon substrates increased SOM mineralization, which induced a positive PE. Plant residues induced the highest average PE, followed by root exudates, biochar, and degradable microplastics. Compared to soils without carbon substrate inputs, the rate of SOM mineralization increased by 113% in soil with cellulose‐rich non‐woody residues, whereas it increased by only 25% in soil with lignin‐rich woody residues. The mineralization of SOM increased by organic acids (151%) was greatest in root exudates, followed by monosaccharides (60%) and polysaccharides (12%). The strong mineralization induced by organic acids was probably related to the release of more mineral nutrients by reducing soil pH. The PE on SOM mineralization by woody biochar with high aromatic carbon content (48%) was greater than that of non‐woody biochar with high alkyl carbon content (43%). Microplastics with rapidly degradable polyhydroxyalkanoates induced more SOM mineralization (258%) than polybutylene succinate (61%) and polybutylene adipate‐co‐terephthalate (21%). The SOM priming was positively correlated with soil clay and incubation moisture, and negatively correlated with soil organic carbon, total nitrogen, soil C:N ratio, dissolved organic carbon, microbial biomass carbon, carbon input rate, incubation temperature, and soil depth. These results show that the positive PE is ubiquitous in soil ecosystems; its magnitude is linked intrinsically to the physicochemical characteristics and source of exogenous carbon substrate.

Targeting the gut-liver axis with dietary polyphenols to ameliorate metabolic dysfunction-associated steatotic liver disease: advances in molecular mechanisms - Zuomin Hu; Zeyu He; Yuyan Wang; Zhongxing Chu; Yaping Zhou; Wen Li; Jun Lu; Qinlu Lin; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2026)

Mechanisms of phosphorus release from coastal sediments driven by organic matter enrichment at high nitrogen concentrations - Chun-Pu Zhao; An-Hao Wang; Ying Zeng; Wen-Hao Yin; Cheng Luo; Shi-Xia Liu; Miao Liu; Hai-Jun Wang; Xiao-Wen Li; Ji-Lin Xu; Shuo-Nan Ma (Marine Pollution Bulletin, 2026)

Mechanistic insights into sulfamethoxazole removal in activated sludge systems through machine learning and microcosm experiments - Junjie Chen; Lipin Li; Xiaowei Lv; Tao Liu; Jun Zhang; Liwen Luo; Yu Tian (Water Research, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Polyphenols-enhanced redox processes achieve remediation and humification in the co-composting of IMI-contaminated soils and agricultural wastes - Yaoning Chen; Yaoqin Nie; Zhigang Yi; Yuanping Li; Jun Wang; Hongjuan Jiang; Nan Wang; Yihang He; Mengwei Luo; Qianruyu Wang; Xing Peng (Journal of Hazardous Materials, 2026)

Nanoscale-controlled lithium ion-sieve based on MnO2·0.5H2O: Microfluidic synthesis and brine extraction performance - Xiang Li; Jiancheng Shu; Jun Luo; Shaoqin Chen; Yong Yang; Weihua Chen (Journal of Environmental Management, 2026)

Research progress in atmospheric haze chemistry: Formation mechanism of air pollution complex and control technologies - Qingxin Ma; Peng Zhang; Tianzeng Chen; Hao Li; Yonghong Wang; Jun Liu; Pengfei Liu; Yujing Mu; Jingjing Liu; Zhi Liu; Guangyan Xu; Yulong Shan; et al. (Journal of Environmental Sciences, 2026)

Magnetic properties driving nitrogen removal improvement in magnetite-enhanced activated sludge: Mechanistic insights and process validation - Jun Shi; Luo-Kai Li; Li-Han Lin; Duo-Kun Li; Jian Lu; Sali Mustafa Saleh; Tian-Yang Zhang; Huan He; Zheng-Yu Dong; Qian Xiao; Bin Xu; Chao Zeng (Environmental Research, 2026)

Water and sulfate management manipulates soil arsenic cycling at the fine scale - Yi Yang; Wen Fang; Paul N. Williams; Ke Xu; Taige Li; Zhaodong Liu; Jun Luo (Environmental Pollution, 2026)

Single-nucleus RNA sequencing reveals the underlying roadmap of early gonadal differentiation in teleost - Jialin Wang; Yajuan Huang; Zhongkai Cui; Kaili Zhang; Na Wang; Jun Luo; Yu Song; Bowen Hu; Ming Li; Yadong Chen; Manfred Schartl; Songlin Chen (Science China Life Sciences, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

Hexavalent chromium induced autophagy-dependent mTOR expression mediated by upregulation of HMGA2 - Li Li; Meng Dan; Shengnan Li; Xiaojing Cui; Shibo Bao; Shengxiang Luo; Jun Cao (Toxicology, 2026)

Highly efficient chromium removal by magnetic nitrogen containing carbon-based composite featuring cross-linking networks - Kaige Gao; Jun Li; Yang Jin; Jiang Pu; Yujing Ma; Tianliang Zhang; Houmin Luo (Journal of Water Process Engineering, 2026)

Enhanced sequential soil moisture estimation using an ensemble deep learning filter without linear-Gaussian constraints - Tuantuan Zhang; Jianxia Chang; Jiangjiang Zhang; Quanxi Shao; Ranjan Sarukkalige; Zengliang Luo; Chenglin Bi; Jun Wang; Yiming Hu; Binquan Li; Zhongmin Liang (Journal of Hydrology, 2026)

Experimental and analytical investigation on continuous two-span RC beams flexural strengthened with aluminum alloy bars - Xu Chen; Guohua Xing; Yakun Li; Jun Zhang; Da Luo; Zhaoqun Chang; Boquan Liu; Haonan Wang (Engineering Structures, 2026)

Correction to: Subsurface structure-induced water use strategies mediate shrub-herb coexistence in soil-limited hillslopes - Zidong Luo; Yunpeng Nie; Jun Zhang; Fa Wang; Wenna Liu; Daoheng Zhuang; Jiajie Li; Hu Du; Hongsong Chen (Plant and Soil, 2026)

Subsurface structure-induced water use strategies mediate shrub-herb coexistence in soil-limited hillslopes - Zidong Luo; Yunpeng Nie; Jun Zhang; Fa Wang; Wenna Liu; Daoheng Zhuang; Jiajie Li; Hu Du; Hongsong Chen (Plant and Soil, 2026)

Experimental Investigation of Porosity and Permeability of Reservoir Rock Under the Action of CO2 and Its Oil Displacement Effect - Bin Zhang; Jun Luo; Fajian Nie; Liang Wang; Xi Jiang; Wei Li; Ya Meng (Natural Resources Research, 2026)

Lecithin supplementation to HFD improves largemouth bass liver health: Implications for regulating lipid homeostasis, antioxidant responses and endoplasmic reticulum stress - Biao Wang; Hua Zheng; Juan Xiong; Hong-Jun Yang; Qing-Lin Li; Zhi Luo (Fish Physiology and Biochemistry, 2026)

Genetic origins and climate‐induced erosion in economically important Asian walnuts - Peng‐Zhen Fan; Guang‐Fu Zhu; Moses C. Wambulwa; Richard I. Milne; Zeng‐Yuan Wu; Ya‐Huang Luo; Robabeh Shahi Shavvon; Alistair S. Jump; Debabrata Maity; Lian‐Ming Gao; Hai‐Ling Qi; Hong‐Yu Wu; et al. (Conservation Biology, 2026)
The global climate is undergoing unprecedented changes, posing significant threats to species persistence. However, the spatiotemporal impacts on genetic diversity remain poorly understood, hindering species conservation and management. Walnuts, generally referred to as Juglans regia and J. sigillata , are economically vital in Asia, but little is known about their genetic origins and how the species will be affected by future climate change. Using 31 microsatellites, we genotyped 5282 individuals from 233 populations of walnuts in Asia. We assessed genetic diversity patterns and demographic history and investigated potential future genetic erosion risks. Genetic diversity of walnuts was high in the Himalaya and Hengduan Mountains. The 2 species diverged during the Pleistocene (around 1.41 Ma BP), and J. regia contained 2 genetic groups (JR1 and JR2). The JR2 group had the lowest diversity and likely arrived in northern China around 9.77 ka BP, perhaps via human transport. The Western Himalaya likely served both as a glacial refugium and the center of origin for J. regia , and the Eastern Himalaya appears to have been the refugium for J. sigillata . The 2 species appear to have hybridized in the Central Himalaya and the Sichuan basin and surroundings, forming two distinct hybrid zones. Our results indicate that genetic diversity will be reduced by up to 9.03% due to range loss under future climate change and dramatic genetic structure turnover in the Himalaya and Hengduan Mountains. In situ conservation in the Himalaya is essential for safeguarding genetic diversity and adaptive potential in Asian walnuts, while ex situ preservation of genetically unique wild germplasm, coupled with its integration into breeding programs, will enhance climate resilience. The findings advance our understanding of the origin of Asian walnuts and how future climatic change may affect their genetic diversity, offering a model for conservation and breeding strategies in other tree species facing similar threats.

Design, synthesis and cytotoxic activity of sulfonylated derivatives of camptothecin - Xiong-Fei Luo; Zhi-Jun Zhang; Zi-Long Song; Zhi-Ping Wang; Jia-Xuan Yan; Xiao-Fei Liu; Li-Zeng Peng; Cheng-Jie Yang; Ying-Qian Liu (Natural Product Research, 2026)

A new isoprenyl-phenol-type meroterpenoid from mangrove endophytic fungus Aspergillus sp. GXNU-Y65 - Fan-Fan Wang; Guo-Bao Huang; Cai-Hong Lu; Li-Jun Chen; Hui-Zhen Chen; Meng-Qin Luo; Ping-Fang Tao; Ming-Xiong Tan; Feng Qin (Natural Product Research, 2026)

Pooled data from phase 3 clinical trials comparing the clinical activity of ceftolozane/tazobactam versus meropenem for the treatment of complicated intra-abdominal infections - Zhiqiang Li; Yue Kang; Hongqiang Gao; Yingpeng Zhao; Ding Luo; Dongdong Wang; Xiang Zhang; Jieqi Yu; Guang Chu; Jun Cao; Fan Wang; Xiongqi Zhao; et al. (Infectious Diseases, 2026)

Molecular mechanisms of cold stress-induced energy stress, cholesterol metabolic disorders, and apoptosis in Pangasianodon hypophthalmus - Dongjie Wang; Min Li; Min Liao; Yao Tian; Qing Wu; Shaolin Xie; Wei Luo; Jixing Zou; Jun Shi; Zongjun Du (Aquaculture, 2026)

Comparison of different flocculants for the synergistic enhancement of activated sludge dewatering under low-temperature and acidic conditions - Dongqin He; Yaojia Zhang; Shengwen Zheng; Qianya Zhang; Mingkai Sun; Tingting Zhu; Hongwei Luo; Jun Li (Journal of Water Process Engineering, 2026)

Sulfite exporter SsTauE enhances bacterial feather degradation by maintaining sulfur homeostasis - Lei Wu; Ming-Shu Zhang; Zhen-Dong Yang; Zhi-Wei Li; Jun-Jin Deng; Xiao-Chun Luo (International Biodeterioration & Biodegradation, 2026)

Efficient fermentation of di-rhamnolipids-rich products by P. aeruginosa using ethanol as solely carbon source - Xingyu Liu; Li Luo; Mengqian Zhao; Deyu Zhang; Bo Chen; Jun Liu; Xuwei Long (Food and Bioproducts Processing, 2026)

The role of DOM on the allocation of PFASs between water and sediment within a river system - Yuchu Xie; Longfei Jiang; Weiping Mei; Jiao Tang; Jun Li; Chunling Luo (Environmental Pollution, 2026)

Engineering and immobilization of imine reductase enable chemoenzymatic synthesis of SLC6A19 inhibitor JNT-517 - Meng Ren; Ling Zhang; Jie Song; Wenxiang Chen; Li Zhang; Daohong Liao; Shu-Shan Gao; Hongde An; Bo Xie; Du-Qiang Luo; Jun Zhang (Bioresource Technology, 2026)

Spatial variation of rainfall for landslide early warning: an examination from Majiajing watershed in Yunnan, China - Jing-Kun Bao; Kun Wang; Chuan-Bing Zhu; Ze Li; Ze-Min Xu; Yun-Fei Zhang; Lin Tian; Yang Yang; Jun-Yao Luo; Tai-Qiang Yang (Natural Hazards, 2026)

Study on the Bioavailability of Arsenic in the Rice–Crayfish Farming System - Kelei Zhang; Shoudong Zhang; Longjun Deng; Tiancai Li; Li Liu; Wei Luo; Yibo Zhang; Yongyao Guo; Dan Liu; Shiyong Yang; Jun Wang; Dongjie Wang; et al. (Fishes, 2025)
Rice–fishery integrated farming has expanded rapidly in China, yet its implications for arsenic (As) accumulation remain insufficiently understood. This study evaluated As bioavailability and enrichment in a rice–crayfish farming system (RCFS) by establishing controlled field plots with soil As concentrations ranging from 5 to 40 mg/kg under three water-management regimes: alternating wetting and drying (AWD), continuously flooded (CF), and RCFS. Soil–water physicochemical variables and As accumulation in both rice organs and crayfish tissues were systematically analyzed, followed by human health risk assessment. Inorganic As in brown rice increased linearly with soil As, following Y = 0.0117X + 0.0598 (R2 = 0.96), and the estimated soil safety thresholds were 26.48 mg/kg for AWD, 11.98 mg/kg for RCFS, and 9.24 mg/kg for CF. AWD consistently exhibited the lowest As risk due to its ability to elevate soil Eh and maintain a more favorable pH, thereby suppressing As mobilization. Compared with CF, RCFS reduced As bioavailability through crayfish-induced bioturbation, which increased Eh, enhanced SOM and CEC, and improved soil aeration. As accumulation in crayfish tissues also rose with soil As, with abdominal muscle As fitting Y = 0.0085X + 0.0553 (R2 = 0.8588). Although abdominal muscle met safety limits, the hepatopancreas accumulated substantially higher As and exceeded carcinogenic risk thresholds, even at 5 mg/kg of soil As, indicating a potential health concern for consumers. This work elucidates As dynamics and enrichment mechanisms in RCFS, providing guidance for safer rice–crayfish production in As-impacted areas.

Knowledge discovery and performance-energy optimization in heterogeneous catalytic ozonation via adaptive multi-task learning - Wei Zhuang; Qianqian Luo; Qingyang Jiang; Songhang Du; Xinwei Li; Jun Ma; Xiao Zhao; Minghao Sui (Water Research, 2025)

Numerical investigation and analysis of environmental effects on water–ground transition of amphibious unmanned vehicles - Mingyang Liu; Xueping Li; Jun Luo; Jinglei Zhao; Shujin Yuan; Huayan Pu (Ocean Engineering, 2025)

Multi-objective optimal allocation and spatial distribution of water and land resources in Yellow River Basin irrigated farmland: A government-farmer duality perspective - Zepeng Zhang; Jun Zhang; Qingyu Guan; Haiping Luo; Yunfan Sun; Haichao Liu; Xiaohan Li (Journal of Hydrology, 2025)

Perinatal maternal lead exposure induces intergenerational neurotoxicity via mitochondrial dysfunction and mediation by perturbation of thyroid function - Lin Zhang; An-Xin Lu; Ling Li; Qian Wei; Yin Lin; Jun-Xia Liu; Li Ma; Ren-Tong Chen; Bin Luo; Chong-Huai Yan (Journal of Hazardous Materials, 2025)

Low-temperature soda-ash roasting of ludwigite ore: Scale-up feasibility for magnetite and borax production - Jinxiang You; Xin Zhang; Mingjun Rao; Jun Luo; Zhiwei Peng; Guanghui Li (Journal of Environmental Chemical Engineering, 2025)

Machine learning intelligently selects feature values to construct a sensor array based on tri-functional Mn-doped covalent organic polymer nanozymes for identifying flavonoid compounds - Guo-Qi Zhang; Wen-Cai Jiang; Xiao-Mei Li; Ren-Jie Li; Yi Feng; Ri-Ge Li Nai; Hui-Lin Cheng; Zhi-Bo Hou; Xiao-Jun Luo; Yan Zhao (Food Chemistry, 2025)

How hydrophobic deep eutectic solvents as liquid-liquid extractants remove Pb2+ from wastewater: Material properties, extraction behavior, and molecular-level mechanism simulation? - Jie Qian; Ying-hua Li; Di Luo; Fei Su; Si-nan Liu; Jun-xiang Wang; Wan-qi Li (Environmental Research, 2025)

Floc-granule microbial symbiosis drives DNRA in anammox bacteria via cross-feeding for complete autotrophic nitrogen removal - Yulong Yang; Wen-Bo Nie; Xin Tan; Lili Li; Chenhui Yu; Shibo Fu; Ke-Di Peng; Yi Luo; Xiao Ran; Zhihong Zheng; Jin Xu; Jun Li; et al. (Chemical Engineering Journal, 2025)

Homogeneous MgF2-engineered Na surface architecture enabling uniform ion deposition in ultra-stable sodium metal batteries - Xueming Su; Junjie Fu; Lin Luo; Xiaoquan Yang; Yue Li; Weijiang Hu; Qing Li; Qingye Li; Chencheng Sun; Jun Yang; Hongwei Gu (Chemical Engineering Journal, 2025)

A new norlignan and other compounds from Artemisia frigida Willd - Xin-Ya Dong; Ru-Ya Li; Hong-Xia Tang; Ya-Jie Li; Jun Chen; Jin-Guo Luo; Na Yu; Xiang-Wei Xu; Xu-Dong Zhou (Biochemical Systematics and Ecology, 2025)

Establishment and Methodology Validation of Latex-Enhanced Turbidimetric Immunoassay for Dextran Determination in Sugar - Guowei Chang; Jun Liu; Bin Feng; Jun Chen; Qing Huang; Guiyun Liu; Xiuyu Luo; Zhide Li; Zengwei Huang; Dafeng Liang (Sugar Tech, 2025)

Regulation of vascular smooth muscle cells phenotype by metformin up-regulated miR-1/ CCND1 axis via targeting AMPK/TGF-β signaling pathway - Yulin Luo; Mengting Li; Jingcan You; Jun Jiang; Min Zeng; Mao Luo (Molecular Biology Reports, 2025)

Comparative chloroplast genomic analysis: uncovering variations and phylogenetic relationships in tea plants from Shaoyang, Hunan Province, China - Jin Li; Yu Qin; Jun Tang; Xiao-Yan Qiu; Chang-Qing Xie; Han Tang; Ai-Ming Tang; Xiao Chen; Jun-Ping Xie; Hua Luo (Genetic Resources and Crop Evolution, 2025)

Correction to: Integrative single-cell and bulk RNA-seq analysis identifies lactylation-related signature in osteosarcoma - Zhou Xie; Xiao Qu; Jun Zhang; Yanran Huang; Runhan Zhao; Dagang Tang; Ningdao Li; Zhule Wang; Xiaoji Luo (Functional & Integrative Genomics, 2025)

Integrative single-cell and bulk RNA-seq analysis identifies lactylation-related signature in osteosarcoma - Zhou Xie; Xiao Qu; Jun Zhang; Yanran Huang; Zhao Runhan; Dagang Tang; Ningdao Li; Zhule Wang; Xiaoji Luo (Functional & Integrative Genomics, 2025)

Transcriptomic profiling reveals mechanism, therapeutic potential, and prognostic value of cancer stemness characteristic in nasopharyngeal carcinoma - Jin-Wei Chen; Run-Nan Shen; Jiang-Quan Zhu; Ying-Hang Wang; Liang-Min Fu; Yu-Hang Chen; Jia-Zheng Cao; Jin-Huan Wei; Jun-Hang Luo; Jia-Ying Li; Cheng-Peng Gui (Functional & Integrative Genomics, 2025)

Precise implementation of the Goldstein current model for self-powered neutron detectors and comparative analysis of its approximate approaches - Jun Chen; Shijie Luo; Tingyu Wu; Li Cai; Haoliang Lu; Bite Qiu; Shiyu Liu; Qingmin Zhang (Annals of Nuclear Energy, 2025)

Myocardial ischemia/reperfusion-induced glycolysis enhances damage through TRPM7 histone lactylation - Shan Hu; Guiqing Liu; Haiyan Xiang; Jun Shao; Wanqi Lan; Chao Luo; Yonggang Shi; Wu Liu; Congcong Li; Yanhua Tang; Juesheng Yang (Toxicology and Applied Pharmacology, 2025)

Activation of the cGAS-STING pathway in monocytes exacerbates pulmonary fibrosis induced by paraquat poisoning - Yangyang Sun; Zheming Yuan; Weidong Li; Xueyang Lin; Chen Yang; Yufeng Yang; Hui Miao; Shengran Wang; Ziqi Cui; Zhenghao Bao; Simin Lang; Weiqiang Sun; et al. (Toxicology and Applied Pharmacology, 2025)

Hydrodynamics knowledge-driven path planning for safety-constrained energy-saving in amphibious unmanned ground vehicles - Jun Luo; Jing Huang; Huayan Pu; Fanglong Wang; Qingfeng Li; Gang Wang; Mingyang Liu (Ocean Engineering, 2025)

Solvent extraction behavior and mechanism of Sc(Ⅲ) and Fe(Ⅲ) in sulfuric acid medium with fluoride ions using D2EHPA - Hao Jiang; Jiaojiao Liu; Yanhong Wang; Jun Luo; Changan Liu; Wei Hu; Suoyuan Dong; Hang Zhan; Guanghui Li (Minerals Engineering, 2025)

Cumulative effect of PM2.5 chemical components surpasses PM2.5 mass on hypertension in older adults: A China-based national analysis - Chen Chen; Binbin Su; Yunhe Wang; Yihao Zhao; Yutong Wu; Jun Li; Yanan Luo; Xiaoying Zheng (Journal of Environmental Sciences, 2025)

A honeycomb-rod-like hierarchical MoO3@MoS2@ZnIn2S4 p-n heterojunction composite photocatalyst for efficient solar hydrogen production - Xiaoming Liu; Wang Gong; Zihui Yan; Along Gao; Yang Li; Yan Luo; Boxiao Zhao; Jun Lin (Fuel, 2025)

Characterization of pivotal metabolites influencing the production of milk components in dairy goats - Mengke Ni; Xinran Luo; Yifan Li; Wenbo Zhang; Xiaochen Qin; Ping Wang; Huaiping Shi; Jun Luo; Cong Li (Food Chemistry, 2025)

Anti-glycation research: using anti-oxidative as indicators, screen the most promising Dendrobium from different habitats and growing environment - Huan Luo; Meng-Yao Jin; Yang-Fan Hu; Nan Yao; Zhi-Jun Zhang; He Li; Tian-Yu Hou (Food Bioscience, 2025)

Beyond mass concentration: The critical role of chemical and biological compositions and sources in PM2.5-induced toxicity in two Chinese megacities - Yihua Wang; Jiawen Xie; Ling Jin; Xiaohao Sun; Lu Zhang; Qian Yang; Xiaosan Luo; Jun Li; Xiangdong Li (Environmental Pollution, 2025)

Suppression mechanism of methane–coal dust hybrid explosions by Mg(OH)2/NH4H2PO4 composite powders: Coupled analysis of flame propagation dynamics and radical emission spectra - Qiuhong Wang; Di Wu; Jun Deng; Zhenmin Luo; Bin Peng; Jian Chen; Fuxin Chen; Guoqiang Dong; Qiulin Li; Zezhou Song (Chemical Engineering Journal, 2025)

Inflammation-responsive biomimetic nanoparticles for targeted acute pancreatitis therapy - Lu Liu; Shujun Chen; Jie Zhong; Yiping Zhu; Tiantian Luo; Yu Pu; Xiaoming Zhang; Jun Deng; Xinghui Li (Chemical Engineering Journal, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Mucus cell-inspired microstructure lubricative gel surface: Secretory, trap-locked and dual antithrombotic - Jun Zhong; Qing Yang; Xiaodan Gou; Mengchen Xu; Qingyun Ma; Lin Kai; Haoyu Li; Mingyong Luo; Feng Chen (Chemical Engineering Journal, 2025)

Engineered bacterial outer membrane vesicles regulate the polarization of tumor-associated neutrophils to enhance tumor immunotherapy - Cheng Song; Puze Li; Meichan Wu; Hai Yang; Xuan Zhu; Changyan Wang; Xue Chen; Yi Xiao; Xuyu Li; Dongdong Wang; Yuan Zhao; Chongyi Wang; et al. (Chemical Engineering Journal, 2025)

Enhanced arsenite removal in water using multifunctional UiO-66-NH2 embedded chitosan biocomposite beads: defects, oxidation and adsorption - Yuxin Li; Zhimin Wang; Yuanfeng Wei; Ting Wang; Maosong Zhao; Jie Luo; Jun Zhou; Zhaoshuang Li; Kai Yin; Chengbin Liu (Chemical Engineering Journal, 2025)

Livestock manure-based organic fertilization facilitates the transmission of antibiotic resistance genes across the soil-onion continuum: A significant contribution from root exudates - Zixuan Zhao; Bin Luo; Tao Cao; Tongtong Bai; Yifan Sun; Hengrui Liu; Li Zhang; Jun Xie; Jun Wang; Huakang Li; Zichen Duan; Zixuan Gao; et al. (Soil Biology and Biochemistry, 2025)

Dismembered Guadalupian (Middle Permian) seamounts within the Yarlung-Tsangpo Suture Zone: Implications for the opening time of the Neo-Tethys Ocean - Hong-fu Zhou; Yi-chun Zhang; Mao Luo; Xin Li; Hua Zhang; Hai-peng Xu; Ruo-lan Liao; Qi Ju; Xiao-Hui Cui; Jun-jie Liu; Yao-feng Cai; Shu-zhong Shen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Multidimensional characterization of microplastic pollution in subtropical urban soils: Combining geospatial analysis and polymer risk indexing - Aolei Du; Yanjun Li; Qiying Jian; Kai Zhang; Yutang Luo; Jun Yan; Peixin Du; Deborah M. Power; Ying Li; Yibing Ma (Journal of Hazardous Materials, 2025)

Mechanistic insights into Perfluorooctanoic acid (PFOA) and Perfluorooctane sulfonates (PFOS)-induced nitrification acceleration: Interkingdom collaboration of AOA-comammox in calcareous soils - Shuoshuo Wu; Keyi Zhang; Yuehang Zhu; Luo Zhang; Wangying Ding; Jun Li; Baowei Hu; Guixin Chu; Rui Tao (Journal of Hazardous Materials, 2025)

From stainless steel to batteries: industrial-scale closed-loop hydrometallurgical integration for ferronickel-to-precursor conversion - Jun Luo; Pengfei Yang; Jing Chen; Yanhu Chen; Mingjun Rao; Guanghui Li; Tao Jiang (Journal of Cleaner Production, 2025)

Enhanced sludge dewatering by low-temperature heat treatment with polyacrylamide under near-neutral conditions: Focusing on microbial community and antibiotic resistance genes - Dongqin He; Tingting Zhu; Mingkai Sun; Bo Bao; Pan Heng; Hongwei Luo; Jun Li (Journal of Environmental Chemical Engineering, 2025)

Tailoring aluminosilicate reactivity in red mud via sodium-activated carbothermic reduction for hydrothermal extraction applications - Jiajian Liu; Jun Luo; Hongzhuang Dong; Lingyun Yi; Guanghui Li (Journal of Environmental Chemical Engineering, 2025)

Synergistic regulatory mechanisms of plant hormone combinations on the growth and lipid accumulation of Chlorella pyrenoidosa in saline wastewater - Qiao-Ling Zhao; Kai-Yuan Li; Jia-Qi Xi; Jin-Long Zhou; Dan-Ni Miao; Zeng-Ling Ma; Ying Zhang; Hai-Jun Luo; Feng Gao (Journal of Environmental Chemical Engineering, 2025)

Identifying gelatin source by mass spectrometry: A review - Xiao-Mei Sha; Le-Ying Yang; Hui Wang; Jie Cheng; Hao-Sheng Luo; Li-Jun Zhang; Zi-Zi Hu; Zong-Cai Tu (Food Chemistry, 2025)

Highly efficient and sustainable bioconversion of cottonseed meal to high-value products through solid-state fermentation by protease-enhanced Streptomyces sp. SCUT-3 - Zhen-Jie Dai; Ming-Shu Zhang; Zhi-Wei Li; De-Lin Lu; Lei Wu; Can Qin; Hai-Ning Wang; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Synergy among multiple electron donors in electro-fermentation chain elongation: Accelerated directional electron transfer and enhanced microbial functions - Dengfei Li; Aijuan Zhou; Jun Mei; Zhihong Liu; Haoran Duan; Jingyang Luo; Zhangwei He; Wenzong Liu; Bing-Jie Ni; Xiuping Yue (Bioresource Technology, 2025)

Compound Inhibitors Mitigate Skin Ulceration Induced by UVA and Vibrio splendidus in the Sea Cucumber Apostichopus japonicus - Xiaonan Li; Ye Tian; Haoran Xiao; Fenglin Tian; Lingshu Han; Chong Zhao; Luo Wang; Jun Ding (Fishes, 2025)
The sea cucumber (Apostichopus japonicus) is highly susceptible to environmental stress during aquaculture, storage, and transportation, often resulting in autolysis and considerable economic losses. UVA irradiation and Vibrio splendidus infection were used to induce skin ulceration in A. japonicus. In this study, UVA irradiation and V. splendidus infection were used to induce skin ulceration, and the effectiveness of a compound inhibitor in delaying its onset was evaluated. The degree of skin ulceration in A. japonicus was evaluated. Body wall tissues were collected to measure the activities of self-digesting enzymes, AchE, cathepsin L, SOD, and CAT. Caspase-3 expression was also analyzed to assess apoptosis and tissue damage. The results indicated that soaking A. japonicus in the inhibitor composition significantly delayed the onset of skin ulceration. After 72 h of UVA irradiation, the skin ulceration in group Eg was 0.55%, which was significantly lower than that in groups Cg and Wg. In the V. splendidus infection model, group Eg showed a 4-day delay in the onset of skin ulceration, compared to group Cg. Enzyme activity and gene expression analysis revealed that the inhibitor composition significantly reduced self-digesting enzyme expression in the A. japonicus body wall, increased SOD and CAT activities, and inhibited Caspase-3 expression. This study provides valuable theoretical insights into controlling skin ulceration in A. japonicus during aquaculture, preservation, and transportation.

Telaprevir attenuates caspase-11-dependent pyroptosis in mouse heart following ischemia/reperfusion via inhibition of MALT1/TRAF6 pathway - Ming-Rui Li; Bi-Feng Yao; Can Tang; Xiu-Ju Luo; Jun Peng (Toxicology and Applied Pharmacology, 2025)

Altererythrobacter guangdongensis sp. nov. and Tsuneonella sediminis sp. nov., two novel carotenoid-producing species isolated from tidal flat sediment - Huan-Huan He; Ying Wang; Bing-Yu Li; Chun-Yan Lu; Shuai Li; Zhuo-Huan Zheng; Liang Zhang; Wen-Hui Lian; Xin-Tao Luo; Hai-Wei Lin; Lei Dong; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

Assessing the methane mitigation potential of biochar and stover incorporation: Insights from the emission dynamics and soil microbiome in maize agroecosystems - Xu Yang; Jun Yuan; Yinghui Bi; Lidan Wang; Junqi Zhang; Chaoqun Wei; Xin Cui; Han Li; Peiyu Luo; Jun Meng; Wenfu Chen (Soil and Tillage Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Exploring the biocontrol performance of Bacillus velezensis against postharvest diseases of eggplants and the underlying action mechanisms in soft rot management - Xiaoyun Zhang; Junyi Wang; Yu Xin; Esa Abiso Godana; Solairaj Dhanasekaran; Ruijie Luo; Jun Li; Lina Zhao; Hongyin Zhang (Postharvest Biology and Technology, 2025)

Discovery of undescribed schinortriterpenoids from Schisandra chinensis by molecular networking and their neuroprotective effects - Peng Jiang; Yu-Meng Luo; Xin-Yuan Li; Shu-Jun Zhang; Wei Guan; Anam-Naseem; Yu-Hang Fan; Qing-Shan Chen; Li-Li Zhang; Hong-Yan Yao; Xiao-Xue He; Hai-Xue Kuang; et al. (Phytochemistry, 2025)

The relationship between physical property evolution and reservoir formation in volcanic rock reservoirs: The Huoshiling Formation, Dehui Fault Depression, southern Songliao Basin - Liang Liu; Jijun Li; Tianhong Yang; Libin Song; Kexin Jia; Lili Li; Weiwei Qu; Jun Jiang; Shikai Ni; Chenghong Luo (Marine and Petroleum Geology, 2025)

Mechanisms of groundwater recovery and land subsidence mitigation in a piedmont plain - Long Zhao; Xiao-Wei Jiang; Yu-Mei Li; Yong Luo; Kun-Chao Lei; Wen-Jie Kou; Fang Tian; Miao-Zhuang Tian; Te Sha; Shu-Fang Wang; Wen-Jun Cui (Journal of Hydrology, 2025)

Innovative application of recyclable magnetic LDO beads for enhancing the remediation of Cd and Pb contamination and the humification during composting - Hongjuan Jiang; Zhigang Yi; Yaoning Chen; Yuanping Li; Mengyang Zhao; Jun Wang; Yihuan Liu; Xuyang Jia; Mengwei Luo; Yaoqin Nie; Nianping Chi (Journal of Hazardous Materials, 2025)

Effects of hyperthermophilic composting on antibiotic resistance and environmental health risk of antibiotic treated cow manure - Ting Hu; Wen Song; Guangdong Wang; Xinyue Zhang; Dan Li; Lu An; Bin Luo; Jun Wang; Xun Qian; Jie Gu (Journal of Hazardous Materials, 2025)

Identification of a Streptomyces sp. SCUT-3 aminopeptidase SsLap1 and its synergistic with endopeptidase Sep39 for peanut meal hydrolysis - Hua-Hong Cai; Ming-Shu Zhang; Lei Wu; Zhi-Wei Li; Can Qin; Chu-Yan Liang; Jun-Jin Deng; Xiao-Chun Luo (Food Bioscience, 2025)

Rubbing resistant and rapid response multifunctional sweat sensor based on core-sheath structure yarns - Dan Luo; Lu Liu; Yuefeng Liu; Jun Li; Zhijie Li; Haibo Sun; Pengfei Peng; Yue Qiu; Yong Liu; Hao Liu (Chemical Engineering Journal, 2025)

An approach and mechanistic insights of coating-type binders for 4.6 V-LiCoO2 cathode of lithium-ion battery - Li Deng; Yu-Xi Luo; Zhen Wang; Jin-Xia Lin; Jun-Ke Liu; Kun-Gui Zheng; Gao-Yang Bai; Zu-Wei Yin; Yao Zhou; Jun-Tao Li (Chemical Engineering Journal, 2025)

Properties of rich-Nae effect and reversible oxygen redox with a complete solid-solution sodium-storage behavior - Wei Zhao; Shao-Hua Luo; Yicheng Lin; Guodong Hao; Rui Huang; Pengyu Li; Ge Wang; Jun Cong; Shengxun Yan; Lixiong Qian (Chemical Engineering Journal, 2025)

Flow paths control on spatiotemporal weathering dynamics in high-relief regions, eastern Qinghai-Tibet Plateau: Insight from dissolved Li-Sr-O isotopes - Tingting Ma; Jun Zhong; Si-Liang Li; Sen Xu; Han Luo; Cong-Qiang Liu (Chemical Geology, 2025)

Mushroom residue extract-based media enhanced the enrichment and isolation of cellulose-degrading bacteria - Xiaoli Luo; Tianshu Wang; Yili Meng; Li Li; Shuihong Yao; Huawei Wu; Jun Li (Bioresource Technology Reports, 2025)

Successful in situ 5-aminolevulinic acid photodynamic therapy in a 53-year-old female with cutaneous squamous cell carcinoma - Limin Luo; Xiaoling Jiang; Jianjun Qiao; Hong Fang; Jun Li (Journal of Zhejiang University-SCIENCE B, 2025)

Drought impact on water-induced erosion: spatiotemporal pattern in typical areas of the southern Tibetan Plateau - Siwen Yu; Wen He; Baofeng Di; Wen Zeng; Jun Luo; Menglai Zhan; Yu Qiao; Pingfeng Li (Journal of Mountain Science, 2025)

Strength characteristics of metakaolin and cement stabilized dredged clay at high water content - Zhicheng Wang; Jun Liu; Fei Guo; Ying Chen; Fuheng Luo; Lei Xiao; Mingdong Li (European Journal of Environmental and Civil Engineering, 2025)

Hotspot regions of reactive oxygen species production and their environmental impacts in periodically flooded soil environments: A review - Xing Liu; Yvjie Xie; Paul N. Williams; Baoying Wang; Haiyi Chen; Xiaotong Li; Li Zhang; Leyi Wang; Junjun Liu; Yingxin Wu; Jun Luo (Critical Reviews in Environmental Science and Technology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Evolutionary dynamics and codon bias analysis of canine circovirus: Insights into global spread and host adaptability - Gen Li; Rongqi Liu; Yongyi Chen; Huixian Liang; Yinyi Liang; Xin Li; Yankun Ke; Bowen Lin; Jianfeng Zhong; Xiaofeng Guo; Jun Che; Jun Luo (Molecular Phylogenetics and Evolution, 2025)

Molecularly engineered visible-light-driven dithienylethenes: near quantitative photocyclization yield, polymorphic control and reconfigurable 3D-printed devices - Qing Yan; Jiaxian Lu; Zhifeng Ma; Miao Luo; Chengpeng Li; Sheng Wang; Jun Ren (Chemical Engineering Journal, 2025)

Design and construction of Ti-incorporated Fe3O4/C/MXene composite with high-performance anodes for lithium-ion batteries - Renhuan Luo; Wang Li; Zhanhua Yang; Guowang Wei; Qiankun Wei; Jun Chen; Jianqiu Deng; M.-Sadeeq Balogun; Wenbin Jiang; Zhongmin Wang; Weijiang Gan (Chemical Engineering Journal, 2025)

Interfacial engineering electron-rich Cuδ−-Ov-Zn oxygen vacancy via Mn Cu alloy in LDH structure for selective CO2 conversion to methanol - Zhefeng Li; Wentao Du; Zhuo Chen; Yongbin Zhong; Tongyun Zhang; Jingwen Xu; Yuanfa Zhuang; Weixin Liu; Hao Li; Shengxuan Luo; Jun Cheng (Chemical Engineering Journal, 2025)

Improving electrochemical performance of silicon-carbon anode for lithium-ion batteries via one-step etching - Huai-Min Wang; Ying Zhou; Bi-Rong Luo; De-Jun Li; Bo Zhang (Chemical Engineering Journal, 2025)

Flavobacterium aestuarii sp. nov., a novel species isolated from the Pearl River Estuary - Qi Li; Zi-Qi Peng; Hong-Chuan Wang; Lei Dong; Dan-Yuan Guo; Pan-Deng Wang; Xiao-Qing Luo; Zhen-Hao Luo; Zi-Wen Yang; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

A Dual-Functional NIR Fluorescent Probe for Detection SO2 Derivatives and Colorimetric Sensing pH as well as its Applications in Food Monitoring and Hepatoma Cells Imaging - Yu Zhu Yang; Lei Ao; Xiao Ping Mao; Gui Yong Li; Xiao Ye Luo; Huan Li Liu; Nan Jun Huang (Journal of Fluorescence, 2025)

Resolving the Snowball Earth conundrum: the role of marine dissolved organic carbon pool - Bing Shen; Xianguo Lang; Ruimin Wang; Yonggang Liu; Shihong Zhang; Tianzheng Huang; Xuelei Chu; Yixin Cui; Weiming Ding; Yuansheng Du; Ran He; Kangjun Huang; et al. (Science Bulletin, 2025)

Virus-host interactions and their effects on the prokaryotic community in thermokarst lakes - Yutong Song; Guibiao Yang; Pandeng Wang; Xiaoqing Luo; Jian-Yu Jiao; Zhihu Zheng; Luyao Kang; Dianye Zhang; Ziliang Li; Wei Zhou; Xuning Liu; Lili Han; et al. (Science Bulletin, 2025)

Developing composite biocontrol agents based on microbiome dynamics during postharvest storage of tomatoes - Lu Zhuang; Xiaoyun Zhang; Solairaj Dhanasekaran; Esa Abiso Godana; Jun Li; Ruijie Luo; Lina Zhao; Yu Li; Xiaoyong Liu; Hongyin Zhang (Postharvest Biology and Technology, 2025)

Neuroprotective lindenane sesquiterpenoids from the roots of Lindera aggregata (Sims) Kosterm - Lie-Feng Ma; Shan-Rong Luo; Qian-Qing Liu; Rui-Si Tang; Ning-Yu Chen; Di Luo; Lu Guo; Jia Li; Rui Wu; Zha-Jun Zhan (Phytochemistry, 2025)

Silver nanoparticles alter plankton-mediated carbon cycle processes in freshwater mesocosms - Peng Wang; Qianqian Xiang; Zihao Fu; Chengjing Li; Haochen Yang; Jun Zhang; Xia Luo; Liqiang Chen (Journal of Hazardous Materials, 2025)

Dual signal output detection of acetamiprid residues in medicine and food homology products via nanopore biosensor - Yao Li; Jiyuan Tu; Hong Wang; Kexin Luo; Pingping Xiao; Tangbin Liao; Guo-Jun Zhang; Zhongyue Sun (Food Chemistry, 2025)

Regulating brønsted/lewis sites of facet-dependent cryptomelane-type MnO2 for simultaneously enhancing performance and N2 selectivity in NOx selective catalytic reduction with NH3 - Changye Mang; Jun Luo; Xiduan Yang; Mingjun Rao; Guipeng Yu; Guanghui Li; Tao Jiang (Chemical Engineering Journal, 2025)

Multifunctional amine salt additive for enhancing the performance of perovskite and perovskite/silicon tandem solar cells - Jun Qu; Wenfeng Zhang; Yangdi Chen; Huiyao Zhao; Yanbei Wei; Rui Zhou; Hongjie Wan; Jie Deng; Dongyong Fan; Yuchen Luo; Haijin Li (Chemical Engineering Journal, 2025)

Where is the effective control range of exhaust hoods? Airflow suction envelope determination and its performance evaluation - Mingyao Ma; Xiawei Luo; Yukun Xu; Bin Li; Jiahua Wang; Jingjing Pei; Jun Gao (Building and Environment, 2025)

Mechanism study of the effects of astragaloside IV and quercetin on idiopathic pulmonary fibrosis - Ye Luo; Chang-jun Xu; Xing-hui Ai; Yu-ping Li; Xing Zhu; Chang-fu Yang (Journal of Natural Medicines, 2025)

Tiered ecological risk assessment of perfluoroalkyl acid mixtures based on relative potency factor and species sensitivity distribution - Jianming Jiang; Xun Wang; Xi-Long Zhang; Hui Liu; Wen-Jun Hong; Minjie Li; Liang-Hong Guo; Cheng Ye; Hai-Wei Luo (Environmental Geochemistry and Health, 2025)

Functional identification of mango MiEXPLA1a2 and MiEXPA4e1 genes in transgenic Arabidopsis and tomato - Xiang-juan Zhang; Ji-hong Yang; Jia-jun Li; Hui-jun Yang; Ming-qing Li; Yue-xing Zhang; Cong Luo; Xin-hua He (Plant Science, 2025)

Impact on nonlinear runoff of LID facilities and parameter response in the TVGM model - Pengjun Li; Luwen Zhuang; Kairong Lin; Dunxian She; Qiang Wang; Wei Luo; Jianliang He; Jun Xia (Journal of Hydrology, 2025)

Physiological responses and adaptive mechanisms of the harmful algal bloom species Heterosigma akashiwo to naphthalene exposure - Dan Huang; Hao-Yun Zhang; Hua-Jun Wang; Hong-Jia Huang; Shuang Liu; Chu-Yi Qiu; Cai-Qin Cheng; Yun Huang; Zhaohe Luo; Wei-Dong Yang; Hong-Ye Li; Xiao-Fei Zheng; et al. (Journal of Hazardous Materials, 2025)

Composition characteristics, source analysis and risk assessment of PAHs in surface waters of Lipu - Jun Luo; Gui-Bin Huang; Mei Wang; Ya-Nan Zhang; Zi-Xuan Liu; Qin Zhang; Shao-Yuan Bai; Dan-Dan Xu; Hui-Li Liu; Sheng-Peng Mo; Xiao-Bin Zhou; Ming-Ming Fu (Journal of Hazardous Materials, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Fluoride ions enhanced cobalt ferrite for peroxymonosulfate activation with efficient performance and active oxygen yield regulation - Yuhan Luo; Chao Liu; Shurui Kang; Chenghan Ji; Bo Lai; Weiming Zhang; Jun Li; Yi Ren (Journal of Hazardous Materials, 2025)

From waste to wealth: Separation of alumina from coal fly ash and synergistic preparation of soil amendments - Lang Xing; Guanghui Li; Jun Luo; Hao Jiang (Journal of Environmental Management, 2025)

Strengthening mechanism of water content reduction in electrolytic manganese residue by sodium oleate - Jing Wang; Zihan Li; Jiancheng Shu; Zongchen Wei; Shaoqin Chen; Hongyuan Zhao; Jun Luo; Huimin Yang; Yanyan You; Mengjun Chen; Yong Yang (Journal of Environmental Chemical Engineering, 2025)

Identification of the hub genes involved in ATF5 mediated stress response in vitrified mouse oocytes based on WGCNA - Guizhen Zhou; Aiju Liu; Jiachen Bai; Yixiao Zhu; Xinhua Zou; Yuwen Luo; Yizaitiguli Reyimjan; Yan Ma; Shuaixiang Huang; Yunpeng Hou; Jun Li; Xiangwei Fu (Cryobiology, 2025)

Bionic wet-adhesive tooth band-aid with bidirectional anchoring to promote dentin remineralization - Jieyu Zhu; Li Zhen; Yuan Gao; Jun Luo; Jianshu Li; Jiaojiao Yang; Jiyao Li (Chemical Engineering Journal, 2025)

High-performance lithium storage anode: Polypyrrole-coated microrods BiSBr with conversion-alloying dual mechanism - Yonggen Tan; Sen Li; Zhiyuan Huang; Wanda Kang; Yingkai Hua; Xingchen Liu; Guiwen Luo; Xi Chen; Jun Feng (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Changes in granular textures of debris flow viewed from the unified grain size distribution - Taiqiang Yang; Yong Li; Xiaojun Guo; Wei Cheng; Qiming Zhong; Jingjing Liu; Jun Zhang; Junyao Luo (Natural Hazards, 2025)

Copper oxide nanoparticles disrupt lysosomal function and promote foam cell formation in RAW264.7 macrophages - Yilin Luo; Kun Zhang; Lejiao Mao; Meiling Tan; Xiaomei Dong; Na Li; Yuexing Zhou; Chengzhi Chen; Zhen Zou; Jun Zhang (Toxicology, 2025)

Structurally diverse sesquiterpenoids from Sarcandra glabra and their anti-inflammatory activities - An Huang; Mengmeng Yu; Houli Jiang; Danyang Zhang; Zhenyu Zan; Jun Luo; Yi Li (Phytochemistry, 2025)

Associations of multiple metals exposure with immunoglobulin levels in pregnant women: Hangzhou Birth Cohort Study - Jiena Zhou; Lanfei Jin; Yexinyi Zhou; Kunhong Zhong; Kegui Huang; Qi Zhang; Jun Tang; Xue Zhang; Lihe Peng; Shuai Li; Na Lv; Dongdong Yu; et al. (Journal of Environmental Sciences, 2025)

The defect engineering design of COCN/L-CdS/Ni2P for promoting hydrogen energy generation from seawater coupling with photoreforming of plastics - Zhe Yin; Ziwen Wang; Jun Wang; Binglin Tang; Guoping Yu; Qiuyu Wang; Huanyu Chen; Kangzheng Li; Zhichao Zhang; Qingcheng Luo; Fuqin Zhang; Bo Lv (Fuel, 2025)

Hypoglycemic effect of dietary fibers from Moringa oleifera leaves: In vitro and in vivo studies - Xiufen Li; Jinye Yong; Bing Zhao; Yubo Zhu; Jia Luo; Jun Sheng; Yang Tian (Food Research International, 2025)

Intrinsically modified hydrogel electrolyte with highly stretchability, super adhesion and rapid recovery for highly reversible flexible zinc ion batteries - Yanhui Zhang; Yue Li; Kui Chen; Fusheng Luo; Qinqin Xu; Jun Huang; Haibo Xie (Chemical Engineering Journal, 2025)

Impact of pectin structural diversity on gut microbiota: A mechanistic exploration through in vitro fermentation - Weihao Zhang; Hanyan Luo; Wingshan Keung; Yuiman Chan; Kamchun Chan; Xiang Xiao; Fangfei Li; Aiping Lyu; Caixia Dong; Jun Xu (Carbohydrate Polymers, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

SIRT5: a potential target for discovering bioactive natural products - Yuwei Xie; Nali Cai; Xiaohua Liu; Liangliang He; Yiming Ma; Changyu Yan; Juan Liang; Shu-Hua Ouyang; Ao Luo; Yingzhi He; Jun Lu; Dang Ao; et al. (Journal of Natural Medicines, 2025)
Silent information regulator 5 (SIRT5) is the fifth member of the sirtuin family, which is mainly expressed in mitochondrial matrix. SIRT5 plays a key role in metabolism and antioxidant responses, and is an important regulator for maintaining intracellular homeostasis. Given its involvement in multiple cellular processes, dysregulation of SIRT5 activity is associated with a variety of diseases. This review explores the structural characteristics of SIRT5 that influence its substrate specificity, highlights recent research advances, and summarizes its four key enzymatic activities along with their corresponding substrates in disease contexts. We also discuss the natural products that modulate SIRT5 activity and identify potential targets of SIRT5 through virtual docking, which may provide new therapeutic avenues. Although the mechanism of SIRT5 in diseases needs to be further elucidated and deglutathionylation activities are still at an early stage, targeting SIRT5 and its substrates holds significant promise for the development of novel therapeutics. Graphical abstract

Porcine epidemic diarrhea virus induces mitophagy to inhibit the apoptosis and activation of JAK/STAT1 pathway - Xin Li; Yiwan Wu; Jin Peng; Bingjie Li; XiaoLong Li; Zhibin Yan; Gen Li; Yue Zhang; HongLing He; Jun Luo; Xiaofeng Guo (Veterinary Microbiology, 2025)

Building the resilient food waste supply chain for the megacity: Based on the Multi-scale Progressive Fusion framework - Tianrui Zhao; Huihang Sun; Yihe Wang; Wei Zhan; Lipin Li; Yanliang Li; Weijia Li; Xiaomi Tang; Shanshan Luo; Xuanlong Shang; Jun Zhang; Yu Tian (Resources, Conservation and Recycling, 2025)

Integrative proteogenomic and pharmacological landscape of acute myeloid leukaemia - Hanlin Wang; Jun-Yu Xu; Tao Wang; Gaoya Xu; Guanghao Luo; Mingya Zhang; Gusheng Tang; Chang Wang; Libing Wang; Weijia Fu; Xiong Ni; Linhui Zhai; et al. (Science Bulletin, 2025)

Red light-emitting diode irradiation delays the senescence of postharvest pakchoi through promoting antioxidant capacity and regulating ascorbate-glutathione cycle - Feng Guo; Ying Sun; Huali Hu; Hongsheng Zhou; Yingtong Zhang; Xuesong Liu; Jun Ling; Shufen Luo; Pengxia Li (Postharvest Biology and Technology, 2025)

Increased expression of an isoform of the long non-coding RNA, lnc37707, is associated with malathion resistance in Bactrocera dorsalis - Li-Wei Meng; Zong-Yu Luo; Fu-Qiang Zhang; Yi-Xuan Dong; Chao Ye; Wei Zhang; Jin-Jun Wang (Pesticide Biochemistry and Physiology, 2025)

A numerical investigation of flow-induced vibrations on crescent-shaped iced circular cylinders - Xiaogang Yang; Zhitao Yan; Mengzhu Li; Yongli Zhong; Jun Luo (Ocean Engineering, 2025)

Biodegradation of skatole by Bacillus subtilis GDAAS-A32 and its inhibition for odor emissions from swine manure - Jing-Yi Hu; Xue-Ying Han; Hong-Pin Chen; Jia-Zhou Li; Zhi-Lin Wang; Xiao-Chun Luo; Jun-Jin Deng (Journal of Environmental Chemical Engineering, 2025)

Influence of hydroxyl substitution on the inhibition of flavonoids in advanced glycation end-products formation in glucose-lysine-arginine Maillard reaction models - Li-Feng Li; Meng-Di Wang; Chen-Yang Zhang; Meng-Yao Jin; Hua-Lei Chen; Huan Luo; Tian-Yu Hou; Zhi-Jun Zhang; He Li (Food Research International, 2025)

Urbanization leads to convergent succession and homogenization of phytoplankton functional traits in a subtropical watershed over 11 years - Yifan Lu; Lei Jin; Huihuang Chen; Anqi Luo; Elias Ehrlich; Shuzhen Li; David M. Wilkinson; Zhansen Sha; Jun Yang (Environmental Research, 2025)

Occurrence and distribution of PAHs in the Yangtze River and urban river waters of Nanjing, China: Insights from in situ DGT measurements - Qiuyu Rong; Hao Zhang; Yanying Li; Liying Yan; Jun Luo; Kevin C. Jones (Environmental Pollution, 2025)

Carbon confined Mo doped CoP for alkali overall water splitting with enhanced catalytic activity and durability - Jiabing Luo; Yongxiao Tuo; Jianchao Zhang; Wenle Li; Shutao Wang; Yanpeng Li; Yuan Pan; Yan Zhou; Jun Zhang (Chemical Engineering Journal, 2025)

Constraining sulfate sources and its implications on atmospheric pCO2 in Arid Regions: Evidence from the Tarim Basin - Guo-Dong Jia; Jun Zhong; Si-Liang Li; Sen Xu; Han Luo; Cong-Qiang Liu (Chemical Geology, 2025)

NODDI Identifies Cognitive Associations with In Vivo Microstructural Changes in Remote Cortical Regions and Thalamocortical Pathways in Thalamic Stroke - Jie Zhang; Lingling Li; Renjie Ji; Desheng Shang; Xinrui Wen; Jun Hu; Yingqiao Wang; Dan Wu; Li Zhang; Fangping He; Xiangming Ye; Benyan Luo (Translational Stroke Research, 2025)

Hypogene sulfide precipitation during phyllic alteration: insights from copper isotopic evolution of the Dexing porphyry Cu–Mo–Au deposit, South China - Jia-Feng He; Guo-Guang Wang; Matthew J. Brzozowski; Pei Ni; Xiang-Long Luo; Jun Mu; Weiqiang Li (Mineralium Deposita, 2025)

IRF4 Knockdown Inhibits the Chronic Rhinosinusitis Without Nasal Polyps Development by Regulating NLRP3/Caspase-1/GSDMD-Mediated Pyroptosis - Jun Xu; Jiahui Li; Xiaoya Wang; Yunsong An; Wenlong Liu; Renzhong Luo; Changzhi Sun (Biochemical Genetics, 2025)

Monthly variations in nutrient utilization along 45°E transect in the Cosmonaut Sea, East Antarctica during austral summer - Xufeng Yang; Dong Li; Jun Zhao; Cai Zhang; Changfeng Zhu; Shunan Cao; Guangfu Luo; Gaojing Fan; Yongming Sun; Ji Hu; Haifeng Zhang; Peisong Yu; et al. (Acta Oceanologica Sinica, 2025)

Influence of austral summer sea ice melting timing on particle fluxes and composition in Prydz Bay, East Antarctica - Changfeng Zhu; Yufei Ding; Wenhao Huang; Jun Zhao; Dong Li; Haifeng Zhang; Yanhong Xu; Cai Zhang; Ji Hu; Shunan Cao; Guangfu Luo; Yongming Sun; et al. (Acta Oceanologica Sinica, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Chronic intermittent hypoxia modulates energy metabolic pathways and improves hypoxia tolerance capacity in golden pompano, Trachinotus blochii - Geng Hui Fang; Xiao Li Zhou; Chun Li Ran; Chun Xiu Jin; Shao Yang Bu; Yue Chen; Yong Gong; Zeng Tan Hu; Fei Biao Song; Jian Luo; Jun Long Sun (Science of The Total Environment, 2025)

A study on the efficiency and microbial community of anaerobic/anaerobic/anoxic/oxic membrane bioreactor for treating saline alkali-surfactant-polymer flooding wastewater - Xinxin Zhang; Dong Wei; Qian Lu; Qiushi Zhao; Jun Ma; Guoyu Liu; Jia Ouyang; Erming Luo; Chunying Li; Li Wei (Journal of Water Process Engineering, 2025)

Saltiness perception enhancement of myofibrillar protein gel via microwave treatment: Microwave promotes protein aggregation - Na Luo; Jun Xiang; Bimal Chitrakar; Die Li; Yuxia Jin; Chaofan Guo; Xingwei Wang; Jianxin Cao; Xuejiao Wang (Innovative Food Science & Emerging Technologies, 2025)

Green extraction of α-nitroso-β-naphthol from wastewater using hydrophobic deep eutectic solvents: A comprehensive study of efficiency and mechanism - Jie Qian; Ying-hua Li; Di Luo; Si-nan Liu; Fei Su; Jun-xiang Wang (Environmental Pollution, 2025)

Low-temperature one-pot synthesis of Fe-doped hydrotalcite for enhanced boron adsorption and reduced dissolution loss - Chun Bai; Qinglong Luo; Huifang Zhang; Mingzhe Dong; Jun Li; Xueying Wang; Mingzhen Li; Fuliang Ma; Zhijian Wu; Xiao Du (Desalination, 2025)

Unity of terrestrial and extraterrestrial soils in granular configuration - Jun Zhang; Yong Li; Yifei Cui; Zi Wu; Yuan Xue; Jianyi Cheng; Hu Jiang; Yao Li; Jian Guo; Jiayan Nie; Guodong Wang; Ao Luo (Earth and Planetary Science Letters, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Dynamic analysis of a vehicle-track coupled system subjected to uneven frost heave in the subgrade-bridge transition zone - Binqiang Li; Jun Luo; Yanbo Bai; Zhenxing He; Yapeng Wang; Penghao Li; Wanming Zhai (Cold Regions Science and Technology, 2025)

Effects of Cadmium and Lead Co-exposure on Sleep Status in Rural Areas Northwestern China - Min Huang; Honglong Zhang; Haiping Wang; Jingping Niu; Bin Luo; Gang Wu; Xun Li; Jun Yan (Biological Trace Element Research, 2025)

A survey on vehicle–drone cooperative delivery operations optimization: Models, methods, and future research directions - Jing Zhou; Jin Yi; Zhenyu Yang; Huayan Pu; Xinyu Li; Jun Luo; Liang Gao (Swarm and Evolutionary Computation, 2025)

Hazard analysis and control measures for hydrogen-blended natural gas leakage in utility tunnels - Shanbi Peng; Jia Luo; Wei Li; Jun Jiang; Enbin Liu (Process Safety and Environmental Protection, 2025)

2.08 Ga andesitic gneisses in the southwestern Yangtze Block: Unveiling new insights into its geological evolution - Jun-Ping Liu; Zai-Bo Sun; Wei-Ke Li; Hua-Li Luo; Shi-Jun He; Shao-Bin Hu; Jiang-Tai Zhao; Hai-bao Yan; Ming-Guo Zhai; Hai-Long He (Precambrian Research, 2025)

Chemical constituents, biological activities, and quality evaluation of agarwood produced from the qi-nan germplasm of Aquilaria sinensis - Si Li; Yangwenqing Deng; Dong-Bao Hu; Ji-Feng Luo; Pei-Ji Zhao; Jun Yang; Yue-Hu Wang (Phytochemistry Letters, 2025)

Inactivation of antibiotic resistance genes by nanoscale zero-valent iron modified biochar composites: Synergistic effect of oxidative damage and physical destruction - Xiaohan Ma; Jinhao Yao; Tongtao Yue; Liuqingqing Liu; Cuizhu Sun; Zhaohui Cai; Yifan Liu; Mengying Shao; Jun Wu; Xianxiang Luo; Fengmin Li; Hao Zheng (Chemical Engineering Journal, 2025)

Inhibition of electron transfer in anaerobic ammonia-oxidized granular sludge by polyethylene terephthalate microplastics and nanoplastics: A new perspective on molecular docking and molecular dynamics simulations - Chaofan Xie; Dongyue Li; Jiarui Li; Linzhu Du; Yanshuo Wu; Rong Luo; Zheng Wang; Jun Li; Yuhan Zhu; Wei Guo (Chemical Engineering Journal, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

An in-depth understanding of the role and mechanisms of T cells in immune organ aging and age-related diseases - Yudai Xu; Zijian Wang; Shumin Li; Jun Su; Lijuan Gao; Junwen Ou; Zhanyi Lin; Oscar Junhong Luo; Chanchan Xiao; Guobing Chen (Science China Life Sciences, 2025)

CircRNA CDR1AS promotes cardiac ischemia–reperfusion injury in mice by triggering cardiomyocyte autosis - Lina Xuan; Jun Chen; Hua Yang; Junwei Hao; Siyun Li; Qingqing Zhang; Hailong Zhang; Shengjie Wang; Huishan Luo; Jianjun Guo; Xingmei Yang; Guangze Wang; et al. (Journal of Molecular Medicine, 2025)

Role of autophagy in resistance to ivermectin in Haemonchus contortus - Nana Fu; Xiaoping Luo; Junyan Li; Xuezhang Zhou; Jun Du; Bintao Zhai; Anben Li; Xiaoye Yang; Yang Liu (Veterinary Parasitology, 2025)

Dynamic analysis of high-speed vehicle-track coupled system due to lateral differential deformation induced by subgrade frost heave - Binqiang Li; Jun Luo; Yanbo Bai; Zhenxing He; Yapeng Wang; Jianfeng Yun; Penghao Li; Wanming Zhai (Transportation Geotechnics, 2025)

Unraveling the mechanisms of post-treatment to enhance humification and Cd remediation in compost through EDTA-Fenton-Like systems - Hongjuan Jiang; Zhigang Yi; Yaoning Chen; Yuanping Li; Li Chen; Jun Wang; Yaoqin Nie; Mengwei Luo; Qianruyu Wang; Wei Zhang; Yanting Wu; Guangming Zeng (Science of The Total Environment, 2025)

Decreased and fragmented greenspaces in and around rural residential areas of eastern China in the process of urbanization - Wanying Li; Jun Wang; Yuan Luo (Remote Sensing Applications: Society and Environment, 2025)

Hyperspectral classification of ancient cultural remains using machine learning - Rongji Luo; Peng Lu; Panpan Chen; Hongtao Wang; Xiaohu Zhang; Shugang Yang; Qingli Wei; Tao Wang; Yongqiang Li; Tao Liu; Deyang Jiang; Jun Du; et al. (Remote Sensing Applications: Society and Environment, 2025)

Sophflarines B−E, four distinctive matrine alkaloids from Sophora flavescens with potential neuroprotective activities - Ding Luo; Qian Xie; He Tian; Xin-Kai Zheng; Jia-Wen Zou; Yue-Hao Huang; Yan-Jun Chen; Chun-Lin Fan; Li-Jun Hu; Jian-Xin Chen; Hao Wang; Guo-Cai Wang; et al. (Phytochemistry, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Geotrichum candidum AGRC-GC1 prevented the decay of pulp from Citri Reticulatae Pericarpium production by inhibiting the growth of spoilage microorganisms - Xue-Ying Han; Jing-Yi Hu; Xiao-Chun Luo; Zhi-Lin Wang; Jia-Zhou Li; Shuang Li; Jun-Jin Deng (Food Bioscience, 2025)

Photothermal composite polyamidoxime-graphene oxide/polyacrylamide hydrogel for efficient and selective uranium extraction from seawater - Shuaiyu Zheng; Shuhui Li; Xinyu Luo; Jianwei Bai; Feixiang Gao; Huijun Yan; Maokui Li; Long Huo; Chunhong Zhang; Jun Wang (Desalination, 2025)

NIR-driven GOx-like nanozyme-modified injectable thermoresponsive hydrogel for antibacterial therapy and bone regeneration in periodontitis - Changxing Qu; Tianying Luo; Ruxia Han; Dong Mo; Kun Shi; Xicheng Li; Zhongwu Bei; Meng Pan; Songtao Tan; Jun Liu; Zhiyong Qian (Chemical Engineering Journal, 2025)

Engineered sonosensitive probiotics extracellular vesicles coating for ultrasound-driven anti-infection and immunoregulation in implant infection treatment - Mingyue Han; Shuoyuan Li; Wenqi Wang; Jianshu Li; Jun Luo; Zongke Zhou; Jiyao Li; Duan Wang; Jiaojiao Yang (Chemical Engineering Journal, 2025)

Biomineralization-inspired functional biomaterials: From principles to practice - Haohua Hu; Yuting Lin; Bin Yang; Xiaoqing Wen; Panqin Ma; Xian Jun Loh; Zheng Luo; Zibiao Li; Yun-Long Wu (Chemical Engineering Journal, 2025)

Mechanism, diffusion, and kinetics characteristics of nitrocellulose denitrification revealed by DFT and MD - Shen Li; Zhong-Xin Liu; Shi-Ying Li; Ya-Jun Ding; Zhong-Liang Xiao; Jie Zhou; Xiao-Qing Wu; Hong-Lei Fan; Zheng-Hong Luo; Xi-Bao Zhang (Chemical Engineering Journal, 2025)

Skin-inspired graded Micro-Conformal tunneling interface for piezoresistive sensors with Broad-Range Ultra-Sensitivity - Pei Li; Guojun Tai; Wei Luo; Weidong Yang; Dapeng Wei; Zhihao Zhou; Xingzhan Wei; Haofei Shi; Jun Yang (Chemical Engineering Journal, 2025)

Structural characteristics and potential antidepressant mechanism of a water-insoluble β-1,3-glucan from an edible fungus Wolfiporia cocos - Xin-Yao Luo; Meng Yu; Hui-Jun Li; Xin-Yu Kong; Zhong-Mei Zou; Xiao-Chuan Ye (Carbohydrate Polymers, 2025)

Overexpression of OsSTP1 increases grain yield via enhancing carbohydrate metabolism and transport in rice - Dong Liu; Ming-juan Li; Jin-song Luo; Hai-fei Chen; Yong Yang; Gui Xiao; Jun Wu; Abdelbagi M. Ismail; Zhen-hua Zhang (Planta, 2025)

The chloroplast genome of Camellia sinensis var. assamica cv. Duntsa (Theaceae) and comparative genome analysis: mutational hotspots and phylogenetic relationships - Jin Li; Xiao-Yan Qiu; Yu Qin; Han Tang; Jun Tang; Tian-Tian Liu; Li-Zheng Xiao; Hua Luo (Genetic Resources and Crop Evolution, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

A tri-chromosome-based evolutionary algorithm for energy-efficient workflow scheduling in clouds - Yangkun Xia; Xinran Luo; Ting Jin; Jun Li; Lining Xing (Swarm and Evolutionary Computation, 2024)

Distinct effects of flow intermittency on the benthic microbial diversity and their denitrification on different substrates - Lingzhan Miao; Junling Zhang; Dan Luo; Tanveer M. Adyel; Yanhui Ao; Chaoran Li; Yu Yao; Jun Wu; Guoxiang You; Jun Hou (Science of The Total Environment, 2024)

Emerging organic contaminants in sewage sludge: Current status, technological challenges and regulatory perspectives - Dongqin He; Tingting Zhu; Jianqiang Sun; Xiangliang Pan; Jun Li; Hongwei Luo (Science of The Total Environment, 2024)

One-pot synthesis of transition metals-doped LiAl-LDHs to improve lithium adsorption performance and stability - Yujun Ma; Qinglong Luo; Jun Li; Xiao Wang; Fuliang Ma; Mingzhen Li; Xiushen Ye; Kexin Li; Xiao Du; Xueying Wang; Zhijian Wu (Process Safety and Environmental Protection, 2024)

Hydrogen sulfide alleviates cadmium stress in germinating carrot seeds by promoting the accumulation of proline - Miao Sun; Huan-Xuan Qiao; Tao Yang; Peng Zhao; Jun-Hao Zhao; Jia-Ming Luo; Hai-Ye Luan; Xiang Li; Sheng-Cai Wu; Ai-Sheng Xiong (Journal of Plant Physiology, 2024)

Investigation on the rotary atomization evaporation of high-salinity desulfurization wastewater: Performance and products insights - Yurui Wang; Lingxiao Zhan; Qiwei Luo; Heng Chen; Juecen Mao; Jun Wan; Chaozhen Liu; Haijie Chen; Suoqi Zheng; Zhanxing Chen; Zhihao Li; Linjun Yang (Journal of Environmental Management, 2024)

Degradation of particulate matter utilizing non-thermal plasma: Evolution laws of morphological micro-nanostructure and elemental occurrence state - Yunxi Shi; Daolong Hou; Yong Luo; Zhuang Kaiqi; Yinqin Yang; Zhengping Ding; Yixi Cai; Xiaohua Li; Jun Wang; Jing Wang (Journal of Environmental Chemical Engineering, 2024)

Techno-economic and life cycle assessment for the zero-carbon emission process of the production of methanol from VOCs - Qiwei Luo; Qianyue Yu; Qingyang Li; Jun Wan; Yurui Wang; Baiqian Dai; Wenguo Xiang (Journal of Environmental Chemical Engineering, 2024)

Effect of chelator on carbon sequestration and mechanical properties of CO2-cured cement pastes with different pore structures - Ronghua Zhuang; Ying Li; Jun Huang; Quantao Liu; Yingjie Luo; Zizhou Shen; Tianwei Zhang; Yanheng He; Shangheng Zeng; Hao Duan; Jianying Yu (Journal of Environmental Chemical Engineering, 2024)

Erosion modulates the effect of chemical weathering on atmospheric pCO2, Qinghai-Tibet Plateau - Heping Lu; Han Luo; Jun Zhong; Sen Xu; Tingting Ma; Si-Liang Li (Global and Planetary Change, 2024)

Blood cadmium levels and overactive bladder in middle-aged and older adults in the United States: Insights from NHANES 2007–2020 data - Fan Gao; Yin Lu; Qiang Cheng; Qing Ai; Bin Jiang; Zhen-Jun Luo; Guo-Rong Yang; Kai-Kai Lv; Qing Yuan; Hong-Zhao Li (Environmental Pollution, 2024)

Ultra-capacity and low-cost P3-type K0.5Mn0.96Fe0.04O2 cathode materials for K-ion batteries - Jun Cong; Shao-hua Luo; Yi-cheng Lin; Peng-yu Li; Li-xiong Qian; Sheng-xue Yan; Xin Liu; Xue-fei Lei (Chemical Engineering Journal, 2024)

Improved humification and Cr(VI) immobilization by CaO2 and Fe3O4 during composting - Li Chen; Zhigang Yi; Yaoning Chen; Yuanping Li; Hongjuan Jiang; Jun Wang; Yanrong Chen; Yaoqin Nie; Mengwei Luo; Qianruyu Wang; Wei Zhang; Yanting Wu (Bioresource Technology, 2024)

Simultaneous Passivation and Removal of Heavy Metals in the Compost of Agricultural Waste and Sediment by the Enhanced Migration of Liquid Media - Hongjuan Jiang; Yaoning Chen; Yuanping Li; Li Chen; Mengyang Zhao; Jun Wang; Yanrong Chen; Chen Zhao; Mengwei Luo; Qianruyu Wang; Yaoqin Nie (Water, Air, & Soil Pollution, 2024)

Effects of acetate-producing Blautia wexlerae on oxidative stress and NLRP3 inflammasome in obesity-associated male infertility - Yucheng Zhong; Hao Deng; Jun Zhao; Guoqun Luo; Huan Li (Medical Microbiology and Immunology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Effects of dietary vitamin D3 and carbohydrate levels on growth performance, carbohydrate metabolism, and intestinal health of yellow catfish (Pelteobagrus fulvidraco) - Li-Xiang Wu; Qing-Lin Li; Zhi Luo; Mette Sorensen; Xiao-Lei Wei; Hua-Jun Zhang; Xiao-Ying Tan (Aquaculture, 2024)

Intercomparison of measured and modelled photochemical ozone production rates: Suggestion of chemistry hypothesis regarding unmeasured VOCs - Jun Zhou; Wenjie Wang; Yan Wang; Zhen Zhou; Xiongzhou Lv; Meijin Zhong; Bowen Zhong; Minhui Deng; Bin Jiang; Junqing Luo; Jiahua Cai; Xiao-Bing Li; et al. (Science of The Total Environment, 2024)

Methods and experiments for automatic control of surface back pressure based on dung beetle optimizer-PID controller - Zhenyu Long; Jun Li; Hongwei Yang; Wang Chen; Geng Zhang; Biao Wang; Wenxu Wang; Ming Luo; Wentuo Li; Zhiming Yin; Meipeng Ren (Process Safety and Environmental Protection, 2024)

Selective extraction of lithium from salt lake brine by in situ crosslinked stable three-dimensional network film electrodes - Deqing Chen; Zhihua Zhang; Tiezhu Ma; Qinglong Luo; Xiao Du; Xiushen Ye; Xiaogang Hao; Zhijian Wu; Xueying Wang; Jun Li (Process Safety and Environmental Protection, 2024)

Corrigendum to “Association of urban green space with metabolic syndrome and the role of air pollution” [Landsc. Urban Plann. 248 (2024) 105100] - Yi Sun; Yunli Chen; Yuanyuan Huang; Yan Luo; LiPing Yan; Sailimai Man; Canqing Yu; Jun Lv; Chuangshi Wang; Jun Wu; Heling Bao; Bo Wang; et al. (Landscape and Urban Planning, 2024)

Nitrogen and phosphorus recovery from livestock wastewater via magnesium ammonium phosphate precipitation: A critical review of methods, progress, and insights - Jingtong Li; Chunyan Chen; Zifeng Luo; Jinrong Qiu; Li Zhao; Jun Zhang; Xue Xiao; Xiaojun Lin; Xiujuan Wang; Qianyi Cai; Jingwen Zeng; Hongxing Tu; et al. (Journal of Water Process Engineering, 2024)

Corrigendum to “Activity and motion characteristics on the southern segment of the Red River fault zone, Yunnan Province, China” [J. Struct. Geol. 188 (2024) 105245] - Xi Li; Chenxu Wang; Lichun Chen; Qingyun Zhou; Weidong Luo; Jun Guo (Journal of Structural Geology, 2024)

Activity and motion characteristics on the southern segment of the Red River fault zone, Yunnan province, China - Xi Li; Chenxu Wang; Lichun Chen; Qingyun Zhou; Weidong Luo; Jun Guo (Journal of Structural Geology, 2024)

Optimization of degradation conditions for sulfachlorpyridazine by Bacillus sp. DLY-11 and analysis of biodegradation mechanisms - Xiaojun Lin; Jun Zhang; Zifeng Luo; Jingtong Li; Xue Xiao; Xiujuan Wang; Qianyi Cai; Weida Yu; Junshi Tao; Jingwen Zeng; Hongxing Tu; Jinrong Qiu (Journal of Hazardous Materials, 2024)

CDKN1A promotes Cis-induced AKI by inducing cytoplasmic ROS production and ferroptosis - Qian Gao; Jun-ming Chen; Chen-sui-zi Li; Jia-yi Zhan; Xue-dong Yin; Ben-shang Li; Hong-liang Dong; Lian-xiang Luo; Zhi-ling Li (Food and Chemical Toxicology, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Rab7 GTPase, a direct target of miR-131-3p, limits intracellular Spiroplasma eriocheiris infection by modulating phagocytosis - Yubo Ma; Zijie Zhou; Tingyi Luo; Qian Meng; Hui Wang; Xuguang Li; Wei Gu; Jun Zhou; Qingguo Meng (Fish & Shellfish Immunology, 2024)

Reclaiming selenium from water using aluminum-modified biochar: Adsorption behaviors, mechanisms, and effects on growth of wheat seedlings - Xiuyan Wang; Tianxiao Li; Xin Hu; Yuxuan Zhang; Dunhan Zhang; Hanshuo Zhang; Hongxia Xu; Yuanyuan Sun; Xueyuan Gu; Jun Luo; Bin Gao (Environmental Pollution, 2024)

Roll-to-roll Prelithiation of Li-ion Batteries Anodes Using Ultrathin Lithium Strips - Ruowei Yi; Shoulei Hu; Lei Zheng; Yifan Li; Wenting Luo; Haiyang Zhang; Jun Ge; Yanbin Shen; Liwei Chen (Chemical Engineering Journal, 2024)

Deep deoxidation of water in a miniaturized annular rotating device: Experimental investigation and machine learning modeling - Yubin Wang; Yu Chang; Qichen Shang; Jie Deng; Jian Deng; Jun Li; Guangsheng Luo (Chemical Engineering Journal, 2024)

A novel antidepressant homogeneous polysaccharide YLP-1 from Millettia pulchra ameliorates tryptophan metabolism and SCFAs through modulating gut microbiota - Meng Yu; Cong-Cong Cai; Yun-Feng Huang; Yin-Di Zhu; Xin-Yao Luo; Xin-Yu Kong; Wen-Ting Zhang; Hui-Jun Li; Jing-Xian Fang; Zhong-Mei Zou (Carbohydrate Polymers, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

Monitoring and analysis of side-slope deformation along Changgan high-speed railway based on time-series InSAR and BDS techniques - Lv Zhou; Bangding Wei; Jun Ma; Jie Qin; Heng Luo; Youju Huang; Xinyi Li; Changjun Huang (Natural Hazards, 2024)

Phytochemical constituents from rhizomes of Dryopteris crassirhizoma and their anti-inflammatory activity - Xiao-Jun Li; Xiong-Hui Song; Si-Qi Tang; Kai-Xin Wei; Zong-Wu Suo; Yi Xu; Jiao Luo; Hao Huang; Chun-Ying Li; Dong-Xu Liu; Xiang-Qian Liu (Natural Product Research, 2024)

Dynamic variable analysis guided adaptive evolutionary multi-objective scheduling for large-scale workflows in cloud computing - Yangkun Xia; Xinran Luo; Wei Yang; Ting Jin; Jun Li; Lining Xing; Lijun Pan (Swarm and Evolutionary Computation, 2024)

Bauxite residue (red mud) treatment: Current situation and promising solution - Guanghui Li; Jiajian Liu; Lingyun Yi; Jun Luo; Tao Jiang (Science of The Total Environment, 2024)

High sensitivity of dissolved organic carbon transport during hydrological events in a small subtropical karst catchment - Caiqing Qin; Si-Liang Li; Yiping Wu; Adrian M. Bass; Weijun Luo; Hu Ding; Fu-Jun Yue; Pan Zhang (Science of The Total Environment, 2024)

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

Cytotoxic steroidal glycosides from Paris rugosa rhizomes - Jian-Ke Jia; Jun Yang; Xing-Zhi Yang; Ji-Feng Luo; Xiao-Yan Duan; Ying-Li Yang; Jin-Fu Wan; Yue-Hu Wang (Phytochemistry Letters, 2024)

Corrigendum to “Experimental investigation on hydrodynamic interaction between tsunami waves and bridge girder” [Ocean Eng. 294 (15 February 2024), 116683] - Shaolin Yang; Zhiqiang Tan; Wanli Yang; Jun Luo; Ning Wang; Jun Li; Riran Wang (Ocean Engineering, 2024)

Multifunctional Ni-MOF (3D) with N-rich structures for self-generated reactive oxygen species and enhanced electron transfer for synergistic degradation of organic pollutants and removal of Hg(II) - Si-Han Zhou; Rui-Dong Wang; Yun Yang; Hui-ying Li; Li-jun Luo; Feng-zhi Jiang (Journal of Cleaner Production, 2024)

The superior adsorption capacity of biogenic α-Mn2O3 in comparison to chemogenic α-Mn2O3 for five divalent heavy metal cations and the adsorption mechanism of biogenic α-Mn2O3: Experimental and DFT investigations - Mingzhen Hu; Huatao Sun; Jun Luo; Sha Chen; Ding Li (Journal of Environmental Chemical Engineering, 2024)

Multistage regulation of LiMn2O4 electrode for electrochemical lithium extraction from salt-lake - Jun Gu; Linlin Chen; Linjing Fan; Guiling Luo; Xiaowei Li; Xiaojun Chen; Haiyan Ji; Yanhong Chao; Wenshuai Zhu (Desalination, 2024)

Role of polarized and interfacial built-in electric fields in photocatalysts for enhanced photocatalytic performance - Caiyu Luo; Chunping Yang; Jun Xie; Xiang Li; Yan Lin; Shehua Tong; Shanying He (Chemical Engineering Journal, 2024)

Prenatal Exposure to Bisphenols and Visual Impairment in Preschool Children: A Prospective Birth Cohort Study in China - Jinxiu Li; Caimei Mo; Jun Liang; Xingxi Luo; Peng Tang; Lei Lei; Lijun Wang; Dongping Huang; Xiaoqiang Qiu; Xiaoyun Zeng; Shun Liu (Exposure and Health, 2024)

Restoration of degraded alpine meadows from the perspective of plant–soil feedbacks - Chengyang Li; Chimin Lai; Fei Peng; Jun Zhou; Wu Zhang; Xiuli Song; Songying Luo; Jianbo Sun; Xiaojie Chen; Ben Chen; Ji Chen; Xian Xue (Biology and Fertility of Soils, 2024)

Sonic hedgehog ( shh ) gene from Pseudopleuronectes yokohamae (Teleostei: Pleuronectidae): Molecular cloning, characterization, and expression profile during early embryonic, juvenile, and adult stages - Zheng Zhang; Jun Luo; Hui Liu; Shuai Wang; Xilin An; Xuejie Li; Wei Wang (Journal of Fish Biology, 2024)
The hedgehog signaling pathway plays an important role in early development and growth of most vertebrates. Sonic hedgehog ( shh ) gene is a critical regulator of embryonic development in many species, including humans. However, it is not clear what roles shh can play in the development of fish. In this paper, shh gene was cloned from Pseudopleuronectes yokohamae . The full‐length complementary DNA (cDNA) of P. yokohamae sonic hedgehog gene ( Pyshh ) comprises 3194 bp, with a 1317‐bp open reading frame (ORF) that encodes a polypeptide of 438 amino acids with a typical HH‐signal domain and Hint‐N domain. The conserved sequences of the protein among species were predicted by using multiple sequence comparison. The phylogenetic tree construction showed that Py SHH is clustered in a branch of Pleuronectidae . To explore the expression of Pyshh gene in various tissues of P. yokohamae , we used real‐time fluorescence quantitative PCR technology to detect it. The results showed that Pyshh gene is widely distributed in various tissues of P. yokohamae juveniles, different tissues of adult males and females, and is particularly expressed in immune organs. The Pyshh gene expression was higher in the muscle and brain of juvenile fish, and higher in bone, gill, and skin of male fish than that of female fish, suggesting that Pyshh might be involved in the formation of immune organs of P. yokohamae. The expression of Pyshh gene significantly upregulated from the gastrula stage to the hatching stage. Western blotting of the expression levels of Py SHH during different embryonic development stages revealed that Py SHH levels increased gradually during development stages from oosperm stage to hatching stage. These results indicate that Pyshh is highly conserved among species and plays a critical role in the complex process of embryonic development. Its precise regulation is essential for the proper formation of many organs and tissues in the body, and disruptions in its function may have serious consequences for the formation of immune organs in fish.

Levels, sources, and health risk assessment of phthalate acid esters in indoor dust of various microenvironments in university - Jun Pan; Xin Li; Ping Ding; Haojie Luo; Sha Cai; Qing Ge; Liuyi Zhang; Guocheng Hu (Chemosphere, 2024)

Theoretical analysis of naproxen reaction with sulfate and hydroxyl radicals in the aqueous phase: Investigating reactive sites and reaction kinetics - Ji-Feng Yang; Wan-Li You; Deng You; Li-Ying Zheng; Jun-Ling Jin; Sheng-Lian Luo (Chemosphere, 2024)

Investigation of oxygen packaging to maintain beef color stability and microbiology safety after periods of long-term superchilled storage - Jun Yang; Xue Chen; Xinxin Duan; Ke Li; Haijian Cheng; Ge Sun; Xin Luo; David L. Hopkins; Benjamin W.B. Holman; Yimin Zhang; Enliang Song (Meat Science, 2024)

Multi-omics insights into the function and evolution of sodium benzoate biodegradation pathway in Benzoatithermus flavus gen. nov., sp. nov. from hot spring - Chao-Jian Hu; Yi-Qing Lv; Wen-Dong Xian; Jian-Yu Jiao; Zheng-Han Lian; Sha Tan; Meng-Meng Li; Zhen-Hao Luo; Ze-Tao Liu; Ai-Ping Lv; Lan Liu; Mukhtiar Ali; et al. (Journal of Hazardous Materials, 2024)

Freezing/thawing pretreatment for enhanced energy and resource recovery from waste activated sludge: A critical review - Qiuxiang Xu; Jun Zhao; Liwen Luo; Dongyi Li; Min Pan; Xuran Liu; Jonathan W.C.Wong (Journal of Cleaner Production, 2024)

Tin isotope heterogeneity and baseline of the upper continental crust - Jia-Xin She; Weiqiang Li; Edith Kubik; Frédéric Moynier; Xiang-Long Luo; Jun Mu; Shichao An; Chang-Zhi Wu; Zhongya Hu; Junfeng Ji (Geochimica et Cosmochimica Acta, 2024)

Effects of cellulose diameter on the formation and rheological properties of edible walnut oleogels structured by cellulose nanofiber - Yuxuan Zou; Yang Tian; Bing Zhao; Jienan Li; Jia Luo; Jun Sheng; Xiufen Li (Food Hydrocolloids, 2024)

Structure, rheology and stability of walnut oleogels structured by cellulose nanofiber of different lengths - Xiufen Li; Bing Zhao; Yuxuan Zou; Guanshui Guo; Jienan Li; Jun Sheng; Yang Tian; Jia Luo (Food Hydrocolloids, 2024)

Graphene Sterically-Wrapped textile piezoresistive Sensors: A spray coating path for synergistically advancing sensitivity and response range - Chao Zhang; Meng Tao; Wei Luo; Xinyuan Zhao; Pei Li; Xin Gou; Zhongyao Li; Chenhui Dong; Chunbao Li; Haofei Shi; Jun Yang (Chemical Engineering Journal, 2024)

Recent progress on the organelle targeted AlEgens for bioimaging and treatment of diseases - Qihang Ding; Yan Luo; Jun Hu; Shuai Zhang; Wenzhe Zhang; Yuanyuan Feng; Kun Qian; Xin Li; Zhen Cheng; Meijia Gu (Chemical Engineering Journal, 2024)

In-situ forming carboxymethyl chitosan hydrogel containing Paeonia suffruticosa Andr. leaf extract for mixed infectious vaginitis treatment by reshaping the micro-biota - Shiami Jia; Shengting Huang; Rezhemu Jimo; Yongbu AXi; Yuanhui Lu; Ziling Kong; Jun Ma; Heran Li; Xiao Luo; Yan Qu; Kaijun Gou; Rui Zeng; et al. (Carbohydrate Polymers, 2024)

Micafungin protects mouse heart against doxorubicin-induced oxidative injury via suppressing MALT1-dependent k48-linked ubiquitination of Nrf2 - Li-Qun Lu; Ming-Rui Li; Lin-Lu Huang; Yan-Xi Che; Ya-Nan Qi; Xiu-Ju Luo; Jun Peng (Chemico-Biological Interactions, 2024)

Insight into furfural-tolerant and hydrogen-producing microbial consortia: Mechanism of furfural tolerance and hydrogen production - Li-Li Luo; Ming-Jun Zhu (Bioresource Technology, 2024)

Anti-inflammatory lindenane sesquiterpenoid dimers from the roots of Chloranthus holostegius var. trichoneurus - Xiaoli Wang; Zhenyu Zan; Jun Chi; An Huang; Danyang Zhang; Houli Jiang; Yi Li; Jun Luo (Journal of Natural Medicines, 2024)

Signal Transduction Associated with Mn-induced Neurological Dysfunction - Xiao-wei Zheng; Yuan-yuan Fang; Jun-jie Lin; Jing-jing Luo; Shao-jun Li; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2024)

Alleviation of cadmium uptake in rice (Oryza sativa L.) by iron plaque on the root surface generated by Providencia manganoxydans via Fe(II) oxidation - Ding Li; Zeping He; Sha Chen; Jinyuan Chen; Zhexu Ding; Jun Luo; Zongpei Li; Yuanyi Hu (Archives of Microbiology, 2024)

Development of gonad and brood pouch and expression profiles of cgα, fshβ and lhβ transcripts and plasma 17β-E2 and 11-KT during the first reproductive cycle of farmed big-belly seahorse (Hippocampus abdominalis) - Yuru Li; Limiao Zhao; Weiqi Jin; Renhui Luo; Gang Xu; Yan Fang; Bin Wang; Jun Chen (Aquaculture, 2024)

Histology and transcriptomic analysis reveal the inflammation and affected pathways under 2-methylisoborneol (2-MIB) exposure on grass carp - Huan Han; Jun-ming Zhang; Shuang Ji; Xiang-biao Zeng; Xi-chen Jin; Zi-qian Shen; Bin Xie; Xue-neng Luo; Kang Li; Li-ping Liu (Science of The Total Environment, 2024)

Recent advances in hydrogen process safety: Deflagration behaviors and explosion mitigation strategies - Peng Yang; Tao Wang; Yuhuai Sheng; Yingying Yu; Ruikang Li; Bin Su; Fangming Cheng; Jiao Qu; Jun Deng; Zhenmin Luo (Process Safety and Environmental Protection, 2024)

The biocontrol potentiality of Bacillus amyloliquefaciens against postharvest soft rot of tomatoes and insights into the underlying mechanisms - Xiaoyun Zhang; Qingrong Yue; Yu Xin; Guillaume Legrand Ngolong Ngea; Solairaj Dhanasekaran; Ruijie Luo; Jun Li; Lina Zhao; Hongyin Zhang (Postharvest Biology and Technology, 2024)

Data driven damping separation method for the Mega-offshore wind turbine tower - Gang Liu; Jun Luo; Guoqing Huang; Rongfu Li; Weidong Ji; Tao Long (Ocean Engineering, 2024)

Association of urban green space with metabolic syndrome and the role of air pollution - Yi Sun; Yunli Chen; Yuanyuan Huang; Yan Luo; LiPing Yan; Sailimai Man; Canqing Yu; Jun Lv; Chuangshi Wang; Jun Wu; Heling Bao; Bo Wang; et al. (Landscape and Urban Planning, 2024)

Deciphering the pathogenic risks of microplastics as emerging particulate organic matter in aquatic ecosystem - Ling-Zi Yin; Xiao-Qing Luo; Jia-Ling Li; Zetao Liu; Li Duan; Qi-Qi Deng; Chen Chen; Shaojun Tang; Wen-Jun Li; Pandeng Wang (Journal of Hazardous Materials, 2024)

Tackling climate change in agriculture: A global evaluation of the effectiveness of carbon emission reduction policies - Assa Nsabiyeze; Ruiqin Ma; Jun Li; Hailing Luo; Qinan Zhao; Jan Tomka; Mengjie Zhang (Journal of Cleaner Production, 2024)

Screening and identification of selenium-enriched purine-lowering Lactobacillus plantarum and Lactococcus lactis with high stress tolerance and antioxidant capacity - Jia-Jun Liao; Cai-Yue Tan; Lan Liang; Yi-Zhen Luo; Hong-Lin Li; Yan-Yi Chen; Xiao-Dong Pei; Cheng-Hua Wang (Food Bioscience, 2024)

Enhanced separation flux and compressive strength for oil-water separation by adding sodium lignosulphonate - Hui Jiang; Jun Li; Chao Wu; Zi-wei Xiong; Jia-wei Ding; Hui-fen Su; Ya-hui Li; Wen-bo Luo; Liu-jie Yuan; Si-yi Lv; Lu-xiang Wang; De-qiang Li (Chemical Engineering Journal, 2024)

Downregulation of OATP2B1 by proinflammatory cytokines leads to 5-ASA hyposensitivity in Ulcerative colitis - Ping Li; Jun Luo; Yiming Jiang; Xiaoyi Pan; Minlei Dong; Binxin Chen; Jinhai Wang; Hui Zhou; Huidi Jiang; Yangri Duan; Nengming Lin (Chemico-Biological Interactions, 2024)

Insight into mitigation mechanisms of N2O emission by biochar during agricultural waste composting - Jun Liu; Yunlong Hu; Sijia Gu; Xuemei Li; Zhanglong Ji; Hao Qin; Lihua Zhang; Jiachao Zhang; Hongli Huang; Binghua Yan; Lin Luo (Bioresource Technology, 2024)

LncRNA CCRR maintains Ca2+ homeostasis against myocardial infarction through the FTO-SERCA2a pathway - Hua Yang; Lina Xuan; Shengjie Wang; Huishan Luo; Xiaomeng Duan; Jianjun Guo; Shijia Cui; Jieru Xin; Junwei Hao; Xiufang Li; Jun Chen; Feihan Sun; et al. (Science China Life Sciences, 2024)

Exploration of the molecular mechanism of tea polyphenols against pulmonary hypertension by integrative approach of network pharmacology, molecular docking, and experimental verification - Huan Yang; Jun Cao; Jian-Min Li; Cheng Li; Wen-Wu Zhou; Jin-Wen Luo (Molecular Diversity, 2024)

Age-related changes in the mitochondrial, synthesis of steroids, and cellular homeostasis of the chicken ovary - Xiao-zhi Zhan; Pei Luo; Chen Zhang; Liu-jun Zhang; Xu Shen; Dan-li Jiang; Wen-jun Liu (Animal Reproduction Science, 2024)

Two new alkaloids from the endophytic fungus Schizophyllum sp. HM230 isolated from Vincetoxicum mongolicum Maxim - Zhuang Li; Bing-Wen Zhang; Li Jiang; He Wang; Qing-Yun Ma; Hong-Fei Wang; Jun Zhang; Feng-Li Chen; You-Xing Zhao; Du-Qiang Luo (Natural Product Research, 2024)

SAD2 functions in plant pathogen Pseudomonas syringae pv tomato DC3000 defense by regulating the nuclear accumulation of MYB30 in Arabidopsis thaliana - Tiantian Shi; Yuan Zheng; Rui Wang; Sha Li; Andi Xu; Luoying Chen; Yuanhang Liu; Rong Luo; Chenchen Huang; Yinglu Sun; Jinfeng Zhao; Xiaoying Guo; et al. (Plant Science, 2024)

Catalytic hydrotreatment of fast pyrolysis liquids from Pine wood using Ru-based catalysts supported on nitrogen-doped carbon materials - Yunhui Xia; Nan Xi; Xinyang Yu; Maohua Luo; Shi Chen; Qinglian Wang; Yixiong Lin; Rong Wang; Hao Li; Jun Yue; Chen Yang; Wang Yin; et al. (Fuel, 2024)

Tetrabromobisphenol-A/S and their derivatives in surface particulates from workshop floors of three representative e-waste recycling sites in China - Hui Yang; Xiao-Jun Luo; Jia-Zhuo He; Yan-Hong Zeng; Bi-Xian Mai; Li-Zhong Wang; Xiang Bi (Environmental Research, 2024)

Simultaneous selective separation and enrichment of bromine and cesium ions by electrochemically switched amphoteric ion membrane - Tianyun Wang; Xiaowei An; Peifen Wang; Xuli Ma; Yongguo Li; Xiao Du; Xiaogang Hao; Qinglong Luo; Jun Li (Desalination, 2024)

Cytokines-activated nuclear IKKα-FAT10 pathway induces breast cancer tamoxifen-resistance - Xueyan Chen; Weilin Wu; Ji-Hak Jeong; Matjaz Rokavec; Rui Wei; Shaolong Feng; Werner Schroth; Hiltrud Brauch; Shangwei Zhong; Jun-Li Luo (Science China Life Sciences, 2024)

Multi-objective optimization driven by preponderant individuals and symmetric sampling for operational parameter design in aluminum electrolysis process - Lizhong Yao; Jia Chen; Ling Wang; Rui Li; Haijun Luo; Jun Yi (Swarm and Evolutionary Computation, 2024)

Isolation and biomimetic synthesis of phenylpropionyl phenylethylamines from Chloranthus henryi - Nan Wang; Danyang Zhang; Xiaoli Wang; Jie Wen; Qianqian Li; Zhenyu Zan; Shuai Zhao; Lingyi Kong; Jun Luo (Phytochemistry, 2024)

Rock moisture reinforces belowground water storage under different precipitation scenarios and vegetation coverage - Zhanbin Luo; Jun Fan; Ming'an Shao; Qian Yang; Minghui Li (Journal of Hydrology, 2024)

Driving factors for distribution and transformation of heavy metals speciation in a zinc smelting site - Jin He; Chuxuan Li; Xingyao Tan; Zhihong Peng; Haidong Li; Xinghua Luo; Lu Tang; Jing Wei; Chongjian Tang; Weichun Yang; Jun Jiang; Shengguo Xue (Journal of Hazardous Materials, 2024)

Nitric oxide-mediated regulation of Aspergillus flavus asexual development by targeting TCA cycle and mitochondrial function - Kunlong Yang; Yue Luo; Tongzheng Sun; Han Qiu; Qingru Geng; Yongxin Li; Man Liu; Nancy P. Keller; Fengqin Song; Jun Tian (Journal of Hazardous Materials, 2024)

Establishment and characterization of a golden pompano (Trachinotus blochii) fin cell line for applications in marine fish pathogen immunology - Jin-Feng Tong; Lang Yu; Rui-Hai Gan; Li-Ping Shi; Shao-Yang Bu; Yue Gu; Xin Wen; Jun-Long Sun; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2024)

Electrolyte design to regulate the electrode–electrolyte interface on the electrochemical performance for K0.5MnO2||graphite-based potassium-ion batteries - Yicheng Lin; Shaohua Luo; Pengwei Li; Jian Feng; Wei Zhao; Jun Cong; Shengxue Yan (Chemical Engineering Journal, 2024)

Integrating network pharmacology and experimental models to identify notoginsenoside R1 ameliorates atherosclerosis by inhibiting macrophage NLRP3 inflammasome activation - Jingyue Yu; Jinyu Hu; Margaret Baldini; Huan Lei; Lei Li; Shanshan Luo; Jielian Wu; Xupin Liu; Dan Shan; Yanfei Xie; Haihong Fang; Jun Yu (Journal of Natural Medicines, 2024)

Modelling the impact of replacing fish oil with plant oils: A meta‐analysis to match the optimal plant oil for major cultured fish - Yi‐Fan Qian; Jun‐Xian Wang; Fang Qiao; Yuan Luo; Li‐Qiao Chen; Mei‐Ling Zhang; Zhen‐Yu Du (Reviews in Aquaculture, 2024)
The replacement of fish oil with plant oils is a common practice in aquaculture to compensate for the shortage of fish oil supply and has been thoroughly studied. However, because the experimental conditions vary in many aspects, the results are usually inconsistent quantitatively. Therefore, a meta‐analysis was conducted based on a dataset containing 328 articles to systematically model the influence of plant oils on the main aquaculture fish. In addition to demonstrating the species‐specific dose‐dependent impact of plant oils on fish growth, feed utilization efficiency, lipid deposition and health parameters, we have also investigated the role of other factors in this process. We found that the adverse effects caused by plant oils worsen as the experimental duration extends for Atlantic salmon, while Gilthead seabream and European seabass gradually adapt to the change. Further, water temperature could be a decisive factor for Rainbow trout, and early adaptation to plant oils would be helpful for Gilthead seabream. Moreover, sufficient fishmeal supply could alleviate the adverse effects caused by plant oils for most species, but for Gilthead seabream and European seabass, the growth suppression effect of plant oil was larger when fed high‐fishmeal diets. Besides, by comprehensively considering the effects of plant oils, we matched the potential optimal plant oil for each fish species. Our article quantitatively modelled the adverse effects of replacing fish oil with plant oils, investigated the influences of assistant factors and offered a panorama of the research status with emphasis on potential breakthrough orientations.

Biotransformation of Pb and As from sewage sludge and food waste by black soldier fly larvae: Migration mechanism of bacterial community and metalloregulatory protein scales - Bo Deng; Junlong Luo; Chao Xu; Xin Zhang; Jun Li; Qiaoxia Yuan; Hongliang Cao (Water Research, 2024)

The effects of different electrode materials on the electric field-assisted co-composting system for the soil remediation of heavy metal pollution - Yaoning Chen; Yu Yuan; Yuanping Li; Li Chen; Hongjuan Jiang; Jun Wang; Hui Li; Yanrong Chen; Qianruyu Wang; Mengwei Luo (Science of The Total Environment, 2024)

Development of a novel DGT passive sampler for measuring polycyclic aromatic hydrocarbons in aquatic systems - Qiuyu Rong; Yanying Li; Jun Luo; Liying Yan; Kevin C. Jones; Hao Zhang (Journal of Hazardous Materials, 2024)

Biotransformation of HBCDs by the microbial communities enriched from mangrove sediments - Fei Yu; Bing Zhang; Yongjin Liu; Wenqi Luo; Haonan Chen; Jun’na Gao; Xueying Ye; Jin Li; Qingyi Xie; Tao Peng; Hui Wang; Tongwang Huang; et al. (Journal of Hazardous Materials, 2024)

Pristine and Fe-functionalized biochar for the simultaneous immobilization of arsenic and antimony in a contaminated mining soil - Jiayi Li; Yurong Gao; Caibin Li; Fenglin Wang; Hanbo Chen; Xing Yang; Paramsothy Jeyakumar; Binoy Sarkar; Zhenbao Luo; Nanthi Bolan; Xiaofei Li; Jun Meng; et al. (Journal of Hazardous Materials, 2024)

Enhanced atomic H* utilization on urchin-like TiO2-supported palladium nanoparticles for efficient electrocatalytic detoxification of chlorinated organics - Jun Zhang; Shuyue Liu; Shiyu Lu; Chunyuan Wang; Pingjuan Liang; Huan Yi; Mengjie Li; Laizheng Luo; Rong Wang; Guangming Jiang (Fuel, 2024)

Mitochondria immobilized carbonized polymer dots for ratio-metric tracking mitophagy - Xueting Luo; Wentao Xiang; Yi Lu; Erjing Wang; Jun You; Cao Li; Ziqiang Xu (Chemical Engineering Journal, 2024)

ECM-inspired calcium/zinc laden cellulose scaffold for enhanced bone regeneration - Chuan Luo; Yuan-Min Li; Kai Jiang; Kai Wang; Maja Kuzmanović; Xuan-He You; Yao Zhang; Jun Lei; Shi-Shu Huang; Jia-Zhuang Xu (Carbohydrate Polymers, 2024)

Karst fissures mitigate the negative effects of drought on plant growth and photosynthetic physiology - Jie Luo; Wei-xue Luo; Jun-ting Liu; Yong-jian Wang; Zong-feng Li; Jian-ping Tao; Jin-chun Liu (Oecologia, 2024)

Concurrent enhancement of biomass production and phycocyanin content in salt-stressed Arthrospira platensis: A glycine betaine- supplementation approach - Chunli Yu; Yao Hu; Yuqin Zhang; Wei Luo; Jing Zhang; Peilun Xu; Jun Qian; Jun Li; Jianfeng Yu; Jin Liu; Wenguang Zhou; Shengxi Shao (Chemosphere, 2024)

Influence mechanism of anions on iron doping into swine bone char: Promoting non-radical oxidation of acetaminophen in a Fenton-like system - Yifeng Zeng; Hongwei Luo; Dongqin He; Jun Li; Anping Zhang; Jianqiang Sun; Juan Xu; Xiangliang Pan (Science of The Total Environment, 2024)

Sedimentary characteristics of mixed source fine-grained gravity-flow and its significance for shale oil exploration in a lacustrine depression basin: A case study of the Chang 73 Sub-member of the Triassic Yanchang Formation in Ordos Basin, NW China - Lin Wang; Qiqi Lyu; Linhan Li; Jun Liu; Shunshe Luo; Xuehu Sun; Lei Zhang; Xinshou Xu (Sedimentary Geology, 2024)

Diverse sesquiterpenoid monomers from the leaves of Sarcandra glabra - Zhenyu Zan; An Huang; Siyuan Wang; Xiaoli Wang; Mengmeng Yu; Danyang Zhang; Houli Jiang; Nan Wang; Jun Luo; Yi Li (Phytochemistry Letters, 2024)

Dietary short-term supplementation of grape seed proanthocyanidin extract improves pork quality and promotes skeletal muscle fiber type conversion in finishing pigs - Yiqiang Li; Yadi Feng; Xiaoling Chen; Jun He; Yuheng Luo; Bing Yu; Daiwen Chen; Zhiqing Huang (Meat Science, 2024)

Visible light-enhancing antibacterial ability of gold ions for its application of the prevention and treatment of dentin caries - Kangjing Li; Beibei Xie; Jun Zhou; Chunyun Liang; Cong Liu; Yiwu Qin; Fengyuan Zhou; Xuan He; Zhiyong Chen; Xiaoping Su; Ying Luo; Cuiping Li; et al. (Journal of Cleaner Production, 2024)

Insight of persulfate-based treatments induced stable volatile fatty acids promotion during waste activated sludge anaerobic fermentation in semi-continuous-flow reactors: Focusing on variations of substrate and microbial functional profiles - Qin Zhang; Yuke Xu; Wenzhuo Li; Yiyun Liu; Zailiang Liu; Jun Zheng; Huijuan Zhang; Jingyang Luo (Journal of Cleaner Production, 2024)

Control of nitrogen and odor emissions during chicken manure composting with a carbon-based microbial inoculant and a biotrickling filter - Haorong Zhang; Liqian Ma; Yinchao Li; Su Yan; Zhenye Tong; Yue Qiu; Xueying Zhang; Xiaoyu Yong; Liwen Luo; Jonathan W.C. Wong; Jun Zhou (Journal of Environmental Management, 2024)

Highly-sensitive, broad-range, and highly-dynamic MXene pressure sensors with multi-level nano-microstructures for healthcare and soft robots applications - Boqing Jia; Zhikang Li; Tengfei Zheng; Jiaxiang Wang; Zhi-Jun Zhao; Libo Zhao; Bin Wang; Jijian Lu; Kang Zhao; Guoxi Luo; Min Li; Qijing Lin; et al. (Chemical Engineering Journal, 2024)

A review for the impacts of circadian disturbance on urological cancers - Tao Li; Yiting Jiang; Yunjin Bai; Kehua Jiang; Guangshi Du; Peng Chen; Chao Luo; Lei Li; Jun Qiao; Jun Shen (Sleep and Biological Rhythms, 2024)

The SIDT2/MDA5/IFN axis contributes to virus resistance in teleost fish - Yaoguo Li; Hao Tang; Mingxue Sun; Qiaolin Liu; Yijing Liao; Hong Luo; Rui Li; Ronghua Wang; Hong Yang; Hongquan Wang; Jun Zou; Tiaoyi Xiao (Aquaculture, 2024)

Recovery of metal ion resources from waste lithium batteries by in situ electro-leaching coupled with electrochemically switched ion exchange - Zeyu Du; Jialu Chen; Shangjun Wang; Xiaowei An; Peifen Wang; Xuli Ma; Xiao Du; Xiaogang Hao; Qinglong Luo; Jun Li; Guoqing Guan (Waste Management, 2024)

Associations between prenatal metal exposure and growth rate in children: Based on Hangzhou Birth Cohort Study - Yexinyi Zhou; Jiena Zhou; Yinyin He; Jiawei Fang; Jun Tang; Shuai Li; Jing Guo; Qiong Luo; Kunhong Zhong; Kegui Huang; Guangdi Chen (Science of The Total Environment, 2024)

Serum exosomes from hepatitis B virus–infected patients inhibit glycolysis in Sertoli cells via miR-122-5p/ALDOA axis - Hao Deng; Yucheng Zhong; Jun Zhao; Xiaohang Li; Guoqun Luo; Huan Li (Reproductive Biology, 2024)

First Pediastrum–temperature transfer function and its application to mid-to-late Holocene reconstruction in Central Asia - Lixiong Xiang; Xiaozhong Huang; Jiawu Zhang; Chong Huang; Antje Schwalb; Jifeng Zhang; Natalia Rudaya; Mingjie Sun; Xiaoyan Mu; Yuan Li; Derui Luo; Farqan Muhammad; et al. (Quaternary Science Reviews, 2024)

Natural product-derived ferroptosis mediators - Yi-Li Chen; Lin-An Xiong; Lie-Feng Ma; Luo Fang; Zha-Jun Zhan (Phytochemistry, 2024)

CRISPR/Cas9-mediated ebony knockout causes melanin pigmentation and prevents moth Eclosion in Ectropis grisescens - Jia-Li Li; Shun-Si Li; Zi-Jun Luo; Ji Lu; Xiao-Ming Cai; Zong-Xiu Luo; Lei Bian; Chun-Li Xiu; Nan-Xia Fu; Nai-Yong Liu; Zhao-Qun Li (Pesticide Biochemistry and Physiology, 2024)

Development and validation of an in situ high-resolution technique for measuring antibiotics in sediments - Yanying Li; Qiuyu Rong; Chao Han; Hanbing Li; Jun Luo; Liying Yan; Degao Wang; Kevin C. Jones; Hao Zhang (Journal of Hazardous Materials, 2024)

Hydroclimatic changes in eastern China during the Holocene based on pollen data and climate modeling - Qin Li; Haibin Wu; Jun Cheng; Wenchao Zhang; Yanyan Yu; Aizhi Sun; Yunli Luo (Global and Planetary Change, 2024)

A novel study of brain microvascular endothelial cells induced by astrocyte conditioned medium for constructing blood brain barrier model in vitro: A promising tool for meningitis of teleost - Yanghui Chen; Yuan Li; Junliang Luo; Zixin Li; Yu Huang; Jia Cai; Dongneng Jiang; Defeng Zhang; Jichang Jian; Jun Qiang; Bei Wang (Fish & Shellfish Immunology, 2024)

Dietary ellagic acid supplementation improves meat quality in growing-finishing pigs - Tengteng Huang; Huawei Li; Xiaoling Chen; Daiwen Chen; Jun He; Bing Yu; Yuheng Luo; Ping Zheng; Hong Chen; Zhiqing Huang (Animal Feed Science and Technology, 2024)

Heterogeneous metal sources for mintage in the early Han empire, second century BCE: archaeometallurgical study of the Banliang coins from the Guanghuacun cemetery, Chengdu, Southwest China - Ding Ma; Ning Wang; Pei Li; Tao Yang; Jun Yang; Ruizhe Wang; Wugan Luo (Archaeological and Anthropological Sciences, 2024)

The Effect of Copper–Cadmium Co-Exposure and Hormone Remediation on the Ovarian Transcriptome of Nile Tilapia (Oreochromis niloticus) - Yijie Wu; Liting Chen; Xin Yan; Jun Xiao; Zhirui Ma; Zhanyang Tang; Zhongbao Guo; Liping Li; Guixiang Tong; Honglian Tan; Fuyan Chen; Xinxian Wei; et al. (Fishes, 2024)
The escalating problem of copper (Cu) and cadmium (Cd) pollution in aquatic environments poses a significant threat to the ovarian tissue and reproductive capacity of fish, hindering the development of the aquaculture industry. However, the combined effects of Cu and Cd on fish gonadal development remain unclear. In this study, the fish species Nile tilapia was stressed with rearing water containing 300 μg/L Cu2+ and 100 μg/L Cd2+ for 30 days, followed by an intraperitoneal injection of luteinizing hormone-releasing hormone (LHRH-α) and human chorionic gonadotropin (HCG) at various concentrations. We investigated the ovarian transcriptome profiles before and after injection. Prior to injection, combined treatment with Cu and Cd resulted in reproductive dysfunction and metal ion imbalance in tilapia. Transcriptomic profiling revealed differential gene annotation concentrated in the MAPK signaling pathway and regulation of GTPase activity. Post-injection, all concentrations of LHRH-α and HCG groups showed an upregulated gonadosomatic index (G.S.I) and higher levels of vitellogenin (VTG), gonadotropin-releasing hormone (GnRH), gonadotropin (GTH), and estrogen (E2) in serum compared to the negative control group. Transcriptomic analysis revealed alterations in various ovarian signaling pathways, preliminarily revealing the in vivo molecular mechanisms and differences in LHRH-α and HCG. The findings from this study could help us better understand how to counteract the effects of combined Cu and Cd exposure on tilapia ovarian development, which has significant implications for the Nile tilapia aquaculture industry.

High-resolution chemical imaging to understand Cd activation in rice rhizosphere of karstic soils - Xing-Yue Li; Xi-Yuan Li; Yi-Fan Jiang; Chao Zhang; Qiong Yang; Maria Manzoor; Jun Luo; Dong-Xing Guan (Chemosphere, 2024)

Sustainable valorizing high-protein feather waste utilization through solid-state fermentation by keratinase-enhanced Streptomyces sp. SCUT-3 using a novel promoter - Wen-Jun Lu; Ming-Shu Zhang; De-Lin Lu; Zhi-Wei Li; Zhen-Dong Yang; Lei Wu; Jing-Tao Ni; Wei-Dong Chen; Jun-Jin Deng; Xiao-Chun Luo (Waste Management, 2024)

Corrigendum to “Serviceability evaluation of highway tunnels based on data mining and machine learning: A case study of continental United States” [Tunnelling and Underground Space Technology 142 (2023) 105418] - Ya-Dong Xue; Wei Zhang; Yi-Lin Wang; Wei Luo; Fei Jia; Sheng-Teng Li; Hao-Jun Pang (Tunnelling and Underground Space Technology, 2024)

Stepwise extraction and utilization of silica and alumina from coal fly ash by mild hydrothermal process - Lang Xing; Xinran Li; Pengxu Cao; Jun Luo; Hao Jiang (Process Safety and Environmental Protection, 2024)

Experimental investigation on hydrodynamic interaction between tsunami waves and bridge girder - Shaolin Yang; Zhiqiang Tan; Wanli Yang; Jun Luo; Ning Wang; Jun Li; Riran Wang (Ocean Engineering, 2024)

A new method of the hydrocarbon secondary migration research: Numerical simulation - Hao Xu; Jun Li; Xiaorong Luo; Ming Cheng; Chao Li; Xiaoying Zhang; Huanquan Pan (Marine and Petroleum Geology, 2024)

An integrated capacitive deionization and photocatalysis system for efficient ammonium removal from low-concentration wastewater - Bin Xu; Kaixiang Jiang; Yonghai Gan; Kegui Zhang; Jie Zhang; Jun Luo; Hui Xu; Zhihao Chen; Wenzhong Yang; Honglin Li; Xinzhe Lu (Journal of Water Process Engineering, 2024)

Tryptophan sulfonate: A new chemical marker for accurate and efficient inspection of sulfur-treated food products - Kam-Chun Chan; Wei-Hao Zhang; Yui-Man Chan; Hiu-Lam Li; Jing Fang; Han-Yan Luo; Jun Xu (Food Chemistry, 2024)

Durability assessment of hybrid double-skin tubular columns (DSTCs) under simulated marine environments - Jun-Jie Zeng; Zhi-Hao Hao; Xiong-Chao Liang; Jia-Luo Li; Yan Zhuge; Feng Liu; Li-Juan Li (Engineering Structures, 2024)

Recovery capability of anaerobic digestion from ammonia stress: Metabolic activity, energy generation, and genome-centric metagenomics - Jun Xu; Zhijian Shi; Ling Xu; Xiaomei Zheng; Yang Zong; Gang Luo; Chen Zhang; Mingxian Liu; Li Xie (Bioresource Technology, 2024)

Stochastic Assembly Increases the Complexity and Stability of Shrimp Gut Microbiota During Aquaculture Progression - Saisai Zhang; Shuang Liu; Hongwei Liu; Hui Li; Jun Luo; Aili Zhang; Yinpeng Ding; Tongjun Ren; Wenbo Chen (Marine Biotechnology, 2024)

China's subtropical deciduous plants are more sensitive to climate change than evergreen plants by flowering phenology - Hong‐Li Li; Arshad Ali; Xu Luo; Ke Liao; Nan Sun; Ming‐Shan Xu; Long‐Bin Sha; Dong He; Yan‐Jun Du; Wei‐Wei Sun; Xiao‐Dong Yang (Global Change Biology, 2024)
The ongoing climate change‐induced shifts in flowering phenology have emerged as a consequential force impacting biodiversity and ecosystems. Despite the globally recognized significance of flowering phenology as a key reproductive attribute, studies in subtropical regions have been relatively fewer, particularly in comparison to temperate and cold regions. Additionally, the nuanced response of deciduous and evergreen plants to climate change remains insufficiently explored. In addressing this gap, we built a phenological model and a generalized linear mixed effect model to assess the differential responses of key flowering phenological traits, that is, first flowering date (FFD), peak flowering date (PFD), end of flowering date (EFD), and flowering duration (FD), to climate factors (temperature and precipitation) between deciduous and evergreen plants. We observed distinct responses in flowering phenological traits to climate change between deciduous and evergreen plants. Specifically, the advancement of FFD, PFD, and EFD in deciduous in response to temperature rise exceeded that in evergreen plants. FD in evergreen plants exhibited a stronger extension to temperature increase compared to deciduous. Conversely, the phenological change of evergreen plants in response to decreasing precipitation was greater than that of deciduous ones. Since temperature is a decisive climatic factor in affecting phenological changes, climate change‐induced advances in flowering phenology of deciduous plants are still larger than evergreen plants. Projections from our phenological model under future climate scenarios (SSP 1‐2.6 and SSP 5‐8.5) indicate a continuous enlargement of difference in flowering phenology between deciduous and evergreen plants, with this trend escalating into the future (2100>2070>2050>2030). The larger extension in FD of evergreens to climate change suggests a potential increase in their proportion within subtropical forest communities relative to deciduous plants. These insights contribute significantly to our understanding of the intricate dynamics of climate‐induced changes in subtropical plant ecosystems.

Anthropogenic disturbance driving population decline of a dominant tree in East Asia evergreen broadleaved forests over the last 11,000 years - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Shuang‐Xiu Xu; Jie Liu; Feng‐Mao Yang; Ya‐Huang Luo; Jun‐Wei Ye; Yao Zhao; Jun Rong; Bing Liu; Peng‐Fei Ma; De‐Zhu Li (Conservation Biology, 2024)
Current biodiversity loss is generally considered to have been caused by anthropogenic disturbance, but it is unclear when anthropogenic activities began to affect biodiversity loss. One hypothesis suggests it began with the Industrial Revolution, whereas others propose that anthropogenic disturbance has been associated with biodiversity decline since the early Holocene. To test these hypotheses, we examined the unique vegetation of evergreen broadleaved forests (EBLFs) in East Asia, where humans have affected landscapes since the early Holocene. We adopted a genomic approach to infer the demographic history of a dominant tree ( Litsea elongata ) of EBLFs. We used Holocene temperature and anthropogenic disturbance factors to calculate the correlation between these variables and the historical effective population size of L. elongata with Spearman statistics and integrated the maximum‐entropy niche model to determine the impact of climate change and anthropogenic disturbance on fluctuation in its effective population size. We identified 9 well‐defined geographic clades for the populations of L. elongata . Based on the estimated historical population sizes of these clades, all the populations contracted, indicating persistent population decline over the last 11,000 years. Demographic history of L . elongata and human population change, change in cropland use, and change in irrigated rice area were significantly negatively correlated, whereas climate change in the Holocene was not correlated with demographic history. Our results support the early human impact hypothesis and provide comprehensive evidence that early anthropogenic disturbance may contribute to the current biodiversity crisis in East Asia.

Length-based stock assessment for Procambarus clarkii aquaculture management in China: An alarming of ongoing recruitment overfishing - Shiyu Jin; Yubin Jiao; Junru Li; Zhiqiang Xu; Yu Xu; Mengmei Zou; Jun Ding; Xiangqian Li; Zhaoyu Wang; Meng Wang; Wei Li; Tanglin Zhang; et al. (Aquaculture, 2024)

MiRNAs enabled Golden pompano (Trachinotus blochii) in response to different reoxygenation patterns after hypoxic stress - Tian Jiang; Jun Long Sun; Chun Xiu Jin; Yu Zhang; Zai Hui Tong; Yue Gu; Fu Cheng Yao; Li Ping Shi; Fei Biao Song; Jian Luo (Aquaculture, 2024)

Vitamin D3 activates the innate immune response and xenophagy against Nocardia seriolae through the VD receptor in liver of largemouth bass (Micropterus salmoides) - Quanquan Cao; Ju Zhao; Mingyao Yan; Zhong Luo; Fu Luo; Lin Feng; Weidan Jiang; Pei Wu; Yan Wang; Debin Li; Haifeng Liu; Jun Jiang (Aquaculture, 2024)

Effects of different picking patterns and sequences on the vibration of apples on the same branch - Guangrui Hu; Jianguo Zhou; Qingyu Chen; Tongyun Luo; Puhang Li; Yu Chen; Shuo Zhang; Jun Chen (Biosystems Engineering, 2024)

Direct humification of biowaste with hydrothermal technology: A review - Yuchao Shao; Zhihua Li; Yuyang Long; Jun Zhao; Weizhong Huo; Zhangrui Luo; Wenjing Lu (Science of The Total Environment, 2024)

Polysulfide regulation by defect-modulated Ta3N5− electrocatalyst toward superior room-temperature sodium-sulfur batteries - Zhen Zhang; Dan Luo; Jun Chen; Chuyin Ma; Matthew Li; Haoze Zhang; Renfei Feng; Rui Gao; Haozhen Dou; Aiping Yu; Xin Wang; Zhongwei Chen (Science Bulletin, 2024)

Phase transformations and microstructure evolution of boron-containing iron concentrate during roasting under CO-CO2-N2 atmosphere: Synergistic effect of soda-ash and CO concentration - Jinxiang You; Meishi Hu; Mingjun Rao; Xin Zhang; Jun Luo; Zhiwei Peng; Guanghui Li (Minerals Engineering, 2024)

Exploring the effect of photobiomodulation and gamma visual stimulation induced by 808 nm and visible LED in Alzheimer's disease mouse model - Hao Xu; Ziyi Luo; Renlong Zhang; Iuliia Golovynska; Yanxia Huang; Soham Samanta; Ting Zhou; Shaowei Li; Bingang Guo; Liwei Liu; Xiaoyu Weng; Jun He; et al. (Journal of Photochemistry and Photobiology B: Biology, 2024)

Simultaneous enhanced generation of reactive oxygen species and H2 over Pd-(Cu-s-Fe0) trimetal for bifunctional catalytic degradation of refractory combined pollutants - Jing Yang; Yongming Ju; Fangfang Li; Shibo Yan; Yu Gong; Zhiyi Deng; Yan You; Jun Luo; Shengtian Zhang (Journal of Cleaner Production, 2024)

Online and in-situ monitoring of the growth of silver nanowires and nanoparticles with conductive measurement - Huangqing Ye; Xuchao Jian; Ying Wang; Jun Long; Xiaofang Zhang; Junqin Wu; Yingying Pan; Yu Wang; Xiping Zeng; Xian-Zhu Fu; Jing-Li Luo (Chemical Engineering Journal, 2024)

Unraveling synergistic mechanisms of polyacrylamide coagulation and Fe2+/CaO2 Fenton-like oxidation to enhance sludge dewatering - Dongqin He; Tingting Zhu; Mingkai Sun; Jingyi Chen; Hongwei Luo; Jun Li (Chemical Engineering Journal, 2024)

Cyclophosphamide reduces gene transcriptional activity and embryo in vitro development by inhibiting NF-κB expression through decreasing AcH4K12 - Zhao-Bo Luo; Liu-Hui Yang; Sheng-Zhong Han; Shuang-Yan Chang; Hongye Liu; Zhi-Yong An; Xiu-Li Zhang; Biao-Hu Quan; Xi-Jun Yin; Jin-Dan Kang (Chemico-Biological Interactions, 2024)

Advances in regulating vitamin K2 production through metabolic engineering strategies - Yan Liu; Jian Wang; Jun-bao Huang; Xiang-fei Li; Yu Chen; Kun Liu; Ming Zhao; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Wei Tao; Jing Wu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Diversity and distribution of yeasts in intertidal zones of China - Hai-Yan Zhu; Da-Yong Han; Liang-Chen Guo; Jun-Ning Li; Xu-Yang Wei; Ri-Peng Zhang; Qi-Ming Wang; Yu-Jie Shang; Lu-Jun Luo; Yu-Hua Wei; Xin-Zhan Liu; Feng-Yan Bai (Frontiers in Marine Science, 2023)
China has the second greatest extent of intertidal zones in the world. The intertidal zone is the most dynamic environments in the biosphere and potentially supports high biodiversity. Marine yeasts show excellent performance in various industrial, environmental and medical applications, however, the marine yeast diversity has rarely been studied in China. In this study, we collected 1241 samples including marine sediments, marine water, plants, and benthos at 161 GPS sites in different types of intertidal zones along the Chinese coastline from north to south. A total of 4436 strains were isolated from these samples using different methods and 286 species including 39 potential novel species were identified from these strains based on the internal transcribed spacer (ITS) region or the D1/D2 domain of the large subunit rRNA gene sequence analysis. The majority of the yeast species in different geographical locations belong to the five orders Serinales , Saccharomycetales , Tremellales , Sporidiobolales , and Pichiales . The yeast species diversity varied depending on sample types, depth of marine sediments, intertidal zone types and geographical locations. Mean annual temperature (MAT), salinity and pH had the greatest effect on the community structures of the yeasts isolated from the intertidal zones. This study represents one of the most comprehensive surveys of marine yeasts in China to date and provides a better understanding of marine yeast diversity and distribution.

Serviceability evaluation of highway tunnels based on data mining and machine learning: A case study of continental United States - Ya-Dong Xue; Wei Zhang; Yi-Lin Wang; Wei Luo; Fei Jia; Sheng-Teng Li; Hao-Jun Pang (Tunnelling and Underground Space Technology, 2023)

Assessing the health risks of coal-burning arsenic-induced skin damage: A 22-year follow-up study in Guizhou, China - Maolin Yao; Qibing Zeng; Peng Luo; Guanghong Yang; Jun Li; Baofei Sun; Bing Liang; Aihua Zhang (Science of The Total Environment, 2023)

Responses of soil microbial communities to manure and biochar in wheat cultivation of a rice-wheat rotation agroecosystem in East China - Jun MENG; Wenjin LI; Yingbo QIU; Zhangtao LI; Linze LI; Yu LUO; Haipeng GUO; Yijun YU; Shengdao SHAN; Huaihai CHEN (Pedosphere, 2023)

Effects of arsenic exposure on trace element levels in the hippocampus and cortex of rats and their gender differences - Xi Yan; Jun Zhang; Junyu Li; Xinglai Zhang; Yi Wang; Xiaolu Chen; Peng Luo; Ting Hu; Xueshan Cao; Hongbin Zhuang; Xiaoxiao Tang; Fang Yao; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Energy-efficient fluorine-free electro-refining of crude lead in a green methanesulfonic acid system - You-gang Li; Cong Chang; Jun-jie Qu; Chang-liu Xiang; Tao Luo; Shan-shan Liu; Shuai Li; Sheng-hai Yang; Heng-hui Wang; Xiao-bo Min; Chang-hong Wang; Yong-ming Chen (Journal of Environmental Chemical Engineering, 2023)

Effects of polyethylene microplastics with different particle sizes and concentrations on the community structure and function of periphytic biofilms - Weiyu Li; Dan Luo; Ning Yan; Lingzhan Miao; Tanveer M. Adyel; Ming Kong; Jun Hou (Journal of Environmental Chemical Engineering, 2023)

Preparation and antibacterial activity of Ag-loaded tobermorite derived from coal fly ash - Hao Jiang; Xinran Li; Zhilong Liu; Xin Zhang; Pengxu Cao; Jun Luo (Journal of Environmental Chemical Engineering, 2023)

Molecular and functional characterization of golden pompano (Trachinotus blochii) TBK1 on IFN regulation - Jin-Feng Tong; Rui-Hai Gan; Lang Yu; Shao-Yang Bu; Jun-Long Sun; Xin Wen; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2023)

Characterizing water body changes in Poyang lake using multi-source remote sensing data - Wenyu Wang; Peng Yang; Jun Xia; Shengqing Zhang; Xiangang Luo; Sheng Hu; Jiang Li; Nengcheng Chen; Chesheng Zhan (Environmental Development, 2023)

A self-assembled hydrogel dressing as multi-target therapeutics to promote wound healing - Yao Wu; Zhaoyu Yang; Xuexuan Li; Teng Li; Jun Zheng; Mingrui Hu; Zhe Yu; Weikang Luo; Wei Zhang; Fei Zheng; Tao Tang; Yang Wang (Chemical Engineering Journal, 2023)

Suppress moisture sensitivity of Ni-rich cathode materials by bioinspired self-assembly hydrophobic layer - Yingde Huang; Pei-Yao Li; Han-Xin Wei; Yu-Hong Luo; Lin-Bo Tang; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Variations of Sr–Nd–Hf–O isotopes and redox conditions across a Neoproterozoic arc magmatic belt in the western margin of the Yangtze craton - Junhua Yao; Wei-Guang Zhu; Chusi Li; Zhong-Jie Bai; Yan-Jun Wang; Lei-Luo Xu (Chemical Geology, 2023)

Protocol for Brain Magnetic Resonance Imaging and Extraction of Imaging-Derived Phenotypes from the China Phenobank Project - Chengyan Wang; Zhang Shi; Yan Li; Xueqin Xia; Xutong Kuang; Shufang Qian; Le Xue; Lizhen Lan; Yudan Wu; Na Zhang; Ji Tao; Xumei Hu; et al. (Phenomics, 2023)

Exploration of the Shared Hub Genes and Biological Mechanism in Osteoporosis and Type 2 Diabetes Mellitus based on Machine Learning - Runhan Zhao; Chuang Xiong; Zenghui Zhao; Jun Zhang; Yanran Huang; Zhou Xie; Xiao Qu; Xiaoji Luo; Zefang Li (Biochemical Genetics, 2023)

Anti-contactin-associated protein-like 2 antibody autoimmune encephalitis with rapidly progressive parkinsonism: a case report and literature review - Xiaohong Qin; Jieying Li; Yuanyuan Luo; Yunsen He; Xiaoqiang Xiao; Arui Tan; Jun Xiao (Acta Neurologica Belgica, 2023)

Molecular mechanisms that regulate the heat stress response in sea urchins (Strongylocentrotus intermedius) by comparative heat tolerance performance and whole-transcriptome RNA sequencing - Lingshu Han; Pengfei Hao; Wenpei Wang; Yanglei Wu; Shuchao Ruan; Chuang Gao; Wanrong Tian; Ye Tian; Xiaonan Li; Luo Wang; Weijie Zhang; Heng Wang; et al. (Science of The Total Environment, 2023)

Interactions between microplastics and contaminants: A review focusing on the effect of aging process - Hongwei Luo; Chaolin Tu; Dongqin He; Anping Zhang; Jianqiang Sun; Jun Li; Juan Xu; Xiangliang Pan (Science of The Total Environment, 2023)

The MKK3–MPK7 cascade phosphorylates ERF4 and promotes its rapid degradation to release seed dormancy in Arabidopsis - Xi Chen; Qiujia Li; Ling Ding; Shengnan Zhang; Siyao Shan; Xiong Xiong; Wenhui Jiang; Bo Zhao; Liying Zhang; Ying Luo; Yiming Lian; Xiuqin Kong; et al. (Molecular Plant, 2023)

Reconstruction of MgAl-layered double hydroxides to LiAl-layered double hydroxides for scalable lithium extraction from salt lake brine - Mingzhe Dong; Qinglong Luo; Jun Li; Kaiyuan Shi; Zhijian Wu; Jie Tang (Minerals Engineering, 2023)

Recycling valuable metals from spent lithium-ion battery cathode materials based on microwave-assisted hydrogen reduction followed by grind-leaching and magnetic separation - Jinxiang You; Zhongxiao Qin; Gaohui Wang; Mingjun Rao; Jun Luo; Zhiwei Peng; Shang Zou; Guanghui Li (Journal of Cleaner Production, 2023)

An eco-friendly technique for shrink-resist finishing of dyed wool via combined use of hydrolase and cyclamate - Zirong Li; Jiancheng Luo; Jun Wang; Yuanyuan Yu; Qiang Wang; Ping Wang (Journal of Cleaner Production, 2023)

Construction of photocatalyst by modification of argentum noble metal and hydrogen doping into WO3 nanoparticles: Enhancing the solar energy utilization - Jun Li; Na Luo; Yinhai Wang; Han Li; Tao Zhang; Xingui Tang; Zhengfa Hu (Fuel, 2023)

Constructing electrochemical sensor using molecular-imprinted polysaccharide for rapid identification and determination of l-tryptophan in diet - Yan-Jun Li; Li-Li Yang; Li Ni; Jia-Min Xiong; Jia-Yuan He; Lian-Di Zhou; Ling Luo; Qi-Hui Zhang; Chun-Su Yuan (Food Chemistry, 2023)

Leopard predation on wild Sichuan snub-nosed monkeys - Bin Yang; James R. Anderson; Ni-Na Gou; Jun Luo; Bo Hong; Wei-Wei Fu; Yong-Feng Chen; Wei-Feng Wang; Bao-Jia Cao; Shi-Yu Chen; Kai-Feng Wang; Bao-Guo Li (Primates, 2023)

Oligopeptide/Histidine Transporter PHT1 and PHT2 — Function, Regulation, and Pathophysiological Implications Specifically in Immunoregulation - Minlei Dong; Ping Li; Jun Luo; Binxin Chen; Huidi Jiang (Pharmaceutical Research, 2023)

Role of sonic hedgehog signaling pathway in the regulation of ion channels: focus on its association with cardio-cerebrovascular diseases - Ming-Rui Li; Xiu-Ju Luo; Jun Peng (Journal of Physiology and Biochemistry, 2023)

Spatial redistribution and enantiomeric signatures of hexachlorocyclohexanes in Chinese forest soils: Implications to environmental behavior and influencing factors - Qian Zheng; Yue Xu; Zhen Cao; Shizhen Zhao; Haijian Bing; Jun Li; Chunling Luo; Gan Zhang (Science of The Total Environment, 2023)

Dynamic characteristic analysis of riser considering drilling pipe contact collision - Liang-jie Mao; Jie-fei Luo; Song Zeng; Jun Li; Ran Chen (Ocean Engineering, 2023)

A novel calcium peroxide/attapulgite-Fe(II) process for high concentration phosphate removal and recovery: Efficiency and mechanism - Jun Luo; Jia Peng; Zhenxing Zhong; Xuejun Long; Jiazhi Yang; Rui Li; Jun Wan (Journal of Environmental Management, 2023)

Effect of fiber surface functionalization on adsorption behavior of uranium from seawater desalination brine - Jiahui Zhu; Yinwei Luo; Junbi Liu; Qi Liu; Jing Yu; Jingyuan Liu; Rongrong Chen; Rumin Li; Jun Wang (Desalination, 2023)

Hyperbaric oxygen augments chemodynamic effect induced by probiotic-derived selenium nanoparticles to enhance cancer immune checkpoint blockade therapy - Puze Li; Yuzhu Yao; Xue Chen; Cheng Song; Meichan Wu; Jinzhao Huang; Dongdong Wang; Xuyu Li; Ban Luo; Xiangliang Yang; Jun Hu (Chemical Engineering Journal, 2023)

Elemental sulfur autotrophic partial denitrification (S0-PDN) with high pH and free ammonia control strategy for low-carbon wastewater: From performance to microbial mechanism - Yong Li; Bohan Chen; Xiaolei Zhang; Zhizhan Luo; Mengen Lei; Tao Song; Zhiyun Long; Ji Li; Jun Ma (Chemical Engineering Journal, 2023)

Alsobacter ponti sp. nov., a novel denitrification and sulfate reduction bacterium isolated from Pearl River sediment - Qi-Qi Deng; Xiao-Qing Luo; Shan-Hui Li; Jia-Ling Li; Pan-Deng Wang; Yang Yuan; Zi-Wen Yang; Wen-Jun Li (Antonie van Leeuwenhoek, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Non-contact sensing technology enables precision livestock farming in smart farms - Maosong Yin; Ruiqin Ma; Hailing Luo; Jun Li; Qinan Zhao; Mengjie Zhang (Computers and Electronics in Agriculture, 2023)

Contaminant occurrence, water quality criteria and tiered ecological risk assessment in water: A case study of antifouling biocides in the Qiantang River and its estuary, Eastern China - Hai-Wei Luo; Jian-Ming Jiang; Xun Wang; Minjie Li; Jin-Jian Ding; Wen-Jun Hong; Liang-Hong Guo (Marine Pollution Bulletin, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Degradation of indole via a two-component indole oxygenase system from Enterococcus hirae GDIAS-5 - Jun-Jin Deng; Jing-Yi Hu; Xue-ying Han; Yang Li; Xiao-Chun Luo; Zhi-Lin Wang; Jia-Zhou Li (Journal of Hazardous Materials, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Local provincialism of late Permian plant–arthropod associations in South Cathaysia: Evidence of arthropod-mediated damages in a Wuchiapingian assemblage of South China - Fu-Jun Ma; Die-Die Luo; Song Liu; Cheng-Wan Zhang; Qiu-Jun Wang; Bing-Xia Li; Chuan-Yuan Liu; Bai-Nian Sun; Xiao He (Journal of Asian Earth Sciences, 2023)

Development and characterization of walnut oleogels structured by cellulose nanofiber - Xiufen Li; Guanshui Guo; Yuxuan Zou; Jia Luo; Jun Sheng; Yang Tian; Jienan Li (Food Hydrocolloids, 2023)

Metal-organic framework-derived brain platygyra coral-like porous carbon architectures for real-time monitoring of hydrogen peroxide in biological matrices - Jun Li; Can Shen; Jiao Luo; Ti Pan; Jianlan Deng; Zhong Cao (Chemical Engineering Journal, 2023)

Hierarchical sheet-like W-doped NiCo2O4 spinel synthesized by high-valence oxyanion exchange strategy for highly efficient electrocatalytic oxygen evolution reaction - Jiabing Luo; Xingzhao Wang; Yufeng Gu; Shutao Wang; Yanpeng Li; Tingyong Wang; Yang Liu; Yan Zhou; Jun Zhang (Chemical Engineering Journal, 2023)

Highly sensitive, wide-pressure and low-frequency characterized pressure sensor based on piezoresistive-piezoelectric coupling effects in porous wood - Jingjing Luo; Feihua Liu; Ao Yin; Xue Qi; Jiang Liu; Zhongqi Ren; Shiqiang Zhou; Yuxin Wang; Yang Ye; Qingzhi Ma; Junjun Zhu; Kang Li; et al. (Carbohydrate Polymers, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Profiling Genetic Breeding Progress in Bagrid Catfishes - Lishi Huang; Guosong Zhang; Yupeng Zhang; Xinlan Li; Zhong Luo; Wenyu Liu; Fu Luo; Haifeng Liu; Shaowu Yin; Jun Jiang; Xia Liang; Quanquan Cao (Fishes, 2023)
The Bagridae fish family holds significant economic value and enjoys a high demand in the commercial market due to its desirable characteristics, such as delicious meat, fewer muscle spines, and a pleasing flavor. In recent years, the Bagridae has experienced rapid development in the seed industry in response to industry demands. Researchers have conducted extensive studies on genetic breeding in the Bagridae, employing a comprehensive breeding approach that combines conventional breeding techniques with innovative new technologies and cooperative efforts. In this review, we present an overview of the market situation and discuss various breeding processes applied to the Bagridae, including selective breeding, genetic engineering breeding, cell engineering breeding, molecular marker-assisted breeding, and hybrid breeding. Additionally, we focus on introducing the cultivation methods for two new Bagridae varieties. Furthermore, we explore and summarize the breeding conditions, genetic background, heterosis, comprehensive breeding technology, stress resistance, and metabolic nutrition of hybrid Bagridae catfishes. Overall, noticeable heterosis has been observed in the breeding of the hybrid yellow catfish “Huangyou-1”, which exhibits promising market prospects and economic benefits for aquaculture. Our study aims to underscore the importance of harnessing the heterosis of catfish, particularly the Pelteobagrus and Bagridae species. Consequently, this review provides an update on the current available information regarding the seed industry of the Bagridae fish family.

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Effects of dietary starch and metformin levels on the growth performance, body composition, hepatic glycolipid metabolism, and liver histology of juvenile largemouth bass Micropterus salmoides - Qin-Qin Liu; Ru Xia; Xin Deng; Hui-Jun Yang; Li Luo; Shi-Mei Lin; Chuan-Jie Qin; Yong-Jun Chen (Aquaculture, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Evolution effect of -CF2- group amount in hydrofluoroether on the solvation structure and high voltage cycle performance of Ether-based localized High-concentration electrolytes - Pan Luo; Jun Yang; Ying Zhang; Li Liao; Qiu Chen; Bo Yu; Bingshu Guo; Mingshan Wang; Junchen Chen; Zhiyuan Ma; Yun Huang; Jiangtao Liu; et al. (Chemical Engineering Journal, 2023)

Genome-centric polyhydroxyalkanoate reconciliation reveals nutrient enriched growth dependent biosynthesis in Bacillus cereus IBA1 - Rajat Kumar; Dongyi Li; Liwen Luo; M.K. Manu; Jun Zhao; Rajeshwar D. Tyagi; Jonathan W.C. Wong (Bioresource Technology, 2023)

ED-DQN: An event-driven deep reinforcement learning control method for multi-zone residential buildings - Qiming Fu; Zhu Li; Zhengkai Ding; Jianping Chen; Jun Luo; Yunzhe Wang; You Lu (Building and Environment, 2023)

Enhanced vitamin K2 production by engineered Bacillus subtilis during leakage fermentation - Meng-jie Zhou; Jing Wu; Liu-xiu Hu; Wen-song Hu; Jun-bao Huang; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Zheng-lian Xue; Yan Liu (World Journal of Microbiology and Biotechnology, 2023)

Enhancing biosensing with fourfold amplification and self-powering capabilities: MoS2@C hollow nanorods-mediated DNA hexahedral framework architecture for amol-level liver cancer tumor marker detection - Jinyue Shi; Weiling Qin; Yu Lin; Mingxiang Li; Yeyu Wu; Hu Luo; Jun Yan; Ke-Jing Huang; Xuecai Tan (Analytica Chimica Acta, 2023)

Long-term hypoxia and reoxygenation induced oxidative stress lead to immunosuppression and apoptosis in golden pompano (Trachinotus blochii) - Yue Gu; Jun Long Sun; Fu Cheng Yao; Tian Jiang; Chun Xiu Jin; Li Ping Shi; Shu Kui Sun; Fei Biao Song; Jian Luo (Frontiers in Marine Science, 2023)
The fluctuations of dissolved oxygen (DO) often lead to hypoxia in aquaculture, which has a huge adverse impact on fish. This study mainly investigated the effects of long-term hypoxia on oxidative stress, immune response, and cell apoptosis in the liver of golden pompano ( Trachinotus blochii ), which is not tolerant to hypoxia. So we conducted a 14 day low oxygen stress experiment on the golden pompano with a DO of 3.0 ± 0.2 mg/L, then restore the DO to normal levels and continue the 14 day reoxygenation experiment. Results showed that hypoxia and reoxygenation led to significant changes in liver structure. During hypoxia and reoxygenation, the expression of oxidative stress related genes ( SOD1 , SOD2 , GSH-Px , and CAT ) and levels of antioxidant enzymes (CAT and MDA) in the liver were increased. Liver lysozyme activity and the relative expression of the pro-inflammatory factors interleukin ( IL)-1β were significantly increased, but the expression of IL-34 was down-regulated during hypoxia. The expression of IL-12β was significantly increased during reoxygenation. The expression of anti-inflammatory factor IL -11 was decreased duringreoxygenation. The expression of toll like receptors ( TLRs ) -7, -8, and -9 increases after hypoxia and decreases after reoxygenation, indicating that both hypoxia and reoxygenation affect the immune response. In addition, during hypoxia and reoxygenation, TUNEL-positive signals increased, the bcl2/bax ratio decreased, the expression levels of caspases-3 and -8 were significantly up-regulated during hypoxia, and expression levels of caspases-9 was up-regulated during reoxygenation. In summary, hypoxia and reoxygenation can cause oxidative stress, induce inflammatory reactions, inhibit immune processes, activate apoptosis, and lead to liver damage of the golden pompano, which may be irreversible.

Association of maternal pre-pregnancy dietary intake with adverse maternal and neonatal outcomes: A systematic review and meta-analysis of prospective studies - Yunfeng Cui; Minqi Liao; Aihua Xu; Gengdong Chen; Jun Liu; Xiaoxuan Yu; Shuna Li; Xingyao Ke; Sixian Tan; Zeyan Luo; Qian Wang; Yanhua Liu; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Anthropogenic processes drive heterogeneous distributions of toxic elements in shallow groundwater around a smelting site - Lu Tang; Jie Liu; Jiaqing Zeng; Xinghua Luo; Wenshun Ke; Chuxuan Li; Wenyan Gao; Jun Jiang; Shengguo Xue (Journal of Hazardous Materials, 2023)

Inactivation of epithelial sodium ion channel molecules serves as effective diagnostic biomarkers in clear cell renal cell carcinoma - Qian Zheng; Yifang Wang; Ran Zhao; Peipei Han; Jun Zhao; Limei Li; Xiaohui Zhou; Ping Li; Yingxi Mo; Xinli Pan; Wenqi Luo; Xiaoying Zhou (Genes & Genomics, 2023)

The combined effect of seawater salinity and duration on the survival and growth of eelgrass Zostera marina - Yan-Hao Zhang; Jian-Du Li; Wen-Jie Yan; Fan-Shu Luo; Li Wang; Li-Ming Zuo; Jun-Ge Xu; Wen-Tao Li; Pei-Dong Zhang (Aquatic Botany, 2023)

Insight into iron oxychloride composite bone char for peroxymonosulfate activation: Mechanism of singlet oxygen evolution for selective degradation of organic pollutants - Yifeng Zeng; Fan Wang; Dongqin He; Jun Li; Hongwei Luo; Xiangliang Pan (Chemosphere, 2023)

New dimeric sesquiterpenoids from the whole plant of Artemisia sieversiana - Jun-yi Dong; Yu-xing Cai; Ya-lin Li; Yu-xin Zhang; Zhan-peng Yu; Ling-yi Kong; Jian-guang Luo (Phytochemistry Letters, 2023)

Source apportionment and quantitative risk assessment of heavy metals at an abandoned zinc smelting site based on GIS and PMF models - He Jin; Peng Zhihong; Zeng Jiaqing; Li Chuxuan; Tang Lu; Jiang Jun; Luo Xinghua; Gao Wenyan; Guo Junkang; Shao Binbin; Xue Shengguo (Journal of Environmental Management, 2023)

Cytoplasmic Hsp70s promote EcR transport into the nucleus by responding to various stimuli - Jun Gu; Yan Ye; Zi-Wen Zheng; Wei Luo; Yan-Jun Gong; Qi-Li Feng; Sheng Li; Li-Hua Huang (Insect Biochemistry and Molecular Biology, 2023)

Efficient removal of iron during partial neutralization of nickel laterite acid leach solution: DFT calculation and experimental verification of mechanism - Changye Mang; Guanghui Li; Yanhu Chen; Jun Luo; Mingjun Rao; Tao Jiang (Hydrometallurgy, 2023)

Src inhibition induces mitotic arrest associated with chromosomal passenger complex - Song Yang; Youguang Luo; Mulin Yang; Hua Ni; Hanxiao Yin; Ming Hu; Min Liu; Jun Zhou; Yunfan Yang; Dengwen Li (Cell and Tissue Research, 2023)

Carp stocking and climate change are potentially more important factors than nutrient enrichment driving water quality deterioration in subtropical freshwater lakes in China - Haojie Su; Jianfeng Chen; Yun Li; Qingyang Rao; Congqiang Luo; Xuwei Deng; Hong Shen; Renhui Li; Jun Chen; Yuanfeng Sun; Jiamin Pan; Suhui Ma; et al. (Limnology and Oceanography, 2023)
Freshwater lakes across the world have undergone dramatic changes in biological components and water quality over the past several decades. Previous studies focused on potential drivers mainly on nutrient enrichment in the catchment. However, the relative importance of climate change and the top‐down cascade effects of fish stocking on water quality is not fully understood. Here, by compiling 155 lakes data with four periods of field investigation in subtropical lakes in China, we found no significant changes in water total nitrogen and total phosphorus in the past two decades. However, the phytoplankton abundance increased significantly, and the water clarity declined by 44.1%. We further found that carp stocking and climate change are potentially more important than nutrients driving water quality change, which is also evidenced in two lakes (Lake Donghu and Qiandao) with long‐term monitoring histories. Specifically, carp stocking can decrease the water clarity directly by stirring up sediment and indirectly by trophic cascade along the food web. For climatic factors, mean annual temperature (MAT) has a positive effect on phytoplankton abundance, while mean annual precipitation has a negative one, with climates overall having little effect on water clarity. In addition, nutrient enrichment and climate change also have strong interactions with carp stocking, which may enhance the top‐down effects on water quality. Our findings highlight that either MAT or carp stocking may become an overwhelming driver of water clarity decline, which provides new insights into the conservation strategy for water quality management in the subtropical lakes in China.

Effects of different dietary lipid sources (perilla, fish, and soybean oils) on growth, lipid metabolism, antioxidant, and immune status in Chinese giant salamander (Andrias davidianus) - Yi-Hua Guo; Jun-Kang Ma; Hang-zhong Xu; Wei-long Li; Chang-Jiang Liu; Hua Lu; Hong Li; Xu-liang Zhai; Yang Xue; Li Luo (Frontiers in Marine Science, 2023)
Introduction Perilla oil is a natural vegetable oil rich in alpha-linolenic acid extracted from Perilla seeds. Fish oil is a commonly used animal fat containing a large amount of n-3 polyunsaturated fatty acids. Soybean oil is a commonly used vegetable oil rich in linoleic acid. This study aimed to determine whether perilla, fish, or soybean oil can be used as a lipid source in the diet of the Chinese giant salamander ( Andrias davidianus ). Methods Three isonitrogenous and isolipidic diets were created by adding 3.0% each of soybean oil (SO), fish oil (FO), and perilla seed oil (PSO). Eight adolescent giant salamanders were fed in rectangular tanks for 98 days with a total of 96 giant salamanders (mean body weight = 75.20g) and were fed an experimental diet until satiation. Results and Discussion The viscerosomatic index and crude lipid content of muscle were found to be considerably lower and the muscle crude protein was substantially higher in the PSO group than in the other groups (P<0.05). Linoleic acid levels were highest in SO, eicosapentaenoic acid and docosahexaenoic acid levels were highest in FO, and α-linolenic acid levels were highest in PSO in A. davidianus muscle tissue (P<0.05). The results of study indicate that the PSO diet can significantly increase the total antioxidative capabilities in the liver and intestine, by elevating the activities of total superoxide dismutase, carnitine transferase-1, and acetyl-CoA carboxylase in the liver. Meanwhile, the immunoglobulin M and high-density lipoprotein cholesterol levels were higher in the blood (P<0.05). Furthermore, it significantly reduced hepatic malondialdehyde, plasma endotoxin, D-lactic acid, and total cholesterol levels, and plasma alkaline phosphatase, diamine oxidase, aspartate transaminase, and alanine transaminase activities (P<0.05). Therefore, perilla, fish, and soybean oils can be used as single lipid sources for A. davidianus with respect to growth performance. On the other hand, perilla oil can enhance crude protein content of muscle, increase Immunoglobulin M(IgM) content and Alkaline phosphatase(AKP) enzyme activity, promote lipid metabolism, and maintain the health of the liver and intestine in A. davidianus .

Identification and quantification of IEPOX in ambient aerosols, using electron and chemical ionization sources GC/MS as their trimethylsilyl ethers, and using H-NMR - Li Li; Biao Chao; Wu Wang; Yina Luo; Lilin Wang; Lili Lin; Gang Yang; Jun Wu (Science of The Total Environment, 2023)

Tungsten disulfide (WS2) is a highly active co-catalyst in Fe(III)/H2O2 Fenton-like reactions for efficient acetaminophen degradation - Dongqin He; Dongli Wang; Hongwei Luo; Yifeng Zeng; Ganning Zeng; Jun Li; Xiangliang Pan (Science of The Total Environment, 2023)

Global, regional, and national burden of preterm birth attributable to ambient and household PM2.5 from 1990 to 2019: Worsening or improving? - Xiao-Xuan Liu; Shu-Jun Fan; Ya-Na Luo; Li-Xin Hu; Cong-Cong Li; Yi-Dan Zhang; Jia-Xin Li; Hui-Ling Qiu; Guang-Hui Dong; Bo-Yi Yang (Science of The Total Environment, 2023)

Whether the enhanced terrestrial vegetation carbon sink affect the water resources in the middle-low latitude karst areas of China? - Hezhen Lou; Shengtian Yang; Xuewei Shi; Jun Zhang; Zihao Pan; Chaojun Li; Yujia Zhang; Baichi Zhou; Hao Li; Yuanli Shi; Yin Yi; Ya Luo (Journal of Hydrology, 2023)

A review on mechanistic understanding of microplastic pollution on the performance of anaerobic digestion - M.K. Manu; Liwen Luo; Reeti Kumar; Davidraj Johnravindar; Dongyi Li; Sunita Varjani; Jun Zhao; Jonathan Wong (Environmental Pollution, 2023)

Versatile hybrid nanoplatforms for treating periodontitis with chemical/photothermal therapy and reactive oxygen species scavenging - Pei Wang; Lianguo Wang; Yilan Zhan; Yifan Liu; Ziqiang Chen; Jia Xu; Jun Guo; Jun Luo; Junchao Wei; Fei Tong; Zhihua Li (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Identification of DNA methylation and genetic alteration simultaneously from a single blood biopsy - Xiaomin Chen; Jiahui Liu; Jun Li; Yinpeng Xie; Zichen Yu; Lu Shen; Qingfeng Liu; Wei Wu; Qiang Zhao; Haoxiang Lin; Gaotong Liu; Qiuping Luo; et al. (Genes & Genomics, 2023)

Weathering in landslide-prone areas: Evidences from hydrochemistry and sulfur isotopic compositions in the Bailong River, northeastern Qinghai-Tibet Plateau - Han Luo; Jun Zhong; Si-Liang Li; Shuai Chen; Tingting Ma; Jianzhong Duan (Applied Geochemistry, 2023)

Effect mechanism of steel slag on CO2 capture in hydraulic lime - Kai Luo; Ke Peng; Jun Li; Zhongyuan Lu; Jun Jiang (Environmental Science and Pollution Research, 2023)

The association between multi-heavy metals exposure and lung function in a typical rural population of Northwest China - Ling Zheng; Yunhui Yu; Xiaoyu Tian; Li He; Xiaobing Shan; Jingping Niu; Jun Yan; Bin Luo (Environmental Science and Pollution Research, 2023)

Photoaging processes of polyvinyl chloride microplastics enhance the adsorption of tetracycline and facilitate the formation of antibiotic resistance - Yajun Tian; Jianyu Zhu; Chuhan Ying; Hongwei Luo; Shoufeng Zhang; Liqiu Zhang; Renna Li; Jun Li (Chemosphere, 2023)

An in vitro nerve agent brain poisoning transwell model for convenient and accurate antidote evaluation - Yao Li; Lijuan Huang; Zinan Zhang; Jingyi Huang; Huanchun Xing; Lin Wang; Xin Sui; Yuan Luo; Yongan Wang; Jun Yang (Toxicology in Vitro, 2023)

Dynamic responses of carbon metabolism of sediment microbial communities to Ag nanoparticles: Effects of the single and repeated exposure scenarios - Weiyu Li; Dan Luo; Tanveer M. Adyel; Jun Wu; Lingzhan Miao; Ming Kong; Jun Hou (Science of The Total Environment, 2023)

Methylhydroxylase encoded by mchAB gene is involved in methyl oxidation of m-cresol via Comamonas thiooxydans CHJ601 - Ni-Hong Yao; Xi Liu; Chenyang Luo; Lei Zou; Jinhua Li; Jing Chen; Dazhong Yan; Hong-Jun Chao (International Biodeterioration & Biodegradation, 2023)

The role of MAPK/NF-κB-associated microglial activation in T-2 toxin-induced mouse learning and memory impairment - Na Li; Chun-Yan Yao; Jun Diao; Xiao-Ling Liu; En-Jie Tang; Qing-Song Huang; Yu-Meng Zhou; Yue-Gu Hu; Xiu-Kuan Li; Jin-Yun Long; Hua Xiao; Da-Wei Li; et al. (Food and Chemical Toxicology, 2023)

The role of intercellular junction proteins in the penetration resistance of Drosophila larvae to avermectin - Li-Ping Chen; Han-Qing Jiang; Liang Luo; Jun Qiu; Xue-Jie Xing; Rui-Yan Hou; Yi-Jun Wu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Generating waxy rice starch with target type of amylopectin fine structure and gelatinization temperature by waxy gene editing - Yuhao Fu; Yonghuan Hua; Tingting Luo; Chunyan Liu; Baoli Zhang; Xingyu Zhang; Yiping Liu; Zizhong Zhu; Yang Tao; Zhongyan Zhu; Ping Li; Jun Zhu (Carbohydrate Polymers, 2023)

Corticostriatal Projections Relying on GABA Levels Mediate Exercise-Induced Functional Recovery in Cerebral Ischemic Mice - Ying Xing; Anjing Zhang; Congqin Li; Jing Han; Jun wang; Lu Luo; Xuechun Chang; Zhanzhuang Tian; Yulong Bai (Molecular Neurobiology, 2023)

Genome-Wide Analysis of YABBY Gene Family in Lettuce (Lactuca sativa) and Functional Characterization of LsaFILd - Kangsheng Luo; Dechun Zhang; Zhaodong Zhai; Xue Liu; Jun Zhou; Bin Zhang; Dayong Li (Journal of Plant Growth Regulation, 2023)

Genome-wide analysis of genetic pleiotropy and causal genes across three age-related ocular disorders - Xueming Yao; Hongxi Yang; Han Han; Xuejing Kou; Yuhan Jiang; Menghan Luo; Yao Zhou; Jianhua Wang; Xutong Fan; Xiaohong Wang; Mulin Jun Li; Hua Yan (Human Genetics, 2023)

Reynolds-Averaged Simulation of Drag Reduction in Viscoelastic Pipe Flow with a Fixed Mass Flow Rate - Zhuoyue Li; Haibao Hu; Peng Du; Luo Xie; Jun Wen; Xiaopeng Chen (Journal of Marine Science and Engineering, 2023)
A high molecular polymer solution with viscoelasticity has the effect of reducing frictional drag, which is quite practical for energy saving. Effective simulations of viscoelastic flows in a pipeline with a high Reynolds number is realized by incorporating the constitutive equation of viscoelasticity into the k−ε−v′2¯−f turbulence model. The Finitely Extensive Nonlinear Elastic Peterlin (FENE-P) model is employed for characterizing the viscoelasticity. The drag reduction of fully developed viscoelastic pipe flow with a fixed mass flow rate is studied. Different from increasing the center velocity and without changing the velocity near the wall at a fixed pressure drop rate, the addition of a polymer reduces the velocity near the wall and increases the velocity at the center of the pipe and makes the flow tend to be a laminar flow. Decreasing the solvent viscosity ratio or increasing the maximum extensibility or the Weissenberg number can effectively reduce the turbulence intensity and the wall friction. Under the premise of ensuring calculation accuracy, this Reynolds-averaged simulation method for viscoelastic flow has significant advantages in both computational cost and accuracy, which is promising for drag reduction simulation and practical engineering applications.

Effects of cadmium and lead co-exposure on glucocorticoid levels in rural residents of northwest China - Honglong Zhang; Jun Yan; Guole Nie; Danna Xie; Bin Luo; Jingping Niu; Haiping Wang; Xun Li (Chemosphere, 2023)

Investigation of the nephrotoxicity of 2,6-dichloro-1,4-benzoquinone disinfection by-product in mice through a 28-day toxicity test - Ting Liu; Jun Wang; Xinyue Dang; Siyu Wan; Xi Luo; Wen Tang; Haiying Du; Minghua Jin; Juan Li; Jinhua Li (Toxicology, 2023)

Leonurine improves bovine oocyte maturation and subsequent embryonic development by reducing oxidative stress and improving mitochondrial function - Lv Zheng; Yuwen Luo; Dan Zhou; Hongyu Liu; Guizhen Zhou; Lin Meng; Yunpeng Hou; Changbin Liu; Jun Li; Xiangwei Fu (Theriogenology, 2023)

Urinary concentrations of organophosphate esters in relation to semen quality: A cross-sectional study - Yaping Li; Dan Luo; Xiaoya Zhao; Han Wang; Zhiyi Zheng; Jun Liu; Chong Liu; Hui Wang; Yingjun Chen; Yinzhu Shang; Wenqing Lu; Surong Mei; et al. (Science of The Total Environment, 2023)

Single aromatics sulfonamide substituted dibenzothiazole squaraines for tumor NIR imaging and efficient photodynamic therapy at low drug dose - Jun-Hui Li; Pei-Dan You; Fei Lu; Jun-Tao Huang; Jia-Luo Fu; Hao-Yun Tang; Chun-Qiong Zhou (Journal of Photochemistry and Photobiology B: Biology, 2023)

Integrative mRNA-miRNA interaction analysis associated with the immune response of Strongylocentrotus intermedius to Vibrio harveyi infection - Pengfei Hao; Lingshu Han; Zijiao Quan; Xin Jin; Yuanxin Li; Yanglei Wu; Xianglei Zhang; Wenpei Wang; Chuang Gao; Luo Wang; Heng Wang; Weijie Zhang; et al. (Fish & Shellfish Immunology, 2023)

Inhibition of ATF4-mediated elevation of both autophagy and AKT/mTOR was involved in antitumorigenic activity of curcumin - Jie Yang; Hasenbilige; Shibo Bao; Shengxiang Luo; Liping Jiang; Qiujuan Li; Ying Kong; Jun Cao (Food and Chemical Toxicology, 2023)

Intrinsic facet-dependent electrochemical activities of BiOBr nanosheets for Br- exchange in electrochemically switched ion exchange process - Jie Wang; Liang Zhang; Yasi Hu; Xiao Du; Xiaogang Hao; Qing Cao; Guoqing Guan; Zhong Liu; Jun Li; Shanxia Luo; Xiaowei An (Chemical Engineering Journal, 2023)

Role of superoxide radical and singlet oxygen in peroxymonosulfate activation by iron-doped bone char for efficient acetaminophen degradation - Yifeng Zeng; Fan Wang; Dongqin He; Jianqiang Sun; Jun Li; Hongwei Luo; Xiangliang Pan (Chemical Engineering Journal, 2023)

Resilient silica-based aerogels with organic and inorganic molecular hybrid structure prepared by a novel self-catalyzed gelling strategy for efficient heat insulation and CO2 adsorption - Zhen Zhang; Shuang Zhao; Kunfeng Li; Zhifang Fei; Zhongyi Luo; Guobing Chen; Jun Chen; Zichun Yang (Chemical Engineering Journal, 2023)

Cinnamaldehyde affects lipid droplets metabolism after adipogenic differentiation of C2C12 cells - Yanrong Liu; Zhengqun Liu; Qiang Luo; Zhuwen Sun; Ning Li; Zi Zheng; Shuqin Mu; Xiaoqiao Zhou; Jun Yan; Chao Sun; Hongfu Zhang (Molecular Biology Reports, 2023)

The Effect of Smoking Habits on Blood Cadmium and Lead Levels in Residents Living Near a Mining and Smelting Area in Northwest China: a Cross-Sectional Study - Hui Dai; Honglong Zhang; Haiping Wang; Jingping Niu; Bin Luo; Jun Yan; Xun Li (Biological Trace Element Research, 2023)

Effects of a Dry-Mass Conserving Dynamical Core on the Simulation of Tropical Cyclones - Shaoying Li; Jun Peng; Weimin Zhang; Jianping Wu; Qiang Yao; Xiangrong Yang; Tengling Luo (Advances in Atmospheric Sciences, 2023)

DGT method for the in situ measurement of triazines and the desorption kinetics of atrazine in soil - Siheng Zheng; Feng Sheng; Cheng Gu; Yanying Li; Zhou Fang; Jun Luo (Environmental Science and Pollution Research, 2023)

Water quality criteria derivation and tiered ecological risk evaluation of antifouling biocides in marine environment - Hai-Wei Luo; Min Lin; Xin-Xin Bai; Bin Xu; Minjie Li; Jin-Jian Ding; Wen-Jun Hong; Liang-Hong Guo (Marine Pollution Bulletin, 2023)

Sodium para-aminosalicylic acid ameliorates brain neuroinflammation and behavioral deficits in juvenile lead-exposed rats by modulating MAPK signaling pathway and alpha-synuclein - Zhao-cong Li; Yue-song Zhao; Jun-jie Lin; Lei-lei Wang; Han-xiao Song; Cui-liu Gan; Xiao-wei Zheng; Shi-yan Ou; Michael Aschner; Yue-ming Jiang; Jing-jing Luo; Yan Li (Toxicology Letters, 2023)

Autophagy induces mTOR-dependent glucose uptake and mTOR-independent lactate utilization in cadmium-treated A549 cells - Shibo Bao; Cong Zhang; Shengxiang Luo; Liping Jiang; Qiujuan Li; Ying Kong; Jun Cao (Toxicology in Vitro, 2023)

High maternal glucose exacerbates the association between prenatal per- and polyfluoroalkyl substance exposure and reduced birth weight - Zixia Wang; Jiajun Luo; Yan Zhang; Jiong Li; Jun Zhang; Ying Tian; Yu Gao (Science of The Total Environment, 2023)

Surprising leopard restoration in fragmented ecosystems reveals connections as the secret to conservation success - Fu Yanwen; Zhao Guojing; Dai Wenqian; Wang Yue; Li Jiawei; Tan Mengyu; Li Yan; Liu Haoran; Xie Bing; Jin Xiao; Fan Enyu; Zhao Lulu; et al. (Science of The Total Environment, 2023)

Recent advances in microbial mercury methylation: A review on methylation habitat, methylator, mechanism, and influencing factor - Hongwei Luo; Qianqian Cheng; Dongqin He; Jianqiang Sun; Jun Li; Xiangliang Pan (Process Safety and Environmental Protection, 2023)

Investigation of the mechanisms and sensitivity of wellbore breathing effects during drilling in deepwater shallow formations - Honglin Huang; Jun Li; Reyu Gao; Geng Zhang; Hongwei Yang; Wang Chen; Ming Luo; Wentuo Li (Ocean Engineering, 2023)

Reconstruction of the water cycle process reveals the 600-year evolution of the human-water relationship in Tunpu, China - Shengtian Yang; Zihao Pan; Hezhen Lou; Chaojun Li; Jun Zhang; Yujia Zhang; Yin Yi; Jiyi Gong; Ya Luo; Min Zhi; Xi Li (Journal of Hydrology, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Photo-thermal catalytic pyrolysis of waste plastics: Investigation into light-induced metal-support interaction - Haiping Yang; Shuai Yan; Dingding Yao; Hao Luo; Kuo Zeng; Jun Li; Dian Zhong; Haoyu Xiao; Hanping Chen (Fuel, 2023)

Nonlinear rheological behavior and quantitative proteomic analysis of pea protein isolates at the air-water interface - Qian Shen; Yilun Luo; Wei Zheng; Ting Xiong; Fei Han; Jingnan Zuo; Jun Dai; Bin Li; Yijie Chen (Food Hydrocolloids, 2023)

The inhibitory mechanism of pentacyclic triterpenoid acids on pancreatic lipase and cholesterol esterase - Heyu Shen; Jun Wang; Jingfang Ao; Lixia Ye; Yubing Shi; Yujie Liu; Mengyang Li; Anwei Luo (Food Bioscience, 2023)

Effects of fine ambient particulate matters on de novo hypertensive disorders of pregnancy and blood pressure before 20 weeks - Zhichao Yuan; Qin Li; Tao Su; Jie Yang; Junjun Chen; Yuanzhou Peng; Shuang Zhou; Heling Bao; Shusheng Luo; Hui Wang; Jue Liu; Na Han; et al. (Environmental Research, 2023)

Highly efficient shrimp shell recovery by solid-state fermentation with Streptomyces sp. SCUT-3 - De-Lin Lu; Ming-Shu Zhang; Jun-Jin Deng; Wen-Jun Lu; Zhen-Dong Yang; Zhi-Wei Li; Yu-Chen Chen; Xiao-Chun Luo (Chemical Engineering Journal, 2023)

Regulating the charge densities of s-Block calcium single-atom site catalysts for efficient N2 activation and reduction - Tianyong Liu; Xiaoyang Qu; Yuqin Zhang; Xiaohang Wang; Qian Dang; Xingxing Li; Binju Wang; Shaobin Tang; Yi Luo; Jun Jiang (Chemical Engineering Journal, 2023)

DNAzymes-conjugated upconversion nanoamplicon for in-situ ultrasensitive detection and imaging of microRNA in vivo - Yi Zhang; Da Luo; Yin Zhang; Qi-Hai Zhang; Qing-Yuan Ji; Shi-Kang Zhou; Shan Huang; Li-li Li; Feng Lu; Wei-Feng Yao; Fang-Fang Cheng; Jun-Jie Zhu; et al. (Chemical Engineering Journal, 2023)

Engineered celastrol and plasmid co-delivery for in situ expression and targeted mitochondrial relocation of Nur77 protein towards effective drug resistance reversion - Minting Liu; Zheng Luo; Zhiguo Li; Xiyu Lai; Xian Jun Loh; Caisheng Wu; Zibiao Li; Yun-Long Wu (Chemical Engineering Journal, 2023)

Highly efficient polyhydroxyalkanoate production from lignin using genetically engineered Halomonas sp. Y3 - Yuan-Qiu Li; Ming-Jun Wang; Chao-Bing Luo (Bioresource Technology, 2023)

Micropyrones A and B, two new α -pyrones from the actinomycete Microbacterium sp. GJ312 isolated from Glycyrrhiza uralensis Fisch - Ying-Ting Xu; Yu-Cai Luo; Jing-Hua Xue; Yu-Ping Li; Lei Dong; Wen-Jun Li; Zhong-Yu Zhou; Xiao-Yi Wei (Natural Product Research, 2023)

Correction to: Biochars regulate bacterial community and their putative functions in the charosphere: a mesh‑bag field study - Jun Meng; Yan Li; Yingbo Qiu; Yu Luo; Yunying Fang; Lukas Van Zwieten; Hailong Wang; Huaihai Chen (Journal of Soils and Sediments, 2023)

Biochars regulate bacterial community and their putative functions in the charosphere: a mesh-bag field study - Jun Meng; Yan Li; Yingbo Qiu; Yu Luo; Yunying Fang; Lukas Van Zwieten; Hailong Wang; Huaihai Chen (Journal of Soils and Sediments, 2023)

Remote sensing inversion and prediction of land use land cover in the middle reaches of the Yangtze River basin, China - Shengqing Zhang; Peng Yang; Jun Xia; Wenyu Wang; Wei Cai; Nengcheng Chen; Sheng Hu; Xiangang Luo; Jiang Li; Chesheng Zhan (Environmental Science and Pollution Research, 2023)

H3K4me3 as a target of di(2-ethylhexyl) phthalate (DEHP) impairing primordial follicle assembly - Ming-Hao Li; Jun-Jie Wang; Yan-Qin Feng; Xuan Liu; Zi-Hui Yan; Xiao-Jun Zhang; Ya-Xin Wen; Hao-Wei Luo; Lan Li; Massimo De Felici; Ai-Hong Zhao; Wei Shen (Chemosphere, 2023)

Hypoxia alters glucose and lipid metabolisms in golden pompano (Trachinotus blochii) - Tian Jiang; Jun Long Sun; Yue Gu; Fu Cheng Yao; Ye Song Liang; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Li Zhou; Zhong Wei Wang; Jian Fang Gui; Jian Luo (Aquaculture, 2023)

Short-term morphological evolution of an ephemeral gully in the Dry-hot Valley of Southwest China - Lei Wang; Jilin Zheng; Bin Zhang; Wu Li; Jun Luo; Zhengping Du; Qingchun Deng; Hui Liu (Soil and Tillage Research, 2023)

Transcription factor NtWRKY33a modulates the biosynthesis of polyphenols by targeting NtMYB4 and NtHCT genes in tobacco - Zhong Wang; Lanxin Ma; Pingping Liu; Zhaopeng Luo; Zefeng Li; Mingzhu Wu; Xin Xu; Wenxuan Pu; Pingjun Huang; Jun Yang (Plant Science, 2023)

Early Paleozoic collision-related structures in the Tarim Craton, NW China: Implications for the Proto-Tethys evolution - Yue-Jun Li; Yong-Jin Gao; Hui Zhou; Guang-Ya Zhang; Lei Wen; Yan Zhao; Cheng Li; Duo-Ming Zheng; Ya-Lei Liu; Hong-Hui Li; Cai-Ming Luo; Tong-Fei Huang; et al. (Journal of Asian Earth Sciences, 2023)

Mixed heavy metals exposure affects the renal function mediated by 8-OHG: A cross-sectional study in rural residents of China - Xiaoyu Tian; Xiaobing Shan; Li Ma; Chenyang Zhang; Mei Wang; Jie Zheng; Ruoyi Lei; Li He; Jun Yan; Xun Li; Yanjun Bai; Keqin Hu; et al. (Environmental Pollution, 2023)

Constructing anti-scaling and anti-wetting polyvinyl alcohol layers through spray-coating with improved water permeability in membrane distillation - Wei Cheng; Peizhi Wang; Xiaolei Zhang; Ji Li; Yiwen Luo; Wenjuan Zhang; Jun Ma; Tao Zhang (Desalination, 2023)

Manipulating Ga growth profile enables all-flexible high-performance single-junction CIGS and 4 T perovskite/CIGS tandem solar cells - Jun Luo; Liting Tang; Shijin Wang; Hui Yan; Wuji Wang; Zheng Chi; Junbo Gong; Jianmin Li; Xudong Xiao (Chemical Engineering Journal, 2023)

Island-like CeO2 decorated LiMn2O4: Surface modification enhancing electrochemical lithium extraction and cycle performance - Guiling Luo; Xiaowei Li; Linlin Chen; Yuning Zhang; Jun Gu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu; Chunming Xu (Chemical Engineering Journal, 2023)

Cleaner 2,3-butanediol production from unpretreated lignocellulosic biomass by a newly isolated Klebsiella pneumoniae PX14 - Yuan-Qiu Li; Ming-Jun Wang; Xiao-Feng Gan; Chao-Bing Luo (Chemical Engineering Journal, 2023)

Chitosan based photothermal scaffold fighting against bone tumor-related complications: Recurrence, infection, and defects - Yao Zhao; Xu Peng; Xiaoyang Xu; Mingzhen Wu; Fan Sun; Qiangwei Xin; Hongbo Zhang; Liangrui Zuo; Yilin Cao; Yuhang Xia; Jun Luo; Chunmei Ding; et al. (Carbohydrate Polymers, 2023)

ER stress-enhanced HMGA2 plays an important role in Cr (VI)-induced glycolysis and inhibited oxidative phosphorylation by targeting the transcription of ATF4 - Shengxiang Luo; Cong Zhang; Zeyun Gao; Liping Jiang; Qiujuan Li; Xiaoxia Shi; Ying Kong; Jun Cao (Chemico-Biological Interactions, 2023)

Optimized Cationic Lipid-assisted Nanoparticle for Delivering CpG Oligodeoxynucleotides to Treat Hepatitis B Virus Infection - Yi-Fang Chen; Yan Wang; Yue Wang; Ying-Li Luo; Zi-Dong Lu; Xiao-Jiao Du; Cong-Fei Xu; Jun Wang (Pharmaceutical Research, 2023)

Seed Priming with Gibberellin Regulates the Germination of Cotton Seeds Under Low-Temperature Conditions - Jun Xia; Xianzhe Hao; Tangang Wang; Huiqin Li; Xiaojuan Shi; Yongchang Liu; Honghai Luo (Journal of Plant Growth Regulation, 2023)

Dynamic Effective Porosity Explains Laboratory Experiments on Watertable Fluctuations in Coastal Unconfined Aquifers - Zhaoyang Luo; Jun Kong; Lili Yao; Chunhui Lu; Ling Li; D.A. Barry (Advances in Water Resources, 2023)

A new insight into the emission source of DDT in indoor environment from rural area of South China and comprehensive human health exposure assessment - Yin-Zhi Lv; Xiao-Jun Luo; Qi-Qi Li; Yan Yang; Yan-Hong Zeng; Bi-Xian Mai (Environmental Science and Pollution Research, 2022)

Talaromyces marneffei Infections in 8 Chinese Children with Inborn Errors of Immunity - Linlin Wang; Ying Luo; Xiaolin Li; Yixian Li; Yu Xia; Tingyan He; Yanyan Huang; Yongbin Xu; Zhi Yang; Jiayun Ling; Ruohang Weng; Xiaona Zhu; et al. (Mycopathologia, 2022)
Purpose Talaromyces marneffei (TM) is an opportunistic fungus leading to multi-organ damages and poor prognosis in immunocompromised individuals. TM infections in children are rare and our knowledge to TM infection is insufficient. To investigate the clinical characteristics of TM-infected children and to explore the underlying mechanisms for host against TM, we analysed TM-infected patients diagnosed in our hospital. Methods Eight patients with TM infections have been identified in Shenzhen Children’s Hospital during 2017–2021. Clinical data were collected from medical records. Immunological features were evaluated by flow cytometry. Literatures were also reviewed to summarize the reported inborn errors of immunity (IEIs) with TM infections. Results All 8 children were HIV-negative. The most common symptom of TM infections was fever (8/8), followed by weight loss (7/8), pneumonia (7/8), hepatomegaly (7/8), splenomegaly (6/8), anemia (6/8), lymphadenopathy (5/8), thrombocytopenia (3/8), diarrhea (3/8), rashes or skin lesions (3/8), and osteolytic lesions (1/8). Five children died during the follow-ups. CD3+ T cells were decreased in 6 patients. Eight patients had reduced natural killer cells. All patients went gene sequencing and were finally diagnosed as IEIs, including STAT1 gain-of-function, IL-2 receptor common gamma chain deficiency, adenosine deaminase deficiency, CD40 ligand deficiency, and STAT3 deficiency. Another 4 types of IEIs (CARD9, IFN- γ receptor 1, RelB, and NFKB2 deficiency), have been reported with TM infections based on literature review. Conclusion TM infections resulted in systemic injuries and high mortality. The spectrum of IEIs underlying TM infections indicated that T cell-mediated immunity, IFN- γ , IL-17 signalings and NF-κB pathways were important for host responses against TM infection. In reverse, for HIV-negative children without other secondary immunodeficiencies, IEIs should be considered in TM-infected children.

Globular adiponectin-mediated vascular remodeling by affecting the secretion of adventitial-derived tumor necrosis factor-α induced by urotensin II - Jun Li; Limin Luo; Yonggang Zhang; Xiao Dong; Shuyi Dang; Xiaogang Guo; Wenhui Ding (Journal of Zhejiang University-SCIENCE B, 2022)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

CAF-derived midkine promotes EMT and cisplatin resistance by upregulating lncRNA ST7-AS1 in gastric cancer - Ke-Da Yang; Ying Wang; Fan Zhang; Qing-Ling Li; Bai-Hua Luo; De-Yun Feng; Zhi-Jun Zeng (Molecular and Cellular Biochemistry, 2022)

Effects of lead and cadmium co-exposure on liver function in residents near a mining and smelting area in northwestern China - Jun Yan; Honglong Zhang; Jingping Niu; Bin Luo; Haiping Wang; Meng Tian; Xun Li (Environmental Geochemistry and Health, 2022)

Quantitative microbial risk assessment with nasal/oral breathing pattern for S. aureus bioaerosol emission from aeration tanks and residual sludge storage yard in a wastewater treatment plant - Cheng Yan; Xiao-yan Zhao; Xi Luo; Dong-zi An; Hao Zhu; Ming Li; Xiao-jun Ai; Wajid Ali (Environmental Science and Pollution Research, 2022)

Sexual size dimorphism in golden pompano (Trachinotus blochii): Potential roles of changes in energy allocation and differences in muscle metabolism - Jun Long Sun; Fei Biao Song; Lei Wang; Wei Wei Zhang; You Ming Chen; Li Zhou; Jian Fang Gui; Jian Luo (Frontiers in Marine Science, 2022)
Golden pompano ( Trachinotus blochii ) is becoming increasingly popular and produces high yields, but the growth differences between males and females are a concern. In this study, the differences between the growth of males and females were compared, and the transcriptome analysis of muscle tissues was performed. A significant difference between the growth of males and females was observed; females were found to be 17% larger than males after reaching 7 months of age. Gonadal histological analysis revealed that the ovaries were arrested in 7- to 9-month-old golden pompano, whereas the testes continued to develop. The AMPK and adipocytokine signaling pathways were also found to be involved in the regulation of muscle growth and metabolism. After reaching 7 months of age, the expression levels of glut1 , glut4 , ldh , gys, acsl and cpt2 in the muscle of females were lower than those in males, but the hk gene, which is involved in glycolysis, was found to remain highly expressed in females. Additionally, in females, the synthesis of arginine and ornithine and the production of carnosine were found to be inhibited, but the breakdown of glutamine was found to be enhanced and OXPHOS ability was found to be stronger in females after reaching 7 months of age. These results support a certain negative correlation between gonadal development and muscle metabolism depending on differences in energy distribution. Clearly, the faster growth in females after reaching 7 months of age was found to be associated with the more active metabolism of glucose, and amino acids, as well as stronger oxidative phosphorylation levels.

Assessing the Impact of Atrazine on the Availability of Arsenic in Soils Using DGT Technique - Yanying Li; Liying Yan; Qiuyu Rong; Jun Luo; Hao Zhang; Kevin C. Jones (Bulletin of Environmental Contamination and Toxicology, 2022)

Transcriptome analysis and co‐expression network reveal the mechanism linking mitochondrial function to immune regulation in red crucian carp ( Carassius auratus red var) after Aeromonas hydrophila challenge - Ning‐Xia Xiong; Xu‐Ying Kuang; Zi‐Xuan Fang; Jie Ou; Shi‐Yun Li; Jia‐Hui Zhao; Jin‐Fang Huang; Ke‐Xin Li; Rou Wang; Lan‐Fen Fan; Sheng‐Wei Luo; Shao‐Jun Liu (Journal of Fish Diseases, 2022)
Aeromonas hydrophila is a common pathogen of freshwater fish. In this study, A. hydrophila infection was shown to cause tissue damage, trigger physiological changes as well as alter the expression profiles of immune‐ and metabolic‐related genes in immune tissues of red crucian carp (RCC). Transcriptome analysis revealed that acute A. hydrophila infection exerted a profound effect on mitochondrial oxidative phosphorylation linking metabolic regulation to immune response. In addition, we further identified cellular senescence, apoptosis, necrosis and mitogen‐activated protein kinase signal pathways as crucial signal pathways in the kidney of RCC subjected to A. hydrophila infection. These findings may have important implications for understanding modulation of immunometabolic response to bacterial infection.

Corrigendum: Sea urchins in acute high temperature and low oxygen environments: The regulatory role of microRNAs in response to environmental stress - Lingshu Han; Yanglei Wu; Pengfei Hao; Beichen Ding; Yuanxin Li; Wenpei Wang; Xianglei Zhang; Chuang Gao; Heng Wang; Luo Wang; Weijie Zhang; Yaqing Chang; et al. (Frontiers in Marine Science, 2022)

Toward improvements for enhancement the productivity and color value of Monascus pigments: a critical review with recent updates - JinTao He; MingXi Jia; Wen Li; Jing Deng; JiaLi Ren; FeiJun Luo; Jie Bai; Jun Liu (Critical Reviews in Food Science and Nutrition, 2022)

The Effects of Lead and Cadmium Co-exposure on Serum Ions in Residents Living Near a Mining and Smelting Area in Northwest China - Qian Luo; Honglong Zhang; Haiping Wang; Li Ma; Min Huang; Jingping Niu; Bin Luo; Jun Yan; Xun Li (Biological Trace Element Research, 2022)

Quick mapping and characterization of a co-located kernel length and thousand-kernel weight-related QTL in wheat - Xiangru Qu; Cong Li; Hang Liu; Jiajun Liu; Wei Luo; Qiang Xu; Huaping Tang; Yang Mu; Mei Deng; Zhien Pu; Jun Ma; Qiantao Jiang; et al. (Theoretical and Applied Genetics, 2022)

Heroin Addiction Induces Axonal Transport Dysfunction in the Brain Detected by In Vivo MRI - Yueyuan Luo; Chengde Liao; Long Chen; Yongjin Zhang; Shasha Bao; Ailin Deng; Tengfei Ke; Qinqing Li; Jun Yang (Neurotoxicity Research, 2022)

Effects of climate change on major elements of the hydrological cycle in Aksu River basin, northwest China - Peng Yang; Wenyu Wang; Jun Xia; Yaning Chen; Chesheng Zhan; Shengqing Zhang; Cai Wei; Xiangang Luo; Jiang Li (International Journal of Climatology, 2022)
Water resources systems in arid regions are sensitive to climate change, which critically impacts the water cycle. In this study, we applied historical hydrometeorological data, CMIP5 data, and a large‐scale hydrological model (Community Land Model–Distributed Time‐Variant Gain Model [CLM–DTVGM]) to study the impact of climate change on the hydrological cycle (i.e., runoff, actual evapotranspiration (ET a ), and terrestrial water storage [TWS]) under different scenarios at the Aksu River basin (ARB) located in the arid region of northwest China. The primary findings of this study: (a) As the determination coefficient ( R 2 ) and Nash–Sutcliffe efficiency coefficient (NSE) reached desirable levels ( R 2 ≥ 0.583, NSE ≥ 0.371, and root‐mean‐square error ≤ 155.727), the CLM–DTVGM achieved a better simulation of runoff in the ARB; under climate change, the runoff depth in the irrigation area became shallower and followed a decreasing trend, with a minimum depth of 0.5 mm and a significant decreasing trend of −8 mm·a −1 . (b) Along with changes in the precipitation and temperature of the baseline period (i.e., 1980–2010), runoff, ET a , and TWS were predicted to change significantly in future scenarios. (c) Climate change significantly impacted the historical runoff from the Shaliguilanke and Xiehela hydrological stations, with correlation coefficients larger than 0.9; however, the runoff from the Alaer hydrological station was not affected. However, runoff, ET a , and TWS in the ARB were very closely correlated with climate change in the future scenarios, with correlation coefficients exceeding 0.9. Related research in the future would be important for guiding the sustainable development of the ARB.

Improving protected area effectiveness through consideration of different human‐pressure baselines - Chun‐Ting Feng; Ming Cao; Fang‐Zheng Liu; Yue Zhou; Jin‐Hong Du; Li‐Bo Zhang; Wen‐Jie Huang; Jian‐Wu Luo; Jun‐Sheng Li; Wei Wang (Conservation Biology, 2022)
Previous assessments of the effectiveness of protected areas (PAs) focused primarily on changes in human pressure over time and did not consider the different human‐pressure baselines of PAs, thereby potentially over‐ or underestimating PA effectiveness. We developed a framework that considers both human‐pressure baseline and change in human pressure over time and assessed the effectiveness of 338 PAs in China from 2010 to 2020. The initial state of human pressure on PAs was taken as the baseline, and changes in human pressure index (HPI) were further analyzed under different baselines. We used the random forest models to identify the management measures that most improved effectiveness in resisting human pressure for the PAs with different baselines. Finally, the relationships between the changes in the HPI and the changes in natural ecosystems in PAs were analyzed with different baselines. Of PAs with low HPI baselines, medium HPI baselines, and high HPI baselines, 76.92% ( n =150), 11.11% ( n =12), and 22.86% ( n =8) , respectively, showed positive effects in resisting human pressure. Overall, ignoring human‐pressure baselines somewhat underestimated the positive effects of PAs, especially for those with low initial human pressure. For PAs with different initial human pressures, different management measures should be taken to improve effectiveness and reduce threats to natural ecosystems. We believe our framework is useful for assessing the effectiveness of PAs globally, and we recommend it be included in the Convention on Biological Diversity Post‐2020 Strategy.

Transition metal ions-modified birnessite toward highly efficiency photocatalytic formaldehyde oxidation under visible light irradiation - Changye Mang; Guanghui Li; Mingjun Rao; Xin Zhang; Jun Luo; Tao Jiang (Environmental Science and Pollution Research, 2022)

Rhodoflexus caldus gen. nov., sp. nov., a new member of the phylum Bacteroidota isolated from a hot spring sediment - Ze-Tao Liu; Lan Liu; Wen-Dong Xian; Zheng-Han Lian; Jun-Yi Dai; Bao-Zhu Fang; Meng-Meng Li; Ai-Ping Lv; Zhen-Hao Luo; Jian-Yu Jiao; Wen-Jun Li (Antonie van Leeuwenhoek, 2022)

Sea Urchins in Acute High Temperature and Low Oxygen Environments: The Regulatory Role of microRNAs in Response to Environmental Stress - Lingshu Han; Yanglei Wu; Pengfei Hao; Beichen Ding; Yuanxin Li; Wenpei Wang; Xianglei Zhang; Chuang Gao; Heng Wang; Luo Wang; Weijie Zhang; Yaqing Chang; et al. (Frontiers in Marine Science, 2022)
Strongylocentrotus intermedius is an economically valuable sea urchin species in China. However, its growth and survival are severely constrained by ocean warming and the hypoxia that often accompanies high water temperatures. MicroRNAs (miRNAs) are important regulators of gene expression in response to environmental change. In this study, high-throughput RNA sequencing was used to investigate changes in miRNA expression in S. intermedius under heat (25°C), hypoxia (2 mg/L O 2 ), and combined heat and hypoxia stresses. Twelve small RNAs libraries were constructed and 17, 14, and 23 differentially expressed miRNAs (DEMs) were identified in the heat, hypoxia, and combined stress groups ( P <0.05), respectively. Gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway functional analyses of putative target genes of the DEMs suggested that these miRNAs were important in basal metabolism, apoptosis, oxidative stress, and immune-related pathways. By co-analysis with published transcriptome data, key DEMs (miR-193, miR-184, miR-133, miR-125, miR-2008) and their key target genes ( EGF3 , ABCB4 , CYCL , PAN2 , CALN ) were identified. Quantitative real-time PCR analysis of the expression of 10 DEMs and their key target genes confirmed the RNA sequencing results. These results provide information on gene expression regulation of the molecular mechanisms underlying the response of S. intermedius to multi-cause environmental stresses.

Natural products for infectious microbes and diseases: an overview of sources, compounds, and chemical diversities - Lu Luo; Jun Yang; Cheng Wang; Jie Wu; Yafang Li; Xu Zhang; Hui Li; Hui Zhang; Yumei Zhou; Aiping Lu; Shilin Chen (Science China Life Sciences, 2022)

Ligustilide ameliorates cognitive impairment via AMPK/SIRT1 pathway in vascular dementia rat - Dong Peng; Han-Zi Qiao; Hong-Yu Tan; Yi-Xue Wang; Dan Luo; Li-Jun Qiao; Ye-Feng Cai; Shi-Jie Zhang; Qi Wang; Li Guan (Metabolic Brain Disease, 2022)

Alternate freezing and thawing enhanced the sediment and nutrient runoff loss in the restored soil of the alpine mining area - Fa-Yong Li; Ren-jie Luo; Yong-jun You; Xue-fei Hu; Xiao-yan Qian; Peng-yan Zhang; Shan Wang; Guo-yu Li; Mohamed Eltohamy Kamel (Journal of Mountain Science, 2022)

The Impact of Urban Expansion on Plant Diversity Change in Karst Regions of Southwest China - Shengtian Yang; Chaojun Li; Hezhen Lou; Ya Luo; Pengfei Wang; Jun Zhang; Xi Li; Xijin Wu (Chinese Geographical Science, 2022)

Numerical simulation and cause analysis of persistent summer drought during the 1920s in eastern China - Meng Luo; Jinming Feng; Zhongfeng Xu; Jun Wang; Li Dan (Science China Earth Sciences, 2022)

Validation and Assessment of Diffusive Gradients in Thin-Films (DGT) Technique for Measuring Nutrients in Taihu Lake Water with Algae Bloom - Danxing Yang; Haiyi Chen; Haitao Sun; Jun Luo; Yanying Li (Bulletin of Environmental Contamination and Toxicology, 2022)

Chromosome-Scale Assembly and Characterization of the Albino Northern Snakehead, Channa argus var. (Teleostei: Channidae) Genome - Chaowei Zhou; Yan Li; Yan Zhou; Yu Zou; Dengyue Yuan; Xingxing Deng; Luo Lei; Jian Su; Chengke Zhu; Hua Ye; Hui Luo; Guangjun Lv; et al. (Frontiers in Marine Science, 2022)
Northern snakehead, Channa argus ( C. argus ), is an important economic and ecological fish species. The wild population of the species was sharply declined in the last decade. A high-quality reference genome could lay a solid foundation for the genetic and conservation studies for C. argus . In this work, we report a chromosomal genome assembly with PacBio and Hi-C technology using the albino northern snakehead, a color variety of C. argus . A 644.1-Mb genome with 24 chromosomes was obtained with a contig and scaffold N50 of 11.78 and 27.8 Mb, respectively. We inferred that C. argus diverged from A. testudineus around 85.6 million years ago. 514 expanded gene families and 214 positively selected genes were identified in the C. argus genome. The chromosome-level genome provides a valuable high-quality genomic resource for population, as well as genetic and evolutionary studies for C. argus and other species in Channidae.

A soil-borne Mn(II)-oxidizing bacterium of Providencia sp. exploits a strategy of superoxide production coupled to hydrogen peroxide consumption to generate Mn oxides - Sha Chen; Zhexu Ding; Jinyuan Chen; Jun Luo; Xiaofang Ruan; Zongpei Li; Fengfeng Liao; Jing He; Ding Li (Archives of Microbiology, 2022)

Dysfunction of FadA‐cAMP signalling decreases Aspergillus flavus resistance to antimicrobial natural preservative Perillaldehyde and AFB1 biosynthesis - Kunlong Yang; Qingru Geng; Yue Luo; Rui Xie; Tongzheng Sun; Zhen Wang; Ling Qin; Wei Zhao; Man Liu; Yongxin Li; Jun Tian (Environmental Microbiology, 2022)
Summary Aspergillus flavus is an opportunistic fungal pathogen that colonizes agriculture crops with aflatoxin contamination. We found that Perillaldehyde (PAE) effectively inhibited A . flavus viability and aflatoxin production by inducing excess reactive oxygen species (ROS). Transcriptome analysis indicated that the Gα protein FadA was significantly induced by PAE. Functional characterization of FadA showed it is important for asexual development and aflatoxin biosynthesis by regulation of cAMP‐PKA signalling. The Δ fadA mutant was more sensitive to PAE, while Δ pdeL and Δ pdeH mutants can tolerate excess PAE compared to wild‐type A . flavus . Further RNA‐sequence analysis showed that fadA was important for expression of genes involved in oxidation–reduction and cellular metabolism. The flow cytometry and fluorescence microscopy demonstrated that Δ fadA accumulated more concentration of ROS in cells, and the transcriptome data indicated that genes involved in ROS scavenging were downregulated in Δ fadA mutant. We further found that FadA participated in regulating response to extracellular environmental stresses by increasing phosphorylation levels of MAPK Kinase Slt2 and Hog1. Overall, our results indicated that FadA signalling engages in mycotoxin production and A . flavus resistance to antimicrobial PAE, which provide valuable information for controlling this fungus and AF biosynthesis in pre‐ and postharvest of agricultural crops.

Upregulation of h-TERT and Ki-67 in ectopic endometrium is associated with recurrence of endometriosis - Jie Luo; Zhimin Song; Tao Zhang; Ketan Chu; Jingyi Li; Jianhong Zhou; Jun Lin (Journal of Zhejiang University-SCIENCE B, 2022)

Does the institutional environment influence corporate social responsibility? Consideration of green investment of enterprises—evidence from China - Shu-Rong Han; Pei Li; Jian-Jun Xiang; Xiang-Hua Luo; Chun-Yan Chen (Environmental Science and Pollution Research, 2022)

The specialized mitotic behavior of human embryonic stem cells - Rui Lyu; Xuemei Wu; Nan Ma; Difei Wang; Shuang Sun; Youguang Luo; Jun Zhou; Xinyi Lu; Min Liu; Dengwen Li (Cell and Tissue Research, 2022)

Deinococcus aestuarii sp. nov. and Deinococcus aquaedulcis sp. nov., two novel resistant bacteria isolated from pearl river estuary - Ling-Zi Yin; Jia-Ling Li; Ze-Tao Liu; Bao-Zhu Fang; Pandeng Wang; Xiao-Qing Luo; Lei Dong; Li Duan; Shan-Hui Li; Wen-Jun Li (Antonie van Leeuwenhoek, 2022)

Maternal intake of caffeinated products and birth defects: a systematic review and meta-analysis of observational studies - Yan Yue; Wenxing Li; Jun Tang; Yan Zeng; Tao Xiong; Xia Qiu; Jing Shi; Hua Wang; Bin Xia; Lili Luo; Yi Qu; Dezhi Mu (Critical Reviews in Food Science and Nutrition, 2021)

LCZ696 Possesses a Protective Effect Against Homocysteine (Hcy)-Induced Impairment of Blood–Brain Barrier (BBB) Integrity by Increasing Occludin, Mediated by the Inhibition of Egr-1 - Wenfeng Li; Wenjin Yuan; Dandan Zhang; Shuchun Cai; Jun Luo; Kanghua Zeng (Neurotoxicity Research, 2021)

Assessment of probiotic adhesion and inhibitory effect on Escherichia coli and Salmonella adhesion - Ya Wang; Dan Jia; Jia-hui Wang; He-hai Li; Jun-long Liu; Ai-hong Liu; Jin-ming Wang; Gui-quan Guan; Jian-xun Luo; Hong Yin; You-quan Li (Archives of Microbiology, 2021)

Association of myostatin deficiency with collagen related disease-umbilical hernia and tippy toe standing in pigs - Hyo-Jin Paek; Zhao-Bo Luo; Hak-Myong Choe; Biao-Hu Quan; Kai Gao; Sheng-Zhong Han; Zhou-Yan Li; Jin-Dan Kang; Xi-Jun Yin (Transgenic Research, 2021)

Autophagy induced by H. pylori VacA regulated the survival mechanism of the SGC7901 human gastric cancer cell line - Juan Luo; Luyan Bai; Jun Tao; Yu Wen; Mingke Li; Yunzhen Zhu; Sufeng Luo; Guangyu Pu; Lanqing Ma (Genes & Genomics, 2021)
Background Vacuolating cytotoxin (VacA) is an important virulence factor of Helicobacter pylori ( H. pylori ). It was previously believed that VacA can trigger the cascade of apoptosis on mitochondria to lead to cell apoptosis. Recently, it was found that VacA can induce autophagy. However, the molecular mechanism by which VacA induces autophagy is largely unknown. Objective We aimed to explore the molecular mechanism of autophagy induced by H. pylori in gastric cancer cells and the effect of autophagy on the survival of gastric cancer cells. Methods The autophagy of human gastric cancer cell line SGC7901 was detected by Western blot and RT-PCR in the treatment of VacA protein of H. pylori . The relationship between autophagy and reactive oxygen species (ROS) in the proliferation of gastric cancer cells were studied by gene expression silences (siRNA) and CM-H2DCFDA (DCF) staining. Results The results showed that VacA protein secreted by H. pylori in the supernatant stimulated autophagy in SGC7901 cells. After VacA protein treatment, the mRNA expressions of BECN1, ATG7 and PIK3C3, were up-regulated. ATG7 silencing by siRNA inhibited VacA-induced autophagy. Furthermore, our data demonstrated that VacA protein increased ROS levels. Addition of the antioxidant N -acetyl- l -cysteine (NAC) suppressed the levels of ROS, leading to inhibition of autophagy. Conclusions H. pylori VacA is a key toxin that induces autophagy by increased ROS levels. And our findings demonstrated that VacA significantly inhibited proliferation in SGC7901 cells.

Sandaracinobacteroides hominis gen. nov., sp. nov., isolated from human skin - Ping-Hua Qu; Hai-Min Luo; Jun-Hui Feng; Song Li; Cha Chen; Lei Dong; Yu-Zhen Ming; Wen-Jun Li; Ying Lin (Archives of Microbiology, 2021)

Simple and Sensitive Multi-components Detection Using Synthetic Nitrogen-doped Carbon Dots Based on Soluble Starch - Yuanyuan Hu; Wenxuan Ji; Jinjuan Qiao; Heng Li; Yun Zhang; Jun Luo (Journal of Fluorescence, 2021)

Design, synthesis, and anticancer activities of 8,9-substituted Luotonin A analogs as novel topoisomerase I inhibitors - Yuanhang Xiang; Haiping Li; Jun Wang; Xiaozhi Peng; Chunling Hu; Laichun Luo (Medicinal Chemistry Research, 2021)

The improved activity of Co3O4 nanorods using silver in the catalytic oxidation of toluene - Tao Li; Jinxian Zhao; Yanhong Quan; Dongmou Luo; Chao Miao; Jun Ren (Environmental Science and Pollution Research, 2021)

Carbon storage of the forest and its spatial pattern in Tibet, China - Long-yu Jia; Gen-xu Wang; Ji Luo; Fei Ran; Wei Li; Jun Zhou; Dan-li Yang; Wen-bo Shi; Qian Xu; Kun Zhu; Yang Yang (Journal of Mountain Science, 2021)

Cysteiniphilum marinum sp. nov., isolated from coastal seawater - Hai-Min Luo; Jun-Hui Feng; Liang-Hui Li; Meng-Meng Li; Ru-Qin Liu; Fu Chen; Ying Lin; Wen-Jun Li; Ping-Hua Qu; Min Xiao (Antonie van Leeuwenhoek, 2021)

Evaluating the Friendliness of Pedestrian Footbridges Using Visibility Analysis: A Case Study in Wuhan - Jun Li; Shuang Wu; Zhiwei Luo; Jingyang Hou; Wenbo Zhang; Xueye Chen; Junru Su; Shen Ying (Journal of Geovisualization and Spatial Analysis, 2021)

EBV-miR-BART12 inhibits cell migration and proliferation by targeting Snail expression in EBV-associated gastric cancer - Jun Li; Yan Zhang; Juanjuan Liu; Qianzhu Shi; Wen Liu; Bing Luo (Archives of Virology, 2021)

Vital roles of soil microbes in driving terrestrial nitrogen immobilization - Zhaolei Li; Zhaoqi Zeng; Zhaopeng Song; Fuqiang Wang; Dashuan Tian; Wenhai Mi; Xin Huang; Jinsong Wang; Lei Song; Zhongkang Yang; Jun Wang; Haojie Feng; et al. (Global Change Biology, 2021)
Nitrogen immobilization usually leads to nitrogen retention in soil and, thus, influences soil nitrogen supply for plant growth. Understanding soil nitrogen immobilization is important for predicting soil nitrogen cycling under anthropogenic activities and climate changes. However, the global patterns and drivers of soil nitrogen immobilization remain unclear. We synthesized 1350 observations of gross soil nitrogen immobilization rate (NIR) from 97 articles to identify patterns and drivers of NIR. The global mean NIR was 8.77 ± 1.01 mg N kg −1 soil day −1 . It was 5.55 ± 0.41 mg N kg −1 soil day −1 in croplands, 15.74 ± 3.02 mg N kg −1 soil day −1 in wetlands, and 15.26 ± 2.98 mg N kg −1 soil day −1 in forests. The NIR increased with mean annual temperature, precipitation, soil moisture, soil organic carbon, total nitrogen, dissolved organic nitrogen, ammonium, nitrate, phosphorus, and microbial biomass carbon. But it decreased with soil pH. The results of structural equation models showed that soil microbial biomass carbon was a pivotal driver of NIR, because temperature, total soil nitrogen, and soil pH mostly indirectly influenced NIR via changing soil microbial biomass. Moreover, microbial biomass carbon accounted for most of the variations in NIR among all direct relationships. Furthermore, the efficiency of transforming the immobilized nitrogen to microbial biomass nitrogen was lower in croplands than in natural ecosystems (i.e., forests, grasslands, and wetlands). These findings suggested that soil nitrogen retention may decrease under the land use change from forests or wetlands to croplands, but NIR was expected to increase due to increased microbial biomass under global warming. The identified patterns and drivers of soil nitrogen immobilization in this study are crucial to project the changes in soil nitrogen retention.

Subcellular Localization of the D27 Protein in Sugarcane (Saccharum spp. Hybrids) Using an Optimized Protoplast Isolation, Purification, and Transient Gene Expression Protocol - Zhuan-di Wu; Xin Hu; Feng-gang Zan; Yong-bao Pan; David M. Burner; Zheng-ying Luo; Jia-yong Liu; Li-ping Zhao; Li Yao; Yong Zhao; Xin-long Liu; Hong-ming Xia; et al. (Sugar Tech, 2021)

Human β-Defensin 118 Attenuates Escherichia coli K88–Induced Inflammation and Intestinal Injury in Mice - Qian Lin; Qingqing Fu; Xiang Li; Yuheng Luo; Junqiu Luo; Daiwen Chen; Xiangbing Mao; Bing Yu; Ping Zheng; Zhiqing Huang; Jie Yu; Hui Yan; et al. (Probiotics and Antimicrobial Proteins, 2021)

New titanite U–Pb and molybdenite Re–Os ages for a hydrothermal vein-type Cu deposit in the Lanping Basin, Yunnan, SW China: constraints on regional metallogeny and implications for exploration - Juan Li; Lei-Luo Xu; Xian-Wu Bi; Yong-Yong Tang; Xiang-Yuan Sheng; Hai-Jun Yu; Gong Liu; Rui Ma (Mineralium Deposita, 2021)

Ferroptosis occurs in phase of reperfusion but not ischemia in rat heart following ischemia or ischemia/reperfusion - Li-Jing Tang; Xiu-Ju Luo; Hua Tu; Heng Chen; Xiao-Ming Xiong; Nian-Sheng Li; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Discovery of new small-molecule cyclin-dependent kinase 6 inhibitors through computational approaches - Xiaojiao Luo; Yu Zhao; Pan Tang; Xingkai Du; Feng Li; Qingying Wang; Rong Li; Jun He (Molecular Diversity, 2021)

First report of Chaetomella raphigera causing brown spot on Eucalyptus urophylla × E. grandis in China - Xiu-Xiu Cao; Ji-Guang Wei; Jian-Gan Hou; Chun-Li Fan; Ji Luo; Yao-Jun Wu; Xiu-Hao Yang; Ji-Tong Luo; Xiao-Bing Yang (Journal of Plant Pathology, 2021)

Image-Forming Visual Basis of Empathy for Pain in Mice - Kai-Wen Geng; Rui Du; Na Wei; Chun-Li Li; Yan Wang; Wei Sun; Tao Chen; Dong-Yu Wei; Yang Yu; Ting He; Wen-Jun Luo; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2020)

Update on recommendations for the diagnosis and treatment of SARS-CoV-2 infection in children - Hongjun Miao; Han Li; Yinying Yao; Mingfu Wu; Chao Lu; Jun Wang; Man Tian; Ying Li; Peiliang Luo; Jianhui Gu; Bin Yuan; Shouchuan Wang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
Since the outbreak of novel coronavirus infection pneumonia in Wuhan City, China, in late 2019, such cases have been gradually reported in other parts of China and abroad. Children have become susceptible to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) because of their immature immune function. As the outbreak has progressed, more cases of novel coronavirus infection/pneumonia in children have been reported. Compared with adults, the impact of SARS-CoV-2 infection in children is less severe, with a lower incidence and susceptibility in children, which results in fewer children being tested, thereby underestimating the actual number of infections. Therefore, strengthening the diagnosis of the disease is particularly important for children, and early and clear diagnosis can determine treatment strategies and reduce the harm caused by the disease to children. According to the Novel Coronavirus Infection Pneumonia Diagnosis and Treatment Standards ( trial version 7 ) issued by National Health Committee and the latest diagnosis and treatment strategies for novel coronavirus infection pneumonia in children, this review summarizes current strategies on diagnosis and treatment of SARS-CoV-2 infection in children.

Unsupervised seismic facies analysis using sparse representation spectral clustering - Wang Yao-Jun; Wang Liang-Ji; Li Kun-Hong; Liu Yu; Luo Xian-Zhe; Xing Kai (Applied Geophysics, 2020)

Role of major histocompatibility complex II antigen‐presentation pathway genes in orange‐spotted grouper infected with Cryptocaryon irritans - Jun‐Jin Deng; Shun Xu; Yan‐Wei Li; Dong‐Dong Xu; Ze‐Quan Mo; Jia‐Zhou Li; Xue‐Ming Dan; Xiao‐Chun Luo (Journal of Fish Diseases, 2020)
Cryptocaryon irritans , a pathogen model for fish mucosal immunity, causes skin mucosal and systematic humoral immune response. Where and how MHC II antigen presentation occurs in fish infected with C . irritans remain unknown. In this study, the full‐length cDNA of the grouper cysteine protease CTSS was cloned. The expression distributions of six genes (CTSB, CTSL, CTSS, GILT, MHC IIA and MHC IIB) involved in MHC II antigen presentation pathway were tested. These genes were highly expressed in systematic immune tissues and skin and gill mucosal‐associated immune tissues. All six genes were upregulated in skin at most time points. Five genes expected CTSS was upregulated in spleen at most time points. CTSB, CTSL and MHC IIA were upregulated in the gill and head kidney at some time points. These results indicate that the presentation of MHC II antigen intensively occurred in local infected skin and gill. Spleen, not head kidney, had the most extensive systematic antigen presentation. In skin, six genes most likely peaked at day 2, earlier than in spleen (5–7 days), marking an earlier skin antibody peak than any recorded in serum previously. This significant and earlier mucosal antigen presentation indicates that specific immune response occurs in local mucosal tissues.

Spinal CCL2 Promotes Pain Sensitization by Rapid Enhancement of NMDA-Induced Currents Through the ERK-GluN2B Pathway in Mouse Lamina II Neurons - Hui Zhang; Sui-Bin Ma; Yong-Jing Gao; Jun-Ling Xing; Hang Xian; Zhen-Zhen Li; Shu-Ning Shen; Sheng-Xi Wu; Ceng Luo; Rou-Gang Xie (Neuroscience Bulletin, 2020)
Previous studies have shown that CCL2 (C–C motif chemokine ligand 2) induces chronic pain, but the exact mechanisms are still unknown. Here, we established models to explore the potential mechanisms. Behavioral experiments revealed that an antagonist of extracellular signal-regulated kinase (ERK) inhibited not only CCL2-induced inflammatory pain, but also pain responses induced by complete Freund’s adjuvant. We posed the question of the intracellular signaling cascade involved. Subsequent experiments showed that CCL2 up-regulated the expression of phosphorylated ERK (pERK) and N-methyl D-aspartate receptor [NMDAR] subtype 2B (GluN2B); meanwhile, antagonists of CCR2 and ERK effectively reversed these phenomena. Whole-cell patch-clamp recordings revealed that CCL2 enhanced the NMDAR-induced currents via activating the pERK pathway, which was blocked by antagonists of GluN2B and ERK. In summary, we demonstrate that CCL2 directly interacts with CCR2 to enhance NMDAR-induced currents, eventually leading to inflammatory pain mainly through the CCL2–CCR2–pERK–GluN2B pathway.

Using profitable chrysanthemums for phytoremediation of Cd- and Zn-contaminated soils in the suburb of Shanghai - Fan Luo; Xue-Feng Hu; Kokyo Oh; Li-Jun Yan; Xin-Zhe Lu; Wei-Jie Zhang; Tetsushi Yonekura; Shinichi Yonemochi; Yugo Isobe (Journal of Soils and Sediments, 2020)

Comparative analysis of the gut microbiota of Apis cerana in Yunnan using high-throughput sequencing - Zhi-Wen Luo; Zhi-Xiang Dong; Yi-Fei Chen; Huan-Yuan Li; Qi-He Tang; Ji-Lian Li; Jun Guo (Archives of Microbiology, 2020)

Two CYP71AJ enzymes function as psoralen synthase and angelicin synthase in the biosynthesis of furanocoumarins in Peucedanum praeruptorum Dunn - Xiangyun Jian; Yucheng Zhao; Ziwen Wang; Shan Li; Li Li; Jun Luo; Lingyi Kong (Plant Molecular Biology, 2020)

Comparative iTRAQ Proteomics Reveals Multiple Effects of Selenium Yeast on Dairy Cows in Parturition - Zhi-hua Ren; Li-peng Bai; Liu-hong Shen; Zheng-zhong Luo; Zi-han Zhou; Zhi-cai Zuo; Xiao-ping Ma; Jun-liang Deng; Ya Wang; Sheng-yu Xu; Yu-heng Luo; Sui-zhong Cao; et al. (Biological Trace Element Research, 2020)

Characterization of a Cu2+, SDS, alcohol and glucose tolerant GH1 β-glucosidase from Bacillus sp. CGMCC 1.16541 - Yi-Rui Yin; Peng Sang; Feng-Li Yang; Tao Li; Run-Feng Yang; Hong-Yan Liu; Zong-Long Luo; Wen-Jun Li; Li-Quan Yang (Antonie van Leeuwenhoek, 2020)

Directional seismic response to the complex topography: A case study of 2013 Lushan Ms 7.0 earthquake - Bo Zhao; Yun-sheng Wang; Li-jun Su; Yong-hong Luo; Jing Zhang (Journal of Mountain Science, 2020)

The Oil Content Inversion of Tar Sands by Spectroscopy - Ruixue Fan; Lixin Xing; Jun Pan; Xuanlong Shan; Guangjie Luo; Changwei Li (Journal of the Indian Society of Remote Sensing, 2020)

A robust segmentation framework for closely packed buildings from airborne LiDAR point clouds - Xinsheng Wang; Ting On Chan; Kai Liu; Jun Pan; Ming Luo; Wenkai Li; Chunzhu Wei (International Journal of Remote Sensing, 2020)

Distinct Characteristics of Bacterial Community in the Soil of Nanshazhou Island, South China Sea - Yong-gan Chen; Zhen-hua Zhang; Hong-wei Luo; Zhen Li; Lai-jun Zhang; Hai Huang (Current Microbiology, 2020)

Empathic Contagious Pain and Consolation in Laboratory Rodents: Species and Sex Comparisons - Rui Du; Wen-Jun Luo; Kai-Wen Geng; Chun-Li Li; Yang Yu; Na Wei; Jun Chen (Neuroscience Bulletin, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

Anti-inflammatory bibenzyls from the stems of Dendrobium huoshanense via bioassay guided isolation - Qiang-Ming Li; Hui Jiang; Xue-Qiang Zha; De-Ling Wu; Li-Hua Pan; Jun Duan; Jian Liu; Jian-Ping Luo (Natural Product Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Effects of Exogenous GA3 and DPC Treatments on Levels of Endogenous Hormone and Expression of Key Gibberellin Biosynthesis Pathway Genes During Stem Elongation in Sugarcane - Li-Hang Qiu; Rong-Fa Chen; Han-Min Luo; Ye-Geng Fan; Xing Huang; Jun-Xian Liu; Fa-Qian Xiong; Hui-Wen Zhou; Chong-Kun Gan; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2019)

Reef-carbonate diagenesis in the Pleistocene–Holocene of the well Xike#1, Xisha Islands, South China Sea: implications on sea-level changes - Na Liu; Zhen-feng Wang; Xu-shen Li; Li Liu; Dao-jun Zhang; Li You; Wei Luo; Xin-yu Liu (Carbonates and Evaporites, 2019)

Interleukin-4 signalling pathway underlies the anxiolytic effect induced by 3-deoxyadenosine - Tangxin Gao; Bai Li; Yangyang Hou; Shaolei Luo; Lei Feng; Jun Nie; Yi Ma; Le Xiao; Xu Chen; Hongkun Bao; Xianmin Lu; Feilong Huang; et al. (Psychopharmacology, 2019)

The 2012 Flash Drought Threatened US Midwest Agroecosystems - Cui Jin; Xue Luo; Xiangming Xiao; Jinwei Dong; Xueming Li; Jun Yang; Deyu Zhao (Chinese Geographical Science, 2019)

De Novo Assembled Transcriptome Analysis and Identification of Genic SSR Markers in Red-Flowered Strawberry - Yan Ding; Li Xue; Rui-xue Guo; Gang-jun Luo; Yu-tong Song; Jia-jun Lei (Biochemical Genetics, 2019)

The deafness gene GSDME: its involvement in cell apoptosis, secondary necrosis, and cancers - Yue-Qi Li; Jing-Jie Peng; Jun Peng; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Ligustroflavone reduces necroptosis in rat brain after ischemic stroke through targeting RIPK1/RIPK3/MLKL pathway - Yi-Yue Zhang; Wei-Ning Liu; Yue-Qi Li; Xiao-Jie Zhang; Jie Yang; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Petrogenesis of early Late Cretaceous Asa-intrusive rocks in central Tibet, western China: post-collisional partial melting of thickened lower crust - An-Bo Luo; Ming Wang; Cai Li; Chao-Ming Xie; Jian-jun Fan; Tian-Yu Zhang; Jin-Heng Liu; Wei Wang (International Journal of Earth Sciences, 2019)

Population structure and genetic diversity of Vibrio parahaemolyticus from a coastal area of China based on a multi-locus sequence typing (MLST) scheme - Yu Li; Hong-Qiu Yin; Jun Xia; Hong Luo; Ming-Yi Wang (Antonie van Leeuwenhoek, 2019)

An Upper Crustal Ophiolite Remnant within the Feather River Ultramafic Belt, California: Tectonomagmatic Origins and Implications for Its Evolution - Jun Luo; John Wakabayashi; Zhiliang He; Jinbiao Yun; Quanyou Liu; Tianyi Li; Haiming Song; Wenjiao Xiao (Journal of Earth Science, 2019)

Potassium ameliorates iron deficiency by facilitating the remobilization of iron from root cell walls and promoting its translocation from roots to shoots - Yi Quan Ye; Hong Yan Luo; Mao Li; Jia Jun Zhang; Guang Qiu Cao; Kai Min Lin; Si Zu Lin; Shan Shan Xu (Plant and Soil, 2019)

LCAL1 enhances lung cancer survival via inhibiting AMPK-related antitumor functions - Jun-Yu Li; Zhi-Qiang Luo (Molecular and Cellular Biochemistry, 2019)

Portable vertical pendulum tiltmeter development and application test - Jie-ning Xia; Qiang Lin; Li-Xia Geng; Zhen Li; Song Luo; Nong-Fa Li; Jian-Feng Yu; Jun Liu (Acta Geodaetica et Geophysica, 2019)

Development of attenuated erythromycin‐resistant Streptococcus agalactiae vaccine for tilapia ( Oreochromis niloticus ) culture - Ling Liu; Dan‐Qi Lu; Jun Xu; Heng‐Li Luo; An‐Xing Li (Journal of Fish Diseases, 2019)
Streptococcus agalactiae is an important pathogen in fish, causing great losses of intensive tilapia farming. To develop a potential live attenuated vaccine, a re‐attenuated S. agalactiae (named TFJ‐ery) was developed from a natural low‐virulence S. agalactiae strain TFJ0901 through selection of resistance to erythromycin. The biological characteristics, virulence, stability and the immunization protective efficacy to tilapia of TFJ‐ery were determined. The results indicated that TFJ‐ery grew at a slower rate than TFJ0901. The capsule thickness of TFJ‐ery was significantly less ( p 0.05) than TFJ0901. When Nile tilapia were intraperitoneally (IP) injected with TFJ‐ery, the mortality of fish was decreased than that injected with TFJ0901. The RPS of fish immunized with TFJ‐ery at a dose of 5.0 × 10 7 CFU was 95.00%, 93.02% and 100.00% at 4, 8 and 16 weeks post‐vaccination, respectively. ELISA results showed that the vaccinated fish produced significantly higher ( p 0.05) antibody titres compared to those of control at 2 or 4 weeks post‐vaccination. Taken together, our results suggest that erythromycin could be used to attenuate S. agalactiae , and TFJ‐ery is a potent attenuated vaccine candidate to protect tilapia against S. agalactiae infections.

Complete mitochondrial genome of a kind of snakehead fish Channa siamensis and its phylogenetic consideration - Rui Li; Gang Wang; Zheng-Yong Wen; Yuan-Chao Zou; Chuan-Jie Qin; Yu Luo; Jun Wang; Gui-Hong Chen (Genes & Genomics, 2019)

Establishment and application of distant hybridization technology in fish - Shi Wang; Chenchen Tang; Min Tao; Qinbo Qin; Chun Zhang; Kaikun Luo; Rurong Zhao; Jing Wang; Li Ren; Jun Xiao; Fangzhou Hu; Rong Zhou; et al. (Science China Life Sciences, 2019)

Postprandial change in glucose metabolism at the molecular level in the adipose tissue of omnivorous GIFT Oreochromis niloticus - Jing-Yun Feng; Qin-Qin Liu; Hang-Zhong Xu; Rui-Hong Chen; Li Luo; Shi-Mei Lin; Yong-Jun Chen; De-Shou Wang (Fisheries Science, 2019)

Sesquiterpenes and lignans from the flower buds of Daphne genkwa and their nitric oxide inhibitory activities - Chun-Yang Zhang; Lan Luo; Jing Xia; Ya-Nan Song; Li-Jun Zhang; Miao Zhang; Khalid Rahman; Yin Ye; Hong Zhang; Jian-Yong Zhu (Natural Product Research, 2018)

Functions of PKS Genes in Lipid Synthesis of Schizochytrium sp. by Gene Disruption and Metabolomics Analysis - Zhipeng Li; Xi Chen; Jun Li; Tong Meng; Lingwei Wang; Zhen Chen; Yanyan Shi; Xueping Ling; Weiang Luo; Dafeng Liang; Yinghua Lu; Qingbiao Li; et al. (Marine Biotechnology, 2018)

Cryo-EM structure reveals cylindrical nucleocapsids from two polydnaviruses - Ji-Hui Cui; Ya-Bin Chen; Ming Li; Qiu-Chen Cai; Li-Dan Zhang; Zi-Yun Lu; Jian-Cheng Li; Qi-Shun Zhu; Gang Ji; Kai-Jun Luo (Archives of Virology, 2018)

Combination of Emricasan with Ponatinib Synergistically Reduces Ischemia/Reperfusion Injury in Rat Brain Through Simultaneous Prevention of Apoptosis and Necroptosis - Jing Tian; Shu Guo; Heng Chen; Jing-Jie Peng; Miao-Miao Jia; Nian-Sheng Li; Xiao-Jie Zhang; Jie Yang; Xiu-Ju Luo; Jun Peng (Translational Stroke Research, 2018)

Design, synthesis, and biological evaluation of thiomatrine derivatives as potential anticancer agents - Zheng Li; Lichuan Wu; Bin Cai; Mengyang Luo; Mengtian Huang; Haroon Ur Rashid; Yuwen Yang; Jun Jiang; Lisheng Wang (Medicinal Chemistry Research, 2018)

Repaglinide-irbesartan drug interaction: effects of SLCO1B1 polymorphism on repaglinide pharmacokinetics and pharmacodynamics in Chinese population - Qi Pei; Jun-Yan Liu; Ji-Ye Yin; Guo-Ping Yang; Shi-Kun Liu; Yi Zheng; Pan Xie; Cheng-Xian Guo; Mi Luo; Hong-Hao Zhou; Xi Li; Zhao-Qian Liu (European Journal of Clinical Pharmacology, 2018)

Social Isolation During Adolescence Induces Anxiety Behaviors and Enhances Firing Activity in BLA Pyramidal Neurons via mGluR5 Upregulation - Song Lin; Xin Li; Yi-Hua Chen; Feng Gao; Hao Chen; Neng-Yuan Hu; Lang Huang; Zheng-Yi Luo; Ji-Hong Liu; Qiang-Long You; Ya-Nan Yin; Ze-Lin Li; et al. (Molecular Neurobiology, 2018)

SOX2-mediated inhibition of miR-223 contributes to STIM1 activation in phenylephrine-induced hypertrophic cardiomyocytes - Zhi-Hong Zhao; Jun Luo; Hai-xia Li; Sai-hua Wang; Xin-ming Li (Molecular and Cellular Biochemistry, 2018)

OsPKS2 is required for rice male fertility by participating in pollen wall formation - Ting Zou; Mingxing Liu; Qiao Xiao; Tao Wang; Dan Chen; Tao Luo; Guoqiang Yuan; Qiao Li; Jun Zhu; Yueyang Liang; Qiming Deng; Shiquan Wang; et al. (Plant Cell Reports, 2018)

Morphology and multigene phylogeny reveal new genus and species of Torulaceae from freshwater habitats in northwestern Yunnan, China - Xi-Jun Su; Zong-Long Luo; Rajesh Jeewon; Darbhe J. Bhat; Dan-Feng Bao; Wen-Li Li; Yu-E Hao; Hong-Yan Su; Kevin D. Hyde (Mycological Progress, 2018)

Morphological and molecular taxonomy of novel species Pleurotheciaceae from freshwater habitats in Yunnan, China - Zong-Long Luo; Kevin D. Hyde; Darbhe J. Bhat; Rajesh Jeewon; Sajeewa S. N. Maharachchikumbura; Dan-Feng Bao; Wen-Li Li; Xi-Jun Su; Xiao-Yan Yang; Hong-Yan Su (Mycological Progress, 2018)

Surface IgM λ light chain is involved in the binding and infection of infectious bursal disease virus (IBDV) to DT40 cells - Jiaqi Chi; Leiming You; Peipei Li; Man Teng; Gaiping Zhang; Jun Luo; Aiping Wang (Virus Genes, 2018)

Cytotoxic withanolides from Physalis angulata - Caiyun Gao; Ruijun Li; Miaomiao Zhou; Yanwei Yang; Lingyi Kong; Jun Luo (Natural Product Research, 2018)

Early Carboniferous ophiolite in central Qiangtang, northern Tibet: record of an oceanic back-arc system in the Palaeo-Tethys Ocean - Tian-Yu Zhang; Jian-Jun Fan; Cai Li; Chao-Ming Xie; Ming Wang; Yan-Wang Wu; Meng-Jing Xu; Wei Xu; Jin-Heng Liu; An-Bo Luo (International Geology Review, 2018)

A comparative study of distant hybridization in plants and animals - Jie Chen; Mi Luo; Shengnan Li; Min Tao; Xiaolan Ye; Wei Duan; Chun Zhang; Qinbo Qin; Jun Xiao; Shaojun Liu (Science China Life Sciences, 2018)

Variations in cadmium and nitrate co-accumulation among water spinach genotypes and implications for screening safe genotypes for human consumption - Lin Tang; Wei-jun Luo; Zhen-li He; Hanumanth Kumar Gurajala; Yasir Hamid; Kiran Yasmin Khan; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2018)

A new arbutin derivative from the leaves of Vaccinium dunalianum wight - Na Li; Wei-Lin Zeng; Xu-Lu Luo; Chong-Ren Yang; Ying-Jun Zhang; Yong Ding; Ping Zhao (Natural Product Research, 2018)

ALDH2 genes are negatively correlated with natural deastringency in Chinese PCNA persimmon (Diospyros kaki Thunb.) - Jun-Chi Xu; Jin-Ge Ding; Jian-Ping Gan; Rong-Li Mo; Li-Qing Xu; Qing-Lin Zhang; Zheng-Rong Luo (Tree Genetics & Genomes, 2017)

Analysis of intergeneric sexual hybridization between transgenic Brassica oleracea and Sinapis alba - Jun Li; Chunlei Zhang; Chunyun Guan; Lixia Luo; Li Ren; Wenhui Wei; Guangyuan Lu; Xiaoping Fang (Euphytica, 2017)
Sinapis alba possesses a number of desirable traits that can be employed to broaden genetic variability in Brassica oleracea or B. napus . Using transgenic B. oleracea (CC, 2n = 18) as paternal plants and non-transgenic S. alba (SS, 2n = 24) as maternal plants, 11 hybrid plants were successfully obtained by using a combination of ovary culture and embryo rescue, while 2 seedlings of the reciprocal cross were generated but lost during the propagation. The hybridity of these plants was confirmed by flower color and other agronomic characteristics, chromosome counting, and pollen viability. Most of the intergeneric F 1 plants showed only one set each of S and C chromosome (SC, 2n = 21) and were male sterile, while a few plants were semi-fertile and had one set of S chromosomes but two sets of C chromosomes (CCS, 2n = 30). PCR, genomic Southern blotting and qRT-PCR for bar gene revealed that among the F 1 hybrid plants only 9.1% was bar positive and could be forwarded to F 2 and F 3 generation. The majority of F 3 plants obtained sufficient resistance to Alternaria brassicae . Thus, the generation of disease ( A. brassicae ) and herbicide (Bastar) resistant intergeneric hybrids was of importance for breeding program. The existence of bar gene in these intermediate materials will facilitate the identification of hybridity and transfer of S.alba traits into target genetic background.

Complete plastid genomes of the genus Ammopiptanthus and identification of a novel 23-kb rearrangement - Lei Feng; Li-Fei Gu; Juan Luo; Ai-Si Fu; Qiong Ding; Siu-Ming Yiu; Jun-Xian He (Conservation Genetics Resources, 2017)

Age, nature, and origin of early cretaceous plutons in the Dabie Mo Mineralization belt: the Xinxian example - Qing-quan Liu; Yu Zhang; Yong-jun Shao; Ke-Ping Zhou; Yong-feng Li; Zheng-zhuan Luo (International Geology Review, 2017)

A new catechin derivative from the fruits of Rosa sterilis S. D. Shi - Xu-Lu Luo; Han-Long Dan; Na Li; Yong-He Li; Ying-Jun Zhang; Ping Zhao (Natural Product Research, 2017)

Synthesis and antiproliferative properties of novel naringenin derivatives - Su-You Liu; Jiang Zeng; Kun-Jian Peng; Li-Chao Zhang; Li-Jun Liu; Zhi-Yong Luo; Da-You Ma (Medicinal Chemistry Research, 2017)

A genetic variant in the placenta-derived MHC class I chain-related gene A increases the risk of preterm birth in a Chinese population - Junjiao Song; Jing Li; Han Liu; Yuexin Gan; Yang Sun; Min Yu; Yongjun Zhang; Fei Luo; Ying Tian; Weiye Wang; Jun Zhang; Julian Little; et al. (Human Genetics, 2017)

Construction and characterization of a bacterial artificial chromosome library for Camellia sinensis - Yuling Tai; Hao Wang; Chaoling Wei; Ling Su; Min Li; Liqun Wang; Zhaozhao Dai; Lingyun Shao; Jiayue Jiang; Meizhong Luo; Hua Yang; Weiwei Deng; et al. (Tree Genetics & Genomes, 2017)

Novel adefovir mono L-amino acid ester, mono bile acid ester derivatives: Design, synthesis, biological evaluation, and molecular docking study - Ya Chen; Wen Zheng Zhang; Jing Li; Tao Xiao; Jiang Xia Liu; Min Luo; Hang Su; Xiao-Zhong Fu; Ting Liu; Yong-Xi Dong; Yong-Long Zhao; Bin He; et al. (Medicinal Chemistry Research, 2017)

Climatic and geographic factors affect ecosystem multifunctionality through biodiversity in the Tibetan alpine grasslands - Ying Pan; Jun-xi Wu; Li-ming Luo; Yan-li Tu; Cheng-qun Yu; Xian-zhou Zhang; Yan-jun Miao; Yan Zhao; Jun-ling Yang (Journal of Mountain Science, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

Similar behavior, different mechanisms: the research of the style bending of Alpinia species - Zhi-Long Su; Xian-Liang Cui; Li Li; Qing-Jun Li; Yin-Ling Luo (Acta Physiologiae Plantarum, 2017)

Prior Visual Experience Modulates Learning of Sound Localization Among Blind Individuals - Qian Tao; Chetwyn C. H. Chan; Yue-jia Luo; Jian-jun Li; Kin-hung Ting; Zhong-lin Lu; Susan Whitfield-Gabrieli; Jun Wang; Tatia M. C. Lee (Brain Topography, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

First complete genome sequence of parainfluenza virus 5 isolated from lesser panda - Jun-Qiong Zhai; Shao-Lun Zhai; Tao Lin; Jian-Kui Liu; He-Xing Wang; Bing Li; He Zhang; Shu-Zhan Zou; Xia Zhou; Meng-Fan Wu; Wu Chen; Man-Lin Luo (Archives of Virology, 2017)

Occurrence and distribution of antibiotics in multiple environmental media of the East River (Dongjiang) catchment, South China - Ruijie Zhang; Ruiling Zhang; Jun Li; Zhineng Cheng; Chunling Luo; Yinghui Wang; Kefu Yu; Gan Zhang (Environmental Science and Pollution Research, 2017)

Sodium P-Aminosalicylic Acid Improved Manganese-Induced Learning and Memory Dysfunction via Restoring the Ultrastructural Alterations and γ-Aminobutyric Acid Metabolism Imbalance in the Basal Ganglia - Chao-Yan Ou; Yi-Ni Luo; Sheng-Nan He; Xiang-Fa Deng; Hai-Lan Luo; Zong-Xiang Yuan; Hao-Yang Meng; Yu-Huan Mo; Shao-Jun Li; Yue-Ming Jiang (Biological Trace Element Research, 2017)

Impacts of sediment type on the performance and composition of submerged macrophyte communities - Lin Liu; Xiang-Qi Bu; Jun-Yan Wan; Bi-Cheng Dong; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Aquatic Ecology, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Distribution and health risk assessment of dissolved heavy metals in the Three Gorges Reservoir, China (section in the main urban area of Chongqing) - Xin Zhao; Ting-Yong Li; Tao-Tao Zhang; Wei-Jun Luo; Jun-Yun Li (Environmental Science and Pollution Research, 2017)

Chemical composition, in vitro antioxidant activity and α-glucosidase inhibitory effects of the essential oil and methanolic extract of Elsholtzia densa Benth. - Xue Xuanji; Guo Zengjun; Zhang Hui; Liu Xia; Luo Jun; Li Dandan; Li Jun (Natural Product Research, 2016)

A polydnaviral genome of Microplitis bicoloratus bracovirus and molecular interactions between the host and virus involved in NF-κB signaling - Dong-Shuai Yu; Ya-Bin Chen; Ming Li; Ming-Jun Yang; Yang Yang; Jian-Sheng Hu; Kai-Jun Luo (Archives of Virology, 2016)

Nematode‐trapping fungi and fungus‐associated bacteria interactions: the role of bacterial diketopiperazines and biofilms on Arthrobotrys oligospora surface in hyphal morphogenesis - Lei Li; Min Yang; Jun Luo; Qing Qu; Ying Chen; Lianming Liang; Keqin Zhang (Environmental Microbiology, 2016)
Summary In soil, nematode‐trapping fungi and bacteria often share microhabitats and interact with each other, but effects of fungus‐associated bacteria on its trap formation are underestimated. We have ascertained the presence of Stenotrophomonas and Rhizobium genera associated with A. oligospora GJ‐1. After A. oligospora GJ‐1 without associated bacteria (cured Arthrobotrys ) was co‐cultivated with Stenotrophomonas and its supernatant extract, microscopic study of hyphae from co‐cultivation indicated that bacterial biofilm formation on hyphae was related to trap formation in fungi and Stenotrophomonas supernatant extract. Four diketopiperazines (DKPs) were purified from Stenotrophomonas supernatant extract that could not induce traps in the cured Arthrobotrys . When cured Arthrobotrys was cultured with Stenotrophomonas and one of DKPs, polar attachment, bacterial biofilms on hyphae and trap formation in fungi were observed. After cured Arthrobotrys with bacterial biofilms was consecutively transferred several times on nutrient poor medium, trap formation disappeared with the disappearance of bacterial biofilms on hyphae. DKPs could facilitate chemotaxis of Stenotrophomonas towards fungal extract which was suggested to contribute to bacterial biofilms on hyphae. Furthermore, when cured Arthrobotrys was cultured with Stenotrophomonas and DKPs in soil, trap formation in fungi and bacterial biofilms on hyphae were also observed, and the fungal activity against nematode was enhanced.

Ethanol Increases Mechanical Pain Sensitivity in Rats via Activation of GABAA Receptors in Medial Prefrontal Cortex - Kai-Wen Geng; Ting He; Rui-Rui Wang; Chun-Li Li; Wen-Jun Luo; Fang-Fang Wu; Yan Wang; Zhen Li; Yun-Fei Lu; Su-Min Guan; Jun Chen (Neuroscience Bulletin, 2016)

Inhibition of the oxidative stress-induced miR-23a protects the human retinal pigment epithelium (RPE) cells from apoptosis through the upregulation of glutaminase and glutamine uptake - Dan-dan Li; Bin-wu Zhong; Hai-xia Zhang; Hong-yan Zhou; Jie Luo; Yang Liu; Gui-chun Xu; Chun-sheng Luan; Jun Fang (Molecular Biology Reports, 2016)

Permeability of novel 4′-N-substituted (aminomethyl) benzoate-7-substituted nicotinic acid ester derivatives of scutellarein in Caco-2 cells and in an in vitro model of the blood-brain barrier - Yu Ou; Min Luo; Yong-Xi Dong; Hang Su; Xiao-Zhong Fu; Yu-Feng Cha; Shun Zhang; Yong-Long Zhao; Yong-Jun Li; Yong-Lin Wang (Medicinal Chemistry Research, 2016)

NK cells contribute to persistent airway inflammation and AHR during the later stage of RSV infection in mice - Xiaoru Long; Jun Xie; Keting Zhao; Wei Li; Wei Tang; Sisi Chen; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Lijia Wang; Zhou Fu; et al. (Medical Microbiology and Immunology, 2016)

Greenhouse gas emissions in a spring wheat–field pea sequence under different tillage practices in semi-arid Northwest China - Stephen Yeboah; Renzhi Zhang; Liqun Cai; Min Song; LingLing Li; Junhong Xie; Zhuzhu Luo; Jun Wu; Jun Zhang (Nutrient Cycling in Agroecosystems, 2016)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

Cerebral blood flow changes in hemodialysis and peritoneal dialysis patients: an arterial-spin labeling MR imaging - Xiao Lu Jiang; Ji Qiu Wen; Long Jiang Zhang; Gang Zheng; Xue Li; Zhe Zhang; Ya Liu; Li Juan Zheng; Long Wu; Hui Juan Chen; Xiang Kong; Song Luo; et al. (Metabolic Brain Disease, 2016)

Efficient biodegradation of phenanthrene by a novel strain Massilia sp. WF1 isolated from a PAH-contaminated soil - Haizhen Wang; Jun Lou; Haiping Gu; Xiaoyan Luo; Li Yang; Laosheng Wu; Yong Liu; Jianjun Wu; Jianming Xu (Environmental Science and Pollution Research, 2016)

Three duplication events and variable molecular evolution characteristics involved in multiple GGPS genes of six Solanaceae species - FENG LI; CHUNYANG WEI; CHAN QIAO; ZHENXI CHEN; PENG WANG; PAN WEI; RAN WANG; LIFENG JIN; JUN YANG; FUCHENG LIN; ZHAOPENG LUO (Journal of Genetics, 2016)

Sodium Para-aminosalicylic Acid Protected Primary Cultured Basal Ganglia Neurons of Rat from Manganese-Induced Oxidative Impairment and Changes of Amino Acid Neurotransmitters - Shao-Jun Li; Yong Li; Jing-Wen Chen; Zong-Xiang Yuan; Yu-Huan Mo; Guo-Dong Lu; Yue-Ming Jiang; Chao-Yan Ou; Fang Wang; Xiao-Wei Huang; Yi-Ni Luo; Shi-Yan Ou; et al. (Biological Trace Element Research, 2016)

Involvement of NADPH oxidases and non-muscle myosin light chain in senescence of endothelial progenitor cells in hyperlipidemia - Ting-Bo Li; Jie-Jie Zhang; Bin Liu; Wei-Qi Liu; Yan Wu; Xiao-Ming Xiong; Xiu-Ju Luo; Qi-Lin Ma; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

Clinical validation of a novel real-time human papillomavirus assay for simultaneous detection of 14 high-risk HPV type and genotyping HPV type 16 and 18 in China - Hui Yang; Lie-Jun Li; Long-Xu Xie; Zhao-Yun Luo; Min Lu; Min Lin; Xiang-bin Zheng; Yue Huang; Li-Ye Yang (Archives of Virology, 2016)

Location- and Subunit-Specific NMDA Receptors Determine the Developmental Sevoflurane Neurotoxicity Through ERK1/2 Signaling - Wen-Yuan Wang; Li-Jie Jia; Yan Luo; Hong-Hai Zhang; Fang Cai; Hui Mao; Wei-Cai Xu; Jun-Biao Fang; Zhi-You Peng; Zheng-Wen Ma; Yan-Hong Chen; Juan Zhang; et al. (Molecular Neurobiology, 2016)

Concomitant coronary and renal revascularization improves left ventricular hypertrophy more than coronary stenting alone in patients with ischemic heart and renal disease - Hao-jian Dong; Cheng Huang; De-mou Luo; Jing-guang Ye; Jun-qing Yang; Guang Li; Jian-fang Luo; Ying-ling Zhou (Journal of Zhejiang University-SCIENCE B, 2016)

Distinct subcellular localization and potential role of LINE1-ORF1P in meiotic oocytes - Yi-Bo Luo; Li Zhang; Zi-Li Lin; Jun-Yu Ma; Jialin Jia; Suk Namgoong; Qing-Yuan Sun (Histochemistry and Cell Biology, 2016)

Differential effects of general anesthetics on anxiety-like behavior in formalin-induced pain: involvement of ERK activation in the anterior cingulate cortex - Cong Luo; Yan-Ling Zhang; Wei Luo; Fiona H Zhou; Chang-Qi Li; Jun-Mei Xu; Ru-Ping Dai (Psychopharmacology, 2015)

Corilagin Protects Against HSV1 Encephalitis Through Inhibiting the TLR2 Signaling Pathways In Vivo and In Vitro - Yuan-Jin Guo; Tao Luo; Fei Wu; Huan Liu; Hua-Rong Li; Yuan-Wu Mei; Shu-Ling Zhang; Jun-Yan Tao; Ji-Hua Dong; Yuan Fang; Lei Zhao (Molecular Neurobiology, 2015)

Long-term effects of oral tea polyphenols and Lactobacillus brevis M8 on biochemical parameters, digestive enzymes, and cytokines expression in broilers - Hua-li Li; Zong-jun Li; Zhong-shan Wei; Ting Liu; Xiao-zuo Zou; Yong Liao; Yu Luo (Journal of Zhejiang University-SCIENCE B, 2015)

Subchronic effects of cadmium on the gonads, expressions of steroid hormones and sex-related genes in tilapia Oreochromis niloticus - Yongju Luo; Dan Shan; Huan Zhong; Yi Zhou; Wenzhi Chen; Jinling Cao; Zhongbao Guo; Jun Xiao; Fulin He; Yifan Huang; Jian Li; Heming Huang; et al. (Ecotoxicology, 2015)

Neuroprotective effect of bisabolangelone on hydrogen peroxide-induced neurotoxicity in SH-SY5Y cells - Jun-Zhi Wang; Xi-Ming Yan; Zi-Cheng Li; Hua-Jun Luo; Nian-Yu Huang; Wei-Qiao Deng (Medicinal Chemistry Research, 2015)

Erratum to: Rapid and environmentally-friendly extraction of carotenoids from Blakeslea trispora - Hong-Bo Wang; Li-Wei Zhang; Jun Luo; Long-Jiang Yu (Biotechnology Letters, 2015)

Rapid and environmentally-friendly extraction of carotenoids from Blakeslea trispora - Hong-Bo Wang; Li-Wei Zhang; Jun Luo; Long-Jiang Yu (Biotechnology Letters, 2015)

HPLC simultaneous determination of arbutin, chlorogenic acid and 6′- O -caffeoylarbutin in different parts of Vaccinium dunalianum Wight - Xu-Lu Luo; Na Li; Min Xu; Hong-Tao Zhu; Peng He; Yong Ding; Ping Zhao; Ying-Jun Zhang (Natural Product Research, 2015)

Pectin Modifications: A Review - Jun Chen; Wei Liu; Cheng-Mei Liu; Ti Li; Rui-Hong Liang; Shun-Jing Luo (Critical Reviews in Food Science and Nutrition, 2015)

Downregulation of the lycopene ε-cyclase gene confers tolerance to salt and drought stress in Nicotiana tabacum - Yanmei Shi; Pingping Liu; Yuzhen Xia; Pan Wei; Wenzheng Li; Wei Zhang; Xia Chen; Peijian Cao; Yalong Xu; Lifeng Jin; Feng Li; Zhaopeng Luo; et al. (Acta Physiologiae Plantarum, 2015)

Inhibition of myosin light chain kinase reduces NADPH oxidase-mediated oxidative injury in rat brain following cerebral ischemia/reperfusion - Hong-Feng Zhang; Ting-Bo Li; Bin Liu; Zheng Lou; Jie-Jie Zhang; Jing-Jie Peng; Xiao-Jie Zhang; Qi-Lin Ma; Jun Peng; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Generation and characterization of Brassica rapa ssp. pekinensis – B. oleracea var. capitata monosomic and disomic alien addition lines - AI XIA GU; SHU XING SHEN; YAN HUA WANG; JIAN JUN ZHAO; SHU XIN XUAN; XUE PING CHEN; XIAO FENG LI; SHUANG XIA LUO; YU JING ZHAO (Journal of Genetics, 2015)

Characterization and risk assessment of polychlorinated biphenyls in soils and rice tissues in a suburban paddy field of the Pearl River Delta, South China - Qilu Li; Yan Wang; Chunling Luo; Jun Li; Gan Zhang (Environmental Science and Pollution Research, 2015)

Analysis of the sucrose synthase gene family in tobacco: structure, phylogeny, and expression patterns - Zhong Wang; Pan Wei; Mingzhu Wu; Yalong Xu; Feng Li; Zhaopeng Luo; Jianfeng Zhang; Ang Chen; Xiaodong Xie; Peijian Cao; Fucheng Lin; Jun Yang (Planta, 2015)

The concentration of selenium matters: a field study on mercury accumulation in rice by selenite treatment in qingzhen, Guizhou, China - Yu-Feng Li; Jiating Zhao; Yunyun Li; Hanjun Li; Junfang Zhang; Bai Li; Yuxi Gao; Chunying Chen; Manyi Luo; Rui Huang; Jun Li (Plant and Soil, 2015)

Genes regulating lipid and protein metabolism are highly expressed in mammary gland of lactating dairy goats - Hengbo Shi; Jiangjiang Zhu; Jun Luo; Wenting Cao; Huaiping Shi; Dawei Yao; Jun Li; Yuting Sun; Huifen Xu; Kang Yu; Juan J. Loor (Functional & Integrative Genomics, 2015)

How Does Experience Modulate Auditory Spatial Processing in Individuals with Blindness? - Qian Tao; Chetwyn C. H. Chan; Yue-jia Luo; Jian-jun Li; Kin-hung Ting; Jun Wang; Tatia M. C. Lee (Brain Topography, 2015)

Expression Analysis and Binding Assays in the Chemosensory Protein Gene Family Indicate Multiple Roles in Helicoverpa armigera - Zhao-Qun Li; Shuai Zhang; Jun-Yu Luo; Jing Zhu; Jin-Jie Cui; Shuang-Lin Dong (Journal of Chemical Ecology, 2015)

In vivo expression patterns of microRNAs of Gallid herpesvirus 2 (GaHV-2) during the virus life cycle and development of Marek’s disease lymphomas - Pu Zhao; Xiu-Jie Li; Man Teng; Lu Dang; Zu-Hua Yu; Jia-Qi Chi; Jing-Wei Su; Gai-Ping Zhang; Jun Luo (Virus Genes, 2015)

Genome-wide identification of phenolic acid biosynthetic genes in Salvia miltiorrhiza - Bo Wang; Wei Sun; Qiushi Li; Ying Li; Hongmei Luo; Jingyuan Song; Chao Sun; Jun Qian; Yingjie Zhu; Alice Hayward; Haibin Xu; Shilin Chen (Planta, 2015)

Characterization of regulatory regions involved in the inducible expression of chiB in Bacillus thuringiensis - Chi-Chu Xie; Jin Shi; Hai-Yun Jia; Peng-Fei Li; Yang Luo; Jun Cai; Yue-Hua Chen (Archives of Microbiology, 2015)

Remote Ischemic Postconditioning Alleviates Cerebral Ischemic Injury by Attenuating Endoplasmic Reticulum Stress-Mediated Apoptosis - Xiangrong Liu; Shangfeng Zhao; Fang Liu; Jun Kang; Ao Xiao; Fang Li; Chencheng Zhang; Feng Yan; Haiping Zhao; Mei Luo; Yumin Luo; Xunming Ji (Translational Stroke Research, 2014)

A prepared anti-MSTN polyclonal antibody reverses insulin resistance of diet-induced obese rats via regulation of PI3K/Akt/mTOR&FoxO1 signal pathways - Liang Tang; Chen-tao Liu; Xu-dan Wang; Kai Luo; Di-di Zhang; Ai-ping Chi; Jing Zhang; Li-jun Sun (Biotechnology Letters, 2014)

A new phenyl glycoside from the aerial parts of Equisetum hyemale - Mei Jin; Changhao Zhang; Tie Zheng; Dalei Yao; Le Shen; Jie Luo; Zhe Jiang; Juan Ma; Xue-Jun Jin; Jiongmo Cui; Jung Joon Lee; Gao Li (Natural Product Research, 2014)

Detection of polyketide synthase and nonribosomal peptide synthetase biosynthetic genes from antimicrobial coral-associated actinomycetes - Jie Li; Jun-De Dong; Jian Yang; Xiong-Ming Luo; Si Zhang (Antonie van Leeuwenhoek, 2014)

Protective effect of vitexin compound B-1 against hypoxia/reoxygenation-induced injury in differentiated PC12 cells via NADPH oxidase inhibition - Zhong-Bao Yang; Bin Tan; Ting-Bo Li; Zheng Lou; Jun-Lin Jiang; Ying-Jun Zhou; Jie Yang; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

The expression and functional role of a FOXC1 related mRNA-lncRNA pair in oral squamous cell carcinoma - Xiang-pan Kong; Jie Yao; Wei Luo; Fu-kui Feng; Jun-tao Ma; Yi-peng Ren; De-li Wang; Rong-fa Bu (Molecular and Cellular Biochemistry, 2014)

Two Chinese pedigrees for adenomatous polyposis coli: new mutations at codon 1309 and predisposition to phenotypic variations - Dai-Xiang Liao; Bing Li; Xue-Mei Du; Jun-Hui Yu; Hong Chang; Zhi-Qiang Wu; Hao-Jie Hao; You-Xin Wang; Wei-Dong Han; Shu-jun Cheng; Cheng-Hua Luo (Familial Cancer, 2014)

Fine mapping of a dominant thermo-sensitive genic male sterility gene (BntsMs) in rapeseed (Brassica napus) with AFLP- and Brassica rapa-derived PCR markers - Xinhua Zeng; Wenpin Li; Yuhuan Wu; Fang Liu; Junling Luo; Yinglong Cao; Li Zhu; Yunjing Li; Jun Li; Qingbo You; Gang Wu (Theoretical and Applied Genetics, 2014)

A promoter analysis of MOTHER OF FT AND TFL1 1 (JcMFT1), a seed-preferential gene from the biofuel plant Jatropha curcas - Yan-Bin Tao; Li Luo; Liang-Liang He; Jun Ni; Zeng-Fu Xu (Journal of Plant Research, 2014)

Notch inhibition promotes fetal liver stem/progenitor cells differentiation into hepatocytes via the inhibition of HNF-1β - Tao Wang; Tao Chen; Hong-yin Liang; Hong-tao Yan; Ning Lin; Li-ye Liu; Hao Luo; Zhu Huang; Nan-lin Li; Wei-hui Liu; Li-jun Tang (Cell and Tissue Research, 2014)

6′- O -Caffeoylarbutin inhibits melanogenesis in zebrafish - Min Xu; Qiao-Cong Lao; Ping Zhao; Xiao-Yu Zhu; Hong-Tao Zhu; Xu-Lu Luo; Chong-Ren Yang; Jian-Hui He; Chun-Qi Li; Ying-Jun Zhang (Natural Product Research, 2014)

Characterization of OsDREB6 responsive to osmotic and cold stresses in rice - Ya-Guang Ke; Zhi-Jun Yang; Shun-Wu Yu; Tian-Fei Li; Jin-Hong Wu; Huan Gao; Ya-Ping Fu; Li-Jun Luo (Journal of Plant Biology, 2014)

Silencing heat shock protein 27 (HSP27) inhibits the proliferation and migration of vascular smooth muscle cells in vitro - Jie Huang; Liang-di Xie; Li Luo; Su-li Zheng; Hua-jun Wang; Chang-sheng Xu (Molecular and Cellular Biochemistry, 2014)

Alda-1 reduces cerebral ischemia/reperfusion injury in rat through clearance of reactive aldehydes - Si-Hai Fu; Hong-Feng Zhang; Zhong-Bao Yang; Ting-Bo Li; Bin Liu; Zheng Lou; Qi-Lin Ma; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Cysteine residues 87 and 320 in the amino terminal domain of NMDA receptor GluN2A govern its homodimerization but do not influence GluN2A/GluN1 heteromeric assembly - Xiao-Min Zhang; Xin-You Lv; Yang Tang; Li-Jun Zhu; Jian-Hong Luo (Neuroscience Bulletin, 2013)

Application of Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration in the Management of Mediastinal and Hilar Lymphadenopathy Without Intrapulmonary Mass: Experience from the Largest Cancer Center of Southern China - Guang-yu Luo; Pei-qiang Cai; Jie-hua He; Jian-jun Li; Yin Li; Hong-bo Shan; Rong Zhang; Xiao-yan Gao; Xiang-ming Lao; Guo-liang Xu (Cell Biochemistry and Biophysics, 2013)

Lipopolysaccharides Reduce Adipogenesis in 3T3-L1 Adipocytes Through Activation of NF-κB Pathway and Downregulation of AMPK Expression - Lifeng Wang; Linlin Li; Xinjian Ran; Mei Long; Minfang Zhang; Yicun Tao; Xin Luo; Ye Wang; Yi Jiao; Xinmin Mao; Jun Ren (Cardiovascular Toxicology, 2013)

Gardiquimod inhibits the expression of calcium-induced differentiation markers in HaCaT cells - Bo Jia; Xin Luo; Feng-Wei Cheng; Lei Li; Dao-Jun Hu; Fang Wang; Sheng-Quan Zhang (Molecular Biology Reports, 2013)

Characterization of embryogenesis and early larval development in the Pacific triton, Charonia tritonis (Gastropoda: Caenogastropoda) - Lü-Ping Zhang; Jian-Jun Xia; Peng-Fei Peng; Hai-Peng Li; Peng Luo; Chao-Qun Hu (Invertebrate Reproduction & Development, 2013)

Molecular cloning of vasa gene and the effects of LHRH-A on its expression in blue tilapia Oreochromis aureus - Jun Xiao; Yongju Luo; Libing Chen; Li Yang; Yulin Huang; Zhongbao Guo; Enyan Guo; Zhanyang Tang; Ming Zhang; Xi Gan (Fish Physiology and Biochemistry, 2013)

Different mechanisms lead to convergence of reproductive strategies in two lacertid lizards (Takydromus wolteri and Eremias argus) - Bao-Jun Sun; Shu-Ran Li; Xue-Feng Xu; Wen-Ge Zhao; Lai-Gao Luo; Xiang Ji; Wei-Guo Du (Oecologia, 2013)

MicroRNA-200b targets CREB1 and suppresses cell growth in human malignant glioma - Biao Peng; Su Hu; Qinming Jun; Dongdong Luo; Xun Zhang; Hailin Zhao; Dan Li (Molecular and Cellular Biochemistry, 2013)

Quantification of serum HBXAP DNA in lung cancer patients by quantitative fluorescent polymerase chain reaction - Yu-Lei Hou; Hui Chen; Ming-Jian Ge; Feng-Zeng Li; Cheng-Jun Xue; Yan-Feng Wu; Hai-Xia Luo (Molecular Biology Reports, 2013)

Neural mechanisms of shifts of spatial attention induced by object words with spatial associations: an ERP study - Entao Zhang; Junlong Luo; Jijia Zhang; Yan Wang; Jun Zhong; Qiwei Li (Experimental Brain Research, 2013)

Two new C-15 enolic acyl phragmalin-type limonoids from Chukrasia tabularis var. velutina - Jun Luo; Yi Li; Jun-Song Wang; Ling-Yi Kong (Natural Product Research, 2013)

Establishment of SYBR green-based qPCR assay for rapid evaluation and quantification for anti-Hantaan virus compounds in vitro and in suckling mice - Fei Wei; Jin-lin Li; Jia-xin Ling; Liang-Jun Chen; Ning Li; Yuan-Yuan Liu; Fan Luo; Hai-Rong Xiong; Wei Hou; Zhan-Qiu Yang (Virus Genes, 2013)

Transforming growth factor-β1 induces matrix metalloproteinase-9 expression in rat vascular smooth muscle cells via ROS-dependent ERK–NF-κB pathways - Hao Zhang; Zhi-Wei Wang; Hong-Bing Wu; Zhi Li; Luo-Cheng Li; Xiao-Ping Hu; Zong-Li Ren; Bai-Jun Li; Zhi-Peng Hu (Molecular and Cellular Biochemistry, 2012)

Greenhouse tomato–cucumber yield and soil N leaching as affected by reducing N rate and adding manure: a case study in the Yellow River Irrigation Region China - Ying Zhao; Jiang-Hang Luo; Xiao-Qun Chen; Xue-Jun Zhang; Wei-Li Zhang (Nutrient Cycling in Agroecosystems, 2012)

Beraprost sodium attenuates cigarette smoke extract-induced apoptosis in vascular endothelial cells - Yan Chen; Hong Luo; Naixin Kang; Chaxiang Guan; Yingjiao Long; Jun Cao; Qin Shen; Junli Li; Min Yang; Hong Peng; Ping Chen (Molecular Biology Reports, 2012)

Effect of C/N ratios on the performance of earthworm eco-filter for treatment of synthetics domestic sewage - Yong-Jun Zhao; Cheng Yan; Yin-Liang Li; Ji-Hua Li; Mo Yang; Er Nie; Zheng Zheng; Xing-Zhang Luo (Environmental Science and Pollution Research, 2012)

The expression of pentraxin 3 and tumor necrosis factor-alpha is increased in preeclamptic placental tissue and maternal serum - Ping Zhou; Xin Luo; Hong-bo Qi; Wen-jun Zong; Hua Zhang; Dan-dan Liu; Qing-shu Li (Inflammation Research, 2012)

Identification and Binding Characterization of Three Odorant Binding Proteins and One Chemosensory Protein from Apolygus lucorum (Meyer-Dur) - Jin-Feng Hua; Shuai Zhang; Jin-Jie Cui; Dao-Jie Wang; Chun-Yi Wang; Jun-Yu Luo; Li-Min Lv (Journal of Chemical Ecology, 2012)

Effects of indole-3-acetic acid and auxin transport inhibitors on the style curvature of three Alpinia species (Zingiberaceae) - Yin-Ling Luo; Ting-Ju Bi; Dong Li; Zhi-Long Su; Chuan Tao; Yan-Jiang Luo; Qing-Jun Li (Acta Physiologiae Plantarum, 2012)

Proteomic analysis of the nuclear phosphorylated proteins in dairy cow mammary epithelial cells treated with estrogen - Jian-guo Huang; Xue-jun Gao; Qing-zhang Li; Li-min Lu; Rong Liu; Chao-chao Luo; Jia-li Wang; Qiao Bin; Xin Jin (In Vitro Cellular & Developmental Biology - Animal, 2012)

Induction of Chlamydospore Formation in Fusarium by Cyclic Lipopeptide Antibiotics from Bacillus subtilis C2 - Lei Li; MingChuan Ma; Rong Huang; Qing Qu; GuoHong Li; JinWei Zhou; KeQin Zhang; KaiPing Lu; XueMei Niu; Jun Luo (Journal of Chemical Ecology, 2012)

A novel gene IBF1 is required for the inhibition of brown pigment deposition in rice hull furrows - Tian Shao; Qian Qian; Ding Tang; Jun Chen; Ming Li; Zhukuan Cheng; Qiong Luo (Theoretical and Applied Genetics, 2012)

Enzymatic fingerprints of polysaccharides of Dendrobium officinale and their application in identification of Dendrobium species - Xue-Qiang Zha; Li-Hua Pan; Jian-Ping Luo; Jun-Hui Wang; Peng Wei; Vibha Bansal (Journal of Natural Medicines, 2012)

Polymorphisms in luteinizing hormone receptor and hypothalamic gonadotropin-releasing hormone genes and their effects on sperm quality traits in Chinese Holstein bulls - Li-Ping Sun; Qing-Zhi Du; Ya-Pan Song; Jun-Na Yu; Shu-Juan Wang; Lei Sang; Luo-Wen Song; Yao-Min Yue; Yu-Ze Lian; Sheng-Li Zhang; Guo-Hua Hua; Shu-Jun Zhang; et al. (Molecular Biology Reports, 2012)

Inhibition of matrine against gastric cancer cell line MNK45 growth and its anti-tumor mechanism - Cong Luo; Hai Jun Zhong; Li Ming Zhu; Xian Guo Wu; Jie Er Ying; Xiao Hong Wang; Wang Xia LÜ; Qi Xu; Yong Liang Zhu; Jian Huang (Molecular Biology Reports, 2012)

Fertilization increases paddy soil organic carbon density - Shao-xian Wang; Xin-qiang Liang; Qi-xiang Luo; Fang Fan; Ying-xu Chen; Zu-zhang Li; Huo-xi Sun; Tian-fang Dai; Jun-nan Wan; Xiao-jun Li (Journal of Zhejiang University-SCIENCE B, 2012)

Systematic assessment and meta-analysis of the efficacy and safety of fasudil in the treatment of cerebral vasospasm in patients with subarachnoid hemorrhage - Guang Jian Liu; Zheng Jun Wang; Yun Fu Wang; Li Li Xu; Xiao Ling Wang; Yong Liu; Guo Jun Luo; Guo Hou He; Yan Jun Zeng (European Journal of Clinical Pharmacology, 2012)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

Atmospheric deposition of Cd accumulated in the montane soil, Gongga Mt., China - Yanhong Wu; Haijian Bin; Jun Zhou; Ji Luo; Dong Yu; Shouqin Sun; Wei Li (Journal of Soils and Sediments, 2011)

Identification of host cell binding peptide from an overlapping peptide library for inhibition of classical swine fever virus infection - Xuewu Li; Li Wang; Dong Zhao; Gaiping Zhang; Jun Luo; Ruiguang Deng; Yanyan Yang (Virus Genes, 2011)

Quantitative trait loci for rice yield-related traits using recombinant inbred lines derived from two diverse cultivars - XU FENG BAI; LI JUN LUO; WEN HAO YAN; MALLIKARJUNA RAO KOVI; YONG ZHONG XING (Journal of Genetics, 2011)

Combined administration of D-galactose and aluminium induces Alzheimerlike lesions in brain - Fei Xiao; Xiao-Guang Li; Xiao-Yu Zhang; Jun-Dai Hou; Lian-Feng Lin; Qin Gao; Huan-Min Luo (Neuroscience Bulletin, 2011)

Subcellular localization of calcium during Alpinia mutica Roxb. (Zingiberaceae) style movement - Yin Ling Luo; Yan Jiang Luo; Qing Jun Li (Protoplasma, 2011)

Viral distribution and lesions in Kunming mice experimentally infected with porcine circovirus type 2b - Zhi-Bang Deng; Nai-Dong Wang; Dao-Jun Xu; An-Wen Yuan; Meng Ge; Wei Luo; Li-Qun Xue; Xing-Long Yu (Veterinary Research Communications, 2011)

Disseminated Penicillium Marneffei Infection in an SLE Patient: A Case Report and Literature Review - Di-Qing Luo; Ming-Chun Chen; Jun-Hua Liu; Zhi Li; Hui-Ting Li (Mycopathologia, 2011)

Degradation of dye rhodamine B under visible irradiation with Prussian blue as a photo-Fenton reagent - Shou-Qing Liu; Shi Cheng; Li Luo; Hong-Ying Cheng; Song-Jun Wang; Shuai Lou (Environmental Chemistry Letters, 2011)

Effect of high glucose levels on the calcification of vascular smooth muscle cells by inducing osteoblastic differentiation and intracellular calcium deposition via BMP-2/Cbfα-1 pathway - Fang Liu; Hui Zhong; Jing-yuan Liang; Ping Fu; Zhi-juan Luo; Li Zhou; Rong Gou; Jun Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Effects of light and low temperature on the reciprocal style curvature of Flexistylous Alpinia Species (Zingiberaceae) - Yin-Ling Luo; Qing-Jun Li (Acta Physiologiae Plantarum, 2010)

A hybrid promoter-containing vector for direct cloning and enhanced expression of PCR-amplified ORFs in mammalian cells - Lei-ming You; Jun Luo; Ai-ping Wang; Gai-ping Zhang; Hai-bo Weng; Ya-nan Guo; Yun-chao Liu; Qiao-mu Li; Man Teng (Molecular Biology Reports, 2010)

AMP-activated protein kinase supports the NGF-induced viability of human HeLa cells to glucose starvation - Luo Ting; Wan Bo; Ruwei Li; Xinya Chen; Yingli Wang; Zhou Jun; Long Yu (Molecular Biology Reports, 2010)

Genetic analysis of strains of Japanese Encephalitis Virus isolated from swine in central China - Jian-Ming Fan; Jun Luo; Lu Chen; Man Teng; Dan Bu; Fang-Yu Wang; Li Wang; Chuan-Qing Wang; Gai-Ping Zhang (Virus Genes, 2010)

Isolation of high quality RNA and construction of a suppression subtractive hybridization library from ramie (Boehmeria nivea L. Gaud.) - Xu-xia Wang; Bo Wang; Li-jun Liu; Xiao-ping Cui; Jin-yu Yang; Hui Wang; Hui Jiang; Bei-bei Luo; Zhu Long; Wen-xiang Dou; Na Zhang; Ding-xiang Peng (Molecular Biology Reports, 2010)

Evidence for the Formation of the Male Gynogenetic Fish - Shaojun Liu; Qinbo Qin; Yuequn Wang; Hong Zhang; Rurong Zhao; Chun Zhang; Jing Wang; Wei Li; Lin Chen; Jun Xiao; Kaikun Luo; Min Tao; et al. (Marine Biotechnology, 2010)

Kinetic Study and Mathematical Modeling of Chromium(VI) Reduction and Microorganism Growth Under Mixed Culture - Bo Kong; Xiandong Zeng; Xiaoying Liu; Xuefang Li; Jun Li; Shenglian Luo; Wanzhi Wei (Current Microbiology, 2009)

The effect of root exudates from two transgenic insect-resistant cotton lines on the growth of Fusarium oxysporum - Xiao-gang Li; Biao Liu; Sondre Heia; Dou-dou Liu; Zheng-min Han; Ke-xin Zhou; Jin-jie Cui; Jun-yu Luo; Yang-ping Zheng (Transgenic Research, 2009)

A thermophilic and acid stable family-10 xylanase from the acidophilic fungus Bispora sp. MEY-1 - Huiying Luo; Jiang Li; Jun Yang; Hui Wang; Yuhui Yang; Huoqing Huang; Pengjun Shi; Tiezheng Yuan; Yunliu Fan; Bin Yao (Extremophiles, 2009)

Infectivity and propagation of attenuated infectious bursal disease virus in the chicken B-lymphocyte cell line DT40 - Jun Luo; Gai-Ping Zhang; Jian-Ming Fan; Man Teng; Lei-Ming You; Ling Zhou; Rui-Guang Deng; Xuan-Nian Wang; Yan-Yan Yang; Li Wang; Guang-Xu Xing; Na Cheng (Archives of Virology, 2009)

Centrifugal forces within usually-used magnitude elicited a transitory and reversible change in proliferation and gene expression of osteoblastic cells UMR-106 - Juan Li; Lingyong Jiang; Ga Liao; Guoping Chen; Ying Liu; Jun Wang; Yi Zheng; Songjiao Luo; Zhihe Zhao (Molecular Biology Reports, 2009)

Activation of the integrins α5β1 and αvβ3 and focal adhesion kinase (FAK) during arteriogenesis - Wei-Jun Cai; Ming Bo Li; Xiaoqiong Wu; Song Wu; Wu Zhu; Dan Chen; Mingying Luo; Inka Eitenmüller; Andreas Kampmann; Jutta Schaper; Wolfgang Schaper (Molecular and Cellular Biochemistry, 2009)

Relationships Among Genetic Makeup, Active Ingredient Content, and Place of Origin of the Medicinal Plant Gastrodia Tuber - Jun Tao; Zhi-yong Luo; Chikira Ismail Msangi; Xiao-shun Shu; Li Wen; Shui-ping Liu; Chang-quan Zhou; Rui-xin Liu; Wei-xin Hu (Biochemical Genetics, 2009)

Isolation and characterization of microsatellite markers for the endangered Taxus yunnanensis - Ying-Chun Miao; Jian-Rong Su; Zhi-Jun Zhang; Hui Li; Jing Luo; Ya-Ping Zhang (Conservation Genetics, 2008)

The Prevalence of Type 2 Diabetes and Hypertension in Uygur and Kazak Populations - Yicun Tao; Xinmin Mao; Zijing Xie; Xinjian Ran; Xiaoyan Liu; Ye Wang; Xin Luo; Mengying Hu; Wenning Gen; Minfang Zhang; Tao Wang; Jun Ren; et al. (Cardiovascular Toxicology, 2008)

Analysis of Prevalence and Risk Factors of Hypertension Among Uygur Adults in Tushala and Hetian Xinjiang Uygur Autonomous Region - Lin-Lin Li; Xiao-Yan Liu; Jian-Xin Ran; Ye Wang; Xin Luo; Tao Wang; Jun Ren; Mayinuer Aisha; Rebiya Abudureheman; Adalaiti Xiawudong; Xiao-Chun Zhang; Xin-Min Mao (Cardiovascular Toxicology, 2008)

The role of extracellular matrix, integrins, and cytoskeleton in mechanotransduction of centrifugal loading - Juan Li; Zhihe Zhao; Jun Wang; Guoping Chen; Jingyuan Yang; Songjiao Luo (Molecular and Cellular Biochemistry, 2008)

A major QTL associated with cold tolerance at seedling stage in rice (Oryza sativa L.) - Qiaojun Lou; Liang Chen; Zongxiu Sun; Yongzhong Xing; Jun Li; Xiaoyan Xu; Hanwei Mei; Lijun Luo (Euphytica, 2007)

Acetylene-Substituted Two-Photon Absorbing Molecules With Rigid Elongated Pi-Conjugation: Synthesis, Spectroscopic Properties and Two-Photon Fluorescence Cell Imaging Applications - Bo Liu; Hai-Li Zhang; Jun Liu; Zhen-Li Huang; Yuan-Di Zhao; Qing-Ming Luo (Journal of Fluorescence, 2007)

Expression of a truncated ripening inhibitor (RIN) protein from tomato and production of an anti-RIN antibody - Hong-Liang Zhu; Ben-Zhong Zhu; Ya-Li Zhang; Yi Shao; Xiao-Guang Wang; Yuan-Hong Xie; An-Jun Chen; Ying-Cong Li; Hui-Qin Tian; Yun-Bo Luo (Biotechnology Letters, 2007)

Mutational analysis of the GDD sequence motif of classical swine fever virus RNA-dependent RNA polymerases - Yujing Wang; Ming Xiao; Jun Chen; Weiqiong Zhang; Jianglan Luo; Kan Bao; Ming Nie; Jiakuan Chen; Bo Li (Virus Genes, 2007)

Variants of Green Fluorescent Protein GFPxm - Wen-Xin Luo; Tong Cheng; Bao-Quan Guan; Shao-Wei Li; Ji Miao; Jun Zhang; Ning-Shao Xia (Marine Biotechnology, 2006)

Variants of Green Fluorescent Protein GFPxm - Wen-Xin Luo; Tong Cheng; Bao-Quan Guan; Shao-Wei Li; Ji Miao; Jun Zhang; Ning-Shao Xia (Marine Biotechnology, 2006)

Distribution patterns of polychlorinated biphenyls in soils collected from Zhejiang province, east China - Jun Gao; Yongming Luo; Qingbo Li; Haibo Zhang; Longhua Wu; Jing Song; Wei Qian; Peter Christie; Shengming Chen (Environmental Geochemistry and Health, 2006)

Species diversity of Lachnum (Helotiales, Hyaloscyphaceae) from temperate China - Ming Ye; Shu-qing Cao; Shao-tong Jiang; Li-jun Pan; Shui-zhong Luo; Xing-jiang Li (Journal of Zhejiang University-SCIENCE B, 2006)

Cloning and characterization of an HDZip I gene GmHZ1 from soybean - Yong-Jun Wang; Yi-Dan Li; Guang-Zuo Luo; Ai-Guo Tian; Hui-Wen Wang; Jin-Song Zhang; Shou-Yi Chen (Planta, 2005)

Fenofibrate decreases asymmetric dimethylarginine level in cultured endothelial cells by inhibiting NF-κB activity - Tian-Lun Yang; Mei-Fang Chen; Bai-Lin Luo; Qi-Ying Xie; Jun-Lin Jiang; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Effect of fenofibrate on LDL-induced endothelial dysfunction in rats - Tian-Lun Yang; Mei-Fang Chen; Bai-Ling Luo; Jing Yu; Jun-Lin Jiang; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Spatial pattern and compositive structure of forests in Guizhou - Yao Yonghui; Zhang Baiping; Zhou Chenghu; Luo Yang; Zhu Jun; Qin Gang; Li Baolin; Chen Xiaodong (Journal of Geographical Sciences, 2002)

Bioluminescence of Aequorea macrodactyla, a Common Jellyfish Species in the East China Sea - Ning-Shao Xia; Wen-Xin Luo; Jun Zhang; Xiao-Yan Xie; Hai-Jie Yang; Shao-Wei Li; Ming Chen; Mun-Hon Ng (Marine Biotechnology, 2002)